Forming belts for producing formed nonwovens exhibiting high visual resolution
By depositing fibers on the forming belt to form a nonwoven fabric with three-dimensional characteristic structure, the problem of difficulty in achieving high visual resolution in the prior art is solved, and a nonwoven fabric with high aesthetics and functionality is achieved.
Patent Information
- Application Number
- CN202310038342.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-18
- Filing Date
- 2020-03-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-03-12
AI Technical Summary
Existing nonwoven fabrics are difficult to exhibit three-dimensional surface features with high visual resolution and lack effective manufacturing methods and equipment to achieve this goal.
A molded nonwoven fabric formed on the forming belt using continuous spunbond filaments, and a fabric with three-dimensional characteristic structure is formed by depositing fibers on the forming belt to achieve high visual resolution.
It achieves high visual resolution of nonwoven fabrics, improves the aesthetics and functionality of the fabrics, and is suitable for personal care products, clothing, medical products and cleaning products.
Smart Images

Figure CN116043420B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to forming belts for producing formed three-dimensional nonwoven fabrics that exhibit high visual resolution. Background Art
[0002] Nonwoven fabrics can be used for a variety of applications, including absorbent personal care products, clothing, medical applications and cleaning applications. Nonwoven personal care products include baby care products such as diapers, child care products such as training pants, feminine care products such as sanitary napkins, and adult care products such as incontinence products, pads and pants. Nonwoven clothing includes protective work clothes and medical clothing such as surgical gowns. Other nonwoven medical applications include nonwoven wound dressings and surgical dressings. Nonwoven cleaning applications include towels and wipes.
[0003] The various properties of nonwoven fabrics can determine the suitability of nonwoven fabrics for specific applications. Therefore, nonwoven fabrics can be processed to have different combinations of properties to meet different needs. The variable properties of nonwoven fabrics include liquid handling properties, such as wettability, distribution and absorbency; strength properties, such as tensile strength and tear strength; softness properties; and durability properties, such as abrasion resistance. The physical shape / pattern of the nonwoven fabric also affects the functionality and aesthetics of the nonwoven fabric. In addition, the aesthetics of the nonwoven fabric can be the key to consumers' preferences for consumer products including such nonwoven fabrics, because the nonwoven fabric aesthetics can convey the value, quality, strength, softness, etc. of the product. An exemplary method of aesthetically conveying many commonly desired properties in patterned nonwoven fabrics is by showing a textured pattern with high visual resolution (i.e., a visually clear pattern). Visually clear patterns provide observers with a higher quality perception because such nonwoven fabric patterns show clean, well-defined texture contrast lines, rather than faded, blurred or difficult to visually identify texture contrast lines.
[0004] Despite previous advances in the nonwoven fabric art, there remains a need for improved nonwoven fabrics having visually discernible regions with three-dimensional surface features, wherein the visually discernible regions exhibit high visual resolution.
[0005] Additionally, there remains a need for methods and apparatuses, particularly forming belts, for making improved nonwoven fabrics having visually discernible regions with three-dimensional surface features, wherein the visually discernible regions exhibit high visual resolution.
[0006] Additionally, there remains a need for articles, including absorbent articles, utilizing improved nonwoven fabrics having visually discernible regions with three-dimensional surface features, wherein the visually discernible regions exhibit high visual resolution. Summary of the invention
[0007] The present invention discloses a forming belt for producing a nonwoven fabric. The nonwoven fabric may include a first surface and a second surface and at least a first visually discernible area of a three-dimensional feature structure on one of the first surface or the second surface. Each of the three-dimensional features may define a micro-region including a first area and a second area. The first area and the second area may have a difference in the value of an intensity characteristic, and the first visually discernible area may exhibit a high visual resolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 is a photograph of an example of a formed nonwoven fabric of the present disclosure.
[0009] Figure 2 is a photograph of an example of a formed nonwoven fabric of the present disclosure.
[0010] Figure 3 is a photograph of an example of a formed nonwoven fabric of the present disclosure.
[0011] Figure 4 For Figure 1 A cross-section of a portion of a fabric of the present disclosure is shown.
[0012] Figure 5A Schematically, a cross section of a filament produced from a primary component A and a secondary component B arranged side by side is shown.
[0013] Figure 5B As a schematic diagram, a cross section of a filament produced with a primary component A and a secondary component B in an eccentric sheath / core arrangement is shown.
[0014] Figure 5C As a schematic diagram, a cross section of a filament made with a primary component A and a secondary component B in a concentric sheath / core arrangement is shown.
[0015] Figure 6 A perspective photograph of a trilobal bicomponent fiber.
[0016] Figure 7 is a schematic diagram of an apparatus for preparing the fabric of the present disclosure.
[0017] Figure 8 for Figure 7 Enlarged view of the middle part A.
[0018] Fig. 9 for Figure 8 Enlarged view of the middle part C.
[0019] Fig.10 for Figure 7 Enlarged view of middle part B.
[0020] Fig.11 The following are photos of examples of the present disclosure.
[0021] Fig.12 is a photograph of a portion of a forming belt that may be used in the present disclosure.
[0022] Fig.13 for Fig.12 A cross-sectional view of a portion of the forming belt is shown.
[0023] Fig.14 For the preparation Fig.12 An image of a portion of a mask forming a strip is shown.
[0024] Fig.15 For the preparation Fig.16 An image of a portion of a mask forming a strip is shown.
[0025] Fig.16 is a photograph of a portion of a forming belt that may be used in the present disclosure.
[0026] Fig.17 For the preparation Fig.18 An image of a portion of a mask forming a strip is shown.
[0027] Fig.18 is a photograph of a portion of a forming belt that may be used in the present disclosure.
[0028] Fig.19 is a photograph of a portion of a forming belt that may be used in the present disclosure.
[0029] Fig. 20 For the preparation Fig.19 Image of mask showing forming tape.
[0030] Fig.21 For Fig.19 A photograph of a fabric of the present disclosure produced on a forming belt is shown.
[0031] Fig. 22 is a schematic perspective view of a forming belt of the present disclosure.
[0032] Fig.23 is a plan view of a nonwoven substrate comprising a nonwoven fabric of the present disclosure.
[0033] Fig.24 is a plan view of a nonwoven substrate comprising a nonwoven fabric of the present disclosure.
[0034] Fig.25A is a plan view of a fabric of the present disclosure with portions removed to allow for measurement of local basis weight.
[0035] Fig.25B is a plan view of a fabric of the present disclosure with portions removed to allow for measurement of local basis weight.
[0036] Fig.26 is a graphical representation of the cross-directional variation in basis weight of the fabrics of the present disclosure.
[0037] Fig. 27 A schematic diagram of a package disclosed herein.
[0038] Fig.28 is a plan view of an absorbent article of the present disclosure.
[0039] Fig.29 A plan view of an absorbent article of the present disclosure
[0040] Fig.30 for Fig.28 A cross-sectional view of section 29-29.
[0041] Fig.31 is a plan view of an absorbent article of the present disclosure.
[0042] Fig.32 for Fig.31 A cross-sectional view of section 32-32.
[0043] Fig.33 is a plan view of an absorbent article of the present disclosure.
[0044] Fig.34 for Fig.33 A cross-sectional view of section 34-34.
[0045] Fig.35 for Fig.33 A cross-sectional view of section 35-35.
[0046] Fig.36 is a photograph of an example of a formed nonwoven fabric of the present disclosure.
[0047] Fig.37 is a photograph of an example of a formed nonwoven fabric of the present disclosure.
[0048] Fig.38 is a photograph of an example of a formed nonwoven fabric of the present disclosure.
[0049] Fig.39 for Fig.38 Photograph of a cross section of the sample shown.
[0050] Fig.40 is a micro-CT perspective image of an example of a formed nonwoven fabric of the present disclosure.
[0051] Fig.41 is a micro-CT perspective image of an example of a formed nonwoven fabric of the present disclosure.
[0052] Fig.42 for Fig.40and Fig.41 Micro-CT image of a cross section of the example shown.
[0053] Fig.43 for Fig.40 and Fig.41 Micro-CT plan view image of the example shown.
[0054] Fig.44 is a graphical depiction of various benefits of the formed nonwoven fabrics of the present disclosure.
[0055] Fig.45 A photographic view image of a portion of an example of a formed nonwoven fabric of the present disclosure.
[0056] Fig.46 A photographic view image of a portion of an example of a formed nonwoven fabric of the present disclosure.
[0057] Fig.47 A photographic view image of a portion of an example of a formed nonwoven fabric of the present disclosure.
[0058] Fig.48 A photographic view image of a portion of an example of a formed nonwoven fabric of the present disclosure.
[0059] Fig.49 for Fig.47 and Fig.48 Photograph of a cross section of the sample shown.
[0060] Fig.50 A photographic view image of a portion of an example of a formed nonwoven fabric of the present disclosure.
[0061] Fig.51 A photographic view image of a portion of an example of a formed nonwoven fabric of the present disclosure.
[0062] Fig.52 A photographic view image of a portion of an example of a formed nonwoven fabric of the present disclosure.
[0063] Fig.53 A photographic view image of a portion of an example of a formed nonwoven fabric of the present disclosure.
[0064] Fig.54 for Fig.40 and Fig.41 Example shown is a micro-CT plan view image after additional processing.
[0065] Fig.55 for Fig.54 A graphical depiction of various beneficial effects of the disclosed invention is shown.
[0066] Fig.56 is a schematic diagram of an apparatus for preparing the fabric of the present disclosure.
[0067] Fig.57 is a photograph of an example of a formed nonwoven fabric of the present disclosure.
[0068] Fig.58 is a photograph of an example of a formed nonwoven fabric of the present disclosure having three identification locations utilized in the In-Article Gray Scale Variation Test Method.
[0069] Fig.59 To plot a graph of various data points generated from samples of formed nonwoven fabrics of the present disclosure using the Haralick Maximum Contrast Test Method.
[0070] Fig.60 Included are images of six separate samples of formed nonwoven fabrics of the present disclosure that were used to measure grayscale variation using the Between-Article Grayscale Variation Test Method.
[0071] Fig.61 A graph is plotted of various data points generated from a sample of a forming belt used to produce a formed nonwoven fabric. DETAILED DESCRIPTION
[0072] The present disclosure provides a shaped nonwoven fabric formed directly on a shaped forming belt with continuous spunbond filaments in a single forming process. The fabric of the present disclosure can present a shape corresponding to the shape of the forming belt. The fabric of the present disclosure prepared on the forming belt of the present disclosure with the method of the present disclosure can be particularly useful for personal care products, clothes, medical products, and cleaning products. The shaped nonwoven fabric can be fluid-permeable so that it is used as the top sheet, back sheet nonwoven, acquisition layer, distribution layer, or other component layers of a diaper, or the top sheet, back sheet nonwoven, acquisition layer, distribution layer, or other component layers of a sanitary towel, the top sheet, back sheet nonwoven, acquisition layer, distribution layer, or other component layers of an adult incontinence pad or pants, or the liner of a floor cleaning tool.
[0073] In some embodiments herein, the beneficial characteristic structures of nonwoven fabrics will be described in the context of the total area of the nonwoven fabric. The total area can be an area determined by a size suitable for certain uses, and the various characteristic structures of the present invention provide beneficial properties for the certain uses. For example, the total area of a fabric can be the total area of a fabric having a size that makes it suitable for use as a top sheet, back sheet nonwoven, acquisition layer, distribution layer, or other component layer of a diaper, or a top sheet, back sheet nonwoven, acquisition layer, distribution layer, or other component layer of a sanitary napkin, a top sheet, back sheet nonwoven, acquisition layer, distribution layer, or other component layer of an adult incontinence pad or pants, or a pad of a floor cleaning tool. Therefore, the total area can be based on a width dimension in the range of 3 cm wide to 50 cm wide and a length dimension in the range of 10 cm long to 100 cm long, thereby producing a 30 cm 2 Up to 500cm 2 The foregoing ranges include every integer size between the range boundaries as if explicitly stated. By way of example, a 176 cm 2 The total area of the formed nonwoven fabric is disclosed in the above ranges. As will be understood from the description herein, the total area of the formed nonwoven fabric can be an area less than the area of the web of nonwoven material, which is a part of the web when the formed nonwoven fabric is commercially prepared. That is, in a given commercially prepared web of nonwoven material, there may be a plurality of formed nonwoven fabrics of the present invention, each of which has a total area less than the area of the web on which the formed nonwoven fabric is prepared.
[0074] A photograph of a representative example of a formed nonwoven fabric 10 is shown in Figures 1 to 3 The formed nonwoven fabric 10 may be a spunbond nonwoven substrate having a first surface 12 and a second surface 14. Figures 1 to 3 In the embodiment, the second surface 14 faces the observer and is opposite to the first surface 12. Figures 1 to 3 Not visible in but shown in Figure 4 The term "surface" is used broadly for descriptive purposes to refer to both sides of the web and is not intended to infer any necessary flatness or smoothness. Although the formed nonwoven fabric 10 is soft and flexible, it will be described in the flattened state, that is, in the context of one or more XY planes parallel to the flattened state, and which planes correspond to the planes of the cross direction CD and the planes of the machine direction MD, respectively, in web preparation technology, as shown in FIG. Figures 1 to 3 The length L along MD and the width W along CD determine the total area A of the nonwoven fabric 10. Figure 4 (It is Figure 1For descriptive purposes, the three-dimensional features of the formed nonwoven fabric are described as extending outwardly from the XY plane of the first surface 16 along the Z direction (see FIG. Figure 4 ). In one embodiment, the maximum dimension of the three-dimensional features in the Z direction may define the maximum distance between the plane of the first surface 16 and the XY plane of the second surface 18, which can be measured as the average thickness AC of the nonwoven fabric 10. The average thickness can be determined via an optical non-contact device, or it can be determined by an instrument involving spaced apart plates that measure the thickness of the nonwoven fabric placed between them under a predetermined pressure. It is not necessary for all three-dimensional features to have the same maximum dimension in the Z direction, but multiple three-dimensional features can have substantially the same maximum dimension in the Z direction determined by the fiber deposition process and the characteristics of the forming belt described below.
[0075] Figures 1 to 4 The exemplary fabrics shown in (as well as other fabrics disclosed herein) are fluid permeable. In one embodiment, the entire fabric may be considered fluid permeable. In one embodiment, a region or zone (described below) may be fluid permeable. As used herein, "fluid permeable" with respect to a fabric means that the fabric has at least one zone that allows liquid to pass through when a consumer product is used. For example, if a fabric is used as a top sheet on a disposable diaper, the fabric may have at least one zone that has a certain fluid permeability, thereby allowing urine, dilute BM, menstrual fluid or any other body exudate to pass through the absorbent core below. As used herein, "fluid permeable" with respect to a zone means that the zone exhibits a porous structure that allows liquid to pass through.
[0076] like Figures 1 to 4 As shown, the nonwoven fabric 10 may have a regular repeating pattern of a plurality of discrete identifiably different three-dimensional features (including a first three-dimensional feature 20, a second three-dimensional feature 22, and a third three-dimensional feature 24), such as Figure 2 and Figure 3 For example, in Figure 1 , the heart-shaped first three-dimensional feature 20 is identifiably different from the smaller, generally triangular-shaped second three-dimensional feature 22. The identifiable difference may be visual, such as a identifiably different size and / or shape.
[0077] The three-dimensional characteristic structure of nonwoven fabric 10 can be formed by directly depositing fibers onto a forming belt having a pattern of corresponding three-dimensional characteristic structures, such as by carding, air-laid method, spinning from solution or melt spinning. In a sense, nonwoven fabric 10 is molded onto a forming belt, which determines the shape of the three-dimensional characteristic structure of fabric 10. However, it is important that, as described herein, the apparatus and method of the present invention produce nonwoven fabric 10 so that in addition to presenting the shape of the forming belt due to the properties of the forming belt and the properties of the apparatus for forming the fabric, the fabric is also endowed with beneficial properties for personal care products, clothes, medical products, and cleaning products. Specifically, due to the properties of the forming belt and other equipment elements, as described below, the three-dimensional characteristic structure of nonwoven fabric 10 has strength characteristics, which can be different between the first and second regions in the microregion in the following manner (described more fully below) or can be different from feature structure to feature structure: the beneficial properties of nonwoven fabric 10 when used for personal care products, clothes, medical products, and cleaning products are provided. For example, the first three-dimensional feature structure 20 may have a basis weight or density that is different from the basis weight or density of the second three-dimensional feature structure 22, and both may have a basis weight or density that is different from the basis weight or density of the third three-dimensional feature structure 24, thereby providing beneficial aesthetic and functional properties related to fluid acquisition, distribution and / or absorption in a diaper or sanitary napkin.
[0078] It is believed that the differences in strength properties between the various three-dimensional features of the nonwoven fabric 10 are due to fiber distribution and compaction resulting from the apparatus and method described below. Fiber distribution occurs during the fiber deposition process, rather than during, for example, a post-production process such as a hydroentanglement process or an embossing process. Since the fibers are free to move during a process such as a melt spinning process, it is believed that the fibers will be more stably and permanently formed in the nonwoven fabric 10 with movement determined by the nature of the features and the air permeability of the forming belt and other processing parameters.
[0079] As can be seen in Figures 1 to 3 , and as can be understood from the description herein, different three-dimensional features can be defined by a visually discernible (relative to the interior of the three-dimensional feature) area, which can be in the form of a closed figure (such as Figure 1 and Figure 3 The heart shape in the Figure 2 and Figure 3 The closed figure may be a curved closed figure, such as Figure 1 and Figure 3 The visually discernible areas on the profile may be the following areas of the nonwoven fabric 10 that are most closely adjacent to the first surface 12 in the Z direction, such as Figure 4The regions 21 shown in the drawings may be located at least partially in or on the first plane 16 when in the flattened state. Figure 1 As shown, the first three-dimensional feature structure 20 is heart-shaped and, as shown in an exemplary first three-dimensional feature structure 20A, is defined by a curvilinear closed heart-shaped element. A curvilinear element can be understood as a linear element having a tangent vector V at any point along its length (in the presence of a closed shape) such that the tangent vector V has both an MD component and a CD component that change value over more than 50% of the length of the linear element of the closed figure. Of course, the figure need not be completely 100% closed, but the linear element may have breaks that do not deviate from the overall impression of the closed figure. As discussed below in the context of a forming belt, a curvilinear closed heart-shaped element that is visually discernible in outline is formed by corresponding closed heart-shaped raised elements on the forming belt to produce a heart-shaped closed figure on the fabric 10. In a repeating pattern, the individual shapes (in Figure 1 In the case of the first three-dimensional features in the nonwoven fabric 10, a heart shape) can result in an aesthetically pleasing soft pillow-like features over the total area OA of the second surface 14 of the fabric 10. In an embodiment where the nonwoven fabric 10 is used as a top sheet for a diaper or sanitary napkin, the second surface 14 of the nonwoven fabric 10 can face the body to deliver excellent aesthetic and performance benefits related to softness, compression resistance, and fluid absorption.
[0080] Specifically, in Figures 1 to 3 In the regularly repeating pattern of closed three-dimensional features shown, without being bound by theory, it is believed that the size of the various features, the average basis weight of the entire fabric 10 over its total area, and other processing parameters described below (which define different strength properties) contribute to beneficially improving compression recovery. It is believed that multiple relatively closely spaced, relatively small and relatively pillow-like three-dimensional features act as springs to resist compression and recover once the compressive force is removed. Compression recovery is important in, for example, the top sheet, back sheet nonwoven, acquisition layer, distribution layer, or other component layers of personal care products such as diapers, sanitary napkins, or adult incontinence pads, diapers or pants because such products are typically packaged and folded in a compressed state. For aesthetic and performance purposes, manufacturers of personal care products wish to retain most, if not all, of the existing thickness. Due to the soft look and feel and the pleasing crisp appearance, well-defined shapes, including very small shapes such as Figure 2The three-dimensionality of the characteristic structure formed by the small heart shape shown provides important aesthetic benefits. The three-dimensional characteristic structure also provides softness, improved absorbency, less leakage, and an overall improved user experience during use. However, during the folding, packaging, shipping and storage of personal care products, the necessary compression can cause the top sheet, backsheet nonwoven fabric, acquisition layer, distribution layer, or other component layers of the absorbent product to be permanently lost in thickness, thereby degrading the functional benefits of the existing product. The nonwoven fabrics of the present disclosure retain their existing three-dimensional characteristic structure to a significant extent, even after undergoing compression packaging and distribution in the compressed packaged state.
[0081] Table 1 below shows the compression recovery data of two embodiments of the present disclosure. Example 1 corresponds to Figure 1 The nonwoven fabric 10 is shown in FIG. Fig.12 and Fig.14 Example 2 corresponds to Figure 2 The nonwoven fabric 10 is shown in FIG. Fig.15 and Fig.16 As can be seen from the data, the fabric 10 of the present invention shows significant benefits in compression recovery when measured by the "Compression Aging Test." In one form, an absorbent article package having the compression recovery features of the present disclosure can have a reduced in-bag stack height, but still deliver the aesthetic, absorbency, and softness benefits of a ready-made diaper; or as if it had never been compressed and packaged. The present invention provides packages with reduced in-bag stack heights that allow caregivers to easily grasp and store the packages, while also providing manufacturers with reduced distribution costs, both while maintaining the ready-made aesthetic clarity, absorbency, or softness performance of the absorbent article.
[0082] Example 1 :
[0083] A bicomponent spunbond nonwoven fabric produced by spinning a 50:50 ratio of polyethylene sheath (Aspun-6850-A from Dow chemical company) and polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration, such as Figure 6 , which is a scanning electron microscope (SEM) showing a cross section of a bicomponent trilobal fiber. The nonwoven fabric is spun on a forming belt having a Fig.12 The repeating pattern is as follows Figure 7 and Figure 8 As described, it moves at a line speed of about 25 meters / minute to an average basis weight of 30 grams / square meter, with a repeating pattern of heart shapes, such as Figure 1The fibers of the fabric are further bonded on the first side 12 by heated compaction rolls 70 , 72 (described below) at 130° C. and wound onto a reel at a winder 75 .
[0084] Example 2 :
[0085] A bicomponent spunbond nonwoven fabric was produced by spinning a 50:50 ratio of polyethylene sheath (Aspun-6850-A from Dow chemical company) and polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration, such as Figure 6 , which is a scanning electron microscope photo showing a cross-section of a bicomponent trilobal fiber. The nonwoven fabric is spun on a forming belt having a Fig.16 The repeating pattern is as follows Figure 7 and Figure 8 As described, it moves at a line speed of about 25 meters / minute to form a fabric 10 having an average basis weight of 30 grams / square meter with a repeating pattern of diamond shapes, such as Figure 2 The fibers of the fabric are further bonded on the first surface 12 by heated compaction rollers 70, 72 (described below) at 130°C.
[0086] Table 1: Compression recovery
[0087]
[0088] As can be seen from Table 1, the fabric 10 of the present invention retains a significant amount of thickness after being compressed under relatively high pressure. For example, the samples of Example 1 and Example 2 retained greater than 70% of their initial average thickness after being tested at a pressure of 35 KPa by the "Compression Aging Test." The "Compression Aging Test" is a simulation of the following conditions that a nonwoven fabric will encounter: packaged in a high compression packaging diaper, and then maintained in this state during distribution to be distributed to a consumer, and then the package is ultimately opened by the consumer.
[0089] The present disclosure may utilize a melt spinning process. In melt spinning, there is no mass loss in the extrudate. Melt spinning is different from other spinning, such as wet spinning or dry spinning from a solution, in which the solvent is removed by volatilization or diffusion from the extrudate, resulting in mass loss.
[0090] Melt spinning can be carried out at about 150°C to about 280°, or in some embodiments, at about 190° to about 230°. The fiber spinning speed can be greater than 100 meters per minute, and can be about 1,000 meters per minute to about 10,000 meters per minute, and can be about 2,000 meters per minute to about 7,000 meters per minute, and can be about 2,500 meters per minute to about 5,000 meters per minute. The spinning speed can affect the brittleness of the spun fiber, and generally speaking, the higher the spinning speed, the less brittle the fiber. Continuous fibers can be produced by a spunbond process or a meltblown process.
[0091] The nonwoven fabric 10 of the present disclosure may include continuous multi-component polymer filaments, including a primary polymer component and a secondary polymer component. The filaments may be continuous bicomponent filaments, including a primary polymer component A and a secondary polymer component B. The bicomponent filaments have a cross section, a length, and a circumferential surface. Component A and component B may be arranged in substantially different zones across the cross section of the bicomponent filaments, and may extend continuously along the length of the bicomponent filaments. Secondary component B continuously forms at least a portion of the circumferential surface of the bicomponent filaments along the length of the bicomponent filaments. Polymer component A and polymer component B may be melt-spun into multi-component fibers on conventional melt spinning equipment. Equipment will be selected based on the desired multi-component configuration. Commercially available melt spinning equipment is purchased from Hills, Inc., located in Melbourne, Florida. The spinning temperature is in the range of about 180°C to about 230°C. The processing temperature is determined by the chemical nature, molecular weight, and concentration of each component. The bicomponent spunbond filaments may have an average diameter of about 6 microns to about 40 microns, and preferably about 12 microns to about 40 microns.
[0092] Component A and component B can be arranged as follows Figure 5A The parallel arrangement structure shown or Figure 5B The eccentric sheath / core arrangement shown in the embodiment of the present invention is used to obtain a filament exhibiting a natural helical crimp. Alternatively, component A and component B may be arranged as shown in the embodiment of the present invention. Figure 5C In addition, component A and component B can also be arranged as shown in FIG. Figure 6 The multi-lobed sheath-core arrangement shown. Other multi-component fibers can be produced by using the compositions and methods of the present disclosure. The bi-component fibers and multi-component fibers can be in a segmented, ribbon, island-in-the-sea configuration, or any combination thereof. The sheath can be continuous or discontinuous around the core. The weight ratio of the sheath to the core is about 5:95 to about 95:5. The fibers of the present disclosure can have different geometric shapes, including circular, elliptical, star-shaped, rectangular, and other various eccentricities.
[0093] Methods for extruding multicomponent polymer filaments into such arrangements are well known to those of ordinary skill in the art.
[0094] A wide variety of polymers are suitable for practicing the present disclosure, including polyolefins (such as polyethylene, polypropylene, and polybutylene), polyesters, polyamides, polyurethanes, elastomeric materials, etc. Non-limiting examples of polymer materials that can be spun into filaments include natural polymers such as starch, starch derivatives, cellulose and cellulose derivatives, hemicellulose, hemicellulose derivatives, chitin, chitosan, polyisoprene (cis and trans), peptides, polyhydroxyalkanoates; and synthetic polymers, including but not limited to thermoplastic polymers such as polyesters, nylons, polyolefins such as polypropylene, polyethylene, polyvinyl alcohol and polyvinyl alcohol derivatives, sodium polyacrylate (absorbent gelling material); and copolymers of polyolefins such as polyethylene-octene or polymers comprising a monomer blend of propylene and ethylene; and biodegradable or compostable thermoplastic polymers such as polylactic acid filaments, polyvinyl alcohol filaments, and polycaprolactone filaments. In one example, the thermoplastic polymer is selected from the group consisting of polypropylene, polyethylene, polyester, polylactic acid, polyhydroxyalkanoate, polyvinyl alcohol, polycaprolactone, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, polyurethane, and mixtures thereof. In another example, the thermoplastic polymer is selected from the group consisting of polypropylene, polyethylene, polyester, polylactic acid, polyhydroxyalkanoate, polyvinyl alcohol, polycaprolactone, and mixtures thereof. Alternatively, the polymer may include a polymer derived from a bio-based monomer such as bio-polyethylene or bio-polypropylene.
[0095] The primary component A and the secondary component B may be selected so that the resulting bicomponent filaments provide improved nonwoven bonding and substrate softness.Primary polymer component A has a melting temperature that is lower than the melting temperature of secondary polymer component B.
[0096] The primary polymer component A may comprise a random copolymer of polyethylene or propylene and ethylene. The secondary polymer component B may comprise a random copolymer of polypropylene or propylene and ethylene. Polyethylene comprises linear low density polyethylene and high density polyethylene. In addition, the secondary polymer component B may also comprise an additive to enhance the natural spiral curling of the long filaments, reduce the bonding temperature of the long filaments and enhance the abrasion resistance, strength and flexibility of the resulting fabric.
[0097] Inorganic fillers such as oxides of magnesium, aluminum, silicon, and titanium may be added as inexpensive fillers or processing aids. Other inorganic materials include hydrated magnesium silicate, titanium dioxide, calcium carbonate, clay, chalk, boron nitride, limestone, diatomaceous earth, mica, glass, quartz, and ceramics.
[0098] The filaments of the present invention also contain a slip additive in an amount sufficient to impart the desired tactile properties to the fiber. As used herein, "slip additive" or "slip agent" refers to an external lubricant. When melt blended with the resin, the slip agent gradually seeps out or migrates to the surface during cooling or after manufacture, thereby forming a uniform, invisibly thin coating, thereby producing a permanent lubricating effect. The slip agent is preferably a fast-acting full-bodied slip agent and can be a hydrocarbon with one or more functional groups selected from hydroxides, aryls and substituted aryls, halogens, alkoxyls, carboxylates, esters, carbon unsaturated substances, acrylates, oxygen, nitrogen, carboxyls, sulfates and phosphates.
[0099] During preparation or in post-processing or even in the two, nonwoven fabric of the present invention can be processed with hydrophilic fiber web or make it hydrophobic with surfactant or other reagent.This is the standard practice for the nonwoven fabric used for absorbent articles.For example, the nonwoven fabric used for top sheet can be processed with hydrophilic material or surfactant, so that it is permeable for body effluent such as urine.For other absorbent articles, top sheet can remain on its natural hydrophobic state or make it more hydrophobic by adding hydrophobic material or surfactant.
[0100] Suitable materials for making the multicomponent filaments of the fabrics of the present disclosure include PH-835 polypropylene available from LyondellBasell and Aspun-6850-A polyethylene available from Dow chemical company.
[0101] When polyethylene is component A (sheath) and polypropylene is component B (core), the bicomponent filaments may comprise polyethylene from about 5% to about 95% by weight and polypropylene from about 95% to about 5% by weight. The filaments may comprise polyethylene from about 40% to about 60% by weight and polypropylene from about 60% to about 40% by weight.
[0102] Go to Figure 7 , discloses a representative production line for making the fabric 10 of the present disclosure. The production line is arranged to produce a fabric of bicomponent continuous filaments, but it should be understood that the present disclosure includes nonwoven fabrics made with monocomponent filaments or multicomponent filaments having more than two components. The bicomponent filaments may be trilobal.
[0103] The production line includes a pair of extruders 32 and 34 driven by extruder drivers 31 and 33, respectively, for separately extruding a primary polymer component A and a secondary polymer component B. Polymer component A is fed into the corresponding extruder 32 from a first hopper 36, and polymer component B is fed into the corresponding extruder 34 from a second hopper 38. Polymer component A and polymer component B can be fed from the extruders 32 and 34 through corresponding polymer conduits 40 and 42 to filters 44 and 45 and melt pumps 46 and 47, which pump the polymers into a spinning assembly 48. Spinnerets for extruding bicomponent filaments are well known to those of ordinary skill in the art, and therefore are not described in detail herein.
[0104] Generally described, the spin pack 48 includes a housing including a plurality of plates stacked one on top of another with a pattern of openings arranged to create flow paths for individually directing polymer component A and polymer component B through a spinneret. The spin pack 48 has openings arranged in one or more rows. When the polymer is extruded through the spinneret, the spinneret openings form a curtain of filaments extending downwardly. For purposes of this disclosure, the spinneret may be arranged to form a plurality of plates stacked one on top of another with a pattern of openings arranged to create flow paths for individually directing polymer component A and polymer component B through a spinneret. Figure 5A , Figure 5B and Figure 5C Sheath / core or side-by-side bicomponent filaments, as well as non-circular fibers such as trilobal fibers, as shown Figure 6 In addition, the fibers may also be monocomponent comprising one polymer component such as polypropylene.
[0105] The production line also includes a quench blower 50 positioned adjacent to the filament curtain extending from the spinneret. The air from the quench blower 50 quenches the filaments extending from the spinneret. The quenching air may be directed from one side of the filament curtain or from both sides of the filament curtain.
[0106] Attenuator 52 is positioned below the spinneret and receives the quenched filaments. Fiber aspiration units or aspirators used as attenuators in the process of melt spinning polymers are well known. Suitable fiber aspiration units for use in the process of the present disclosure include linear fiber attenuators of the type shown in U.S. Patent 3,802,817 and spray guns of the type shown in U.S. Patent 3,692,618 and U.S. Patent 3,423,266, the disclosures of which are incorporated herein by reference.
[0107] Generally described, the attenuator 52 includes an elongated vertical channel through which the filaments are drawn by suction air, which enters from the side of the channel and flows downwardly through the channel. A shaped, annular and at least partially perforated forming belt 60 is positioned below the attenuator 52 and receives the continuous filaments from the outlet opening of the attenuator 52. The forming belt 60 is a belt and travels around a guide roller 62. A vacuum positioned below the forming belt 60 (where the filaments are deposited) draws the filaments against the forming surface. Although the forming belt 60 is in the Figure 8 It is shown as a belt in the figure, but it should be understood that the forming belt can also be in other forms, such as a rotating drum. The details of the forming belt of a specific shape are described below.
[0108] In the operation of the production line, hoppers 36 and 38 are filled with respective polymer components A and B. Polymer components A and B are molten and extruded by respective extruders 32 and 34 through polymer conduits 40 and 42 and a spinning assembly 48. Although the temperature of the molten polymer varies depending on the polymer used, when polyethylene and polypropylene are used as primary component A and secondary component B, respectively, the temperature of the polymer may be in the range of about 190° C. to about 240° C.
[0109] Along with the long filaments that are extruded extending below the spinneret, the air stream from the quenching blower 50 quenches the long filaments at least in part, and for some long filaments, induces the crystallization of the molten long filaments. The quenching air can flow at a speed of about 100 feet per minute to about 400 feet per minute at a temperature of about 0 ℃ to about 35 ℃ along the direction that is substantially perpendicular to the length of the long filaments. The long filaments can be fully quenched before being collected on the forming belt 60 so that the long filaments can be arranged by the forced air passing through the long filaments and the forming surface. Quenching the long filaments reduces the viscosity of the long filaments so that the long filaments are not too closely adhered to each other before being bonded, thereby being collected on the forming belt and forming the fiber web during being moved or arranged on the forming belt.
[0110] After quenching, the filaments are drawn by the air flow of the fiber aspiration unit into the vertical passage of the attenuator 52. The attenuator may be positioned 30 inches to 60 inches below the bottom of the spinneret.
[0111] The filaments may be deposited onto the shaped, traveling forming belt 60 through the outlet holes of the attenuator 52. As the filaments contact the forming surface of the forming belt 60, the vacuum draws air and the filaments against the forming belt 60 to form a nonwoven web of continuous filaments that assumes a shape corresponding to the shape of the forming surface. As described above, since the filaments are quenched, the filaments are not too sticky, and as the filaments are collected on the forming belt 60 and formed into the fabric 10, the vacuum can move the filaments or arrange the filaments on the forming belt 60.
[0112] The production line also includes one or more bonding devices, such as cylindrical compacting rollers 70 and 72, which form a roller gap through which the fabric can be compacted, that is, calendered, and they can also be heated to bond fibers. One or both of the compacting rollers 70, 72 can be heated to provide enhanced characteristics and beneficial effects to nonwoven fabric 10 by bonding some parts of the fabric. For example, it is believed that the heating sufficient to provide thermal bonding will improve the tensile properties of fabric 10. The compacting roller can be a pair of stainless steel rollers with an independent heating controller on a smooth surface. The compacting roller can be heated by an electrical component or a hot oil cycle. The gap between the compacting rollers can be controlled hydraulically to apply a desired pressure to the fabric as it passes through the compacting roller on the forming belt. In one embodiment, wherein the forming belt thickness is 1.4mm, and the spunbonded nonwoven has a basis weight of 30gsm, and the roller gap between the compacting rollers 70 and 72 can be about 1.4mm.
[0113] In one embodiment, the upper compacting roll 70 may be heated sufficiently to melt bond the fibers on the first surface 12 of the fabric 10, thereby imparting strength to the fabric so that it may be removed from the forming belt 60 without loss of integrity. Figure 8 and Fig. 9 As shown, for example, as rollers 70 and 72 rotate in the direction indicated by the arrows, belt 60 (with the spunbond fabric laid thereon) enters the nip formed by rollers 70 and 72. The heated roller 70 can heat the portion of the nonwoven fabric 10 that is pressed against it by the raised resin elements of belt 60 (i.e., in region 21), thereby producing bonded fibers 80 on at least the first surface 12 of the fabric 10. As can be understood from the description herein, the bonded areas so formed can present a pattern of raised elements of the forming belt 60. For example, the bonded areas so formed can be a substantially continuous network or a substantially semi-continuous network on the first surface 12 of region 21, which forms a bond with the first surface 12 of the region 21. Figure 1 and Fig.11 By adjusting the temperature and dwell time, bonding can be primarily confined to the fibers closest to the first surface 12, or thermal bonding can reach the second surface 14, such as Fig.11 (This figure also shows point bonds 90 described in more detail below) and Figures 45 to 49 The bonds may also be a discontinuous network, for example, point bonds 90 described below.
[0114] The raised elements of the forming belt 60 may be selected to establish various network features of the bonding areas of the forming belt and the nonwoven substrate 11 or nonwoven fabric 10. The network corresponds to the resin that constitutes the raised elements of the forming belt 60 and may include options of being substantially continuous, substantially semi-continuous, discontinuous, or a combination thereof. These networks may describe the raised elements of the forming belt 60 as it relates to their appearance or composition within the XY plane of the three-dimensional features of the forming belt 60 or the nonwoven substrate 11 or nonwoven fabric 10 comprising the present invention.
[0115] A "substantially continuous" network is a region within which any two points can be connected by an unbroken line, the entire line length of which extends completely within the region. That is, the substantially continuous network has substantial "continuity" along all directions parallel to the first plane and terminates only at the edges of the region. In conjunction with "continuous", the term "substantially" is intended to indicate that while absolute continuity can be achieved, minor deviations from absolute continuity are tolerable as long as these deviations do not significantly affect the designed and intended performance of the fiber structure (or molded component).
[0116] A "substantially semi-continuous" network refers to a region having "continuity" along all but at least one direction parallel to a first plane, and in which no two points can be connected by an unbroken line whose entire line length extends entirely within the region. A semi-continuous framework may have continuity in only one direction parallel to the first plane. Similar to the continuous region described above, although absolute continuity in all but at least one direction is preferred, slight deviations from this continuity are tolerable as long as they do not significantly affect the performance of the fiber structure.
[0117] A "discontinuous" network refers to discrete and separated regions that are discontinuous in all directions parallel to the first plane.
[0118] After compaction, the fabric may leave the forming belt 60 and may be calendered through the nip formed by calendering rollers 71, 73, after which the fabric may be wound onto a reel. Fig.10As shown in the schematic cross-section of , the calender rolls may be stainless steel rolls having an engraved pattern roll 84 and a smooth roll 86. The engraved roll may have a raised portion 88 that may provide additional compaction and bonding to the fabric 10. The raised portion 88 may be a regular pattern of relatively small, spaced "pins" that form a pattern of relatively small point bonds 90 in the nip between the calender rolls 71 and 73. The percentage of point bonds in the nonwoven fabric 10 may be 3% to 30% or 7% to 20%. The engraved pattern may be a plurality of closely spaced, regular, generally cylindrical, generally flat-topped pin shapes, wherein the pin height is in the range of 0.5 mm to 5 mm and preferably 1 mm to 3 mm. The pins of the bonding calender roll may form closely spaced, regular point bonds 90 in the nonwoven fabric 10, such as Fig.11 Further bonding can be achieved by, for example, heat-through-air bonding.
[0119] As follows about Fig.56 As described, through-air thermal bonding may be another method of producing a higher loft nonwoven structure that may be applicable to this application. Through-air thermal bonding involves applying hot air to the surface of the nonwoven fabric. The hot air flows through holes in a plenum located just above the nonwoven fabric. However, the air is not pushed through the nonwoven fabric as in a normal hot air oven. Negative pressure or suction pulls the air through the open conveyor baffles, which support the nonwoven fabric as it passes through the oven. Pulling air through the nonwoven fabric allows for a more rapid and uniform transfer of heat and minimizes deformation of the fabric. In addition to conventional through-air bonding units, it is conceivable that the bonding unit is placed on top of the 3D belt while setting a vacuum below the belt to simulate the through-air bonding process for this particular application.
[0120] The binder for through-air thermal bonding includes crystalline binder fiber, bicomponent binder fiber and powder. When using crystalline binder fiber or powder, the binder is completely melted and forms droplets in the cross section of the whole nonwoven fabric. When cooling, bonding occurs at these points. With regard to the skin / core binder fiber, the skin is a binder, and the core is a carrier fiber. In one embodiment, the nonwoven fabric comprises skin / core binder fiber, the skin comprises polyethylene, and the core comprises polypropylene. For such nonwoven fabrics, since the through-air bonding time will depend on the basis weight, the required strength level and the operating speed, the through-air thermal bonding air temperature can be in the range of 110°C to 150°C, and the residence time can be in the range of 0.5 seconds to 10 seconds, 5 seconds to 30 seconds or 30 seconds to 60 seconds. The products manufactured using the through-air oven tend to be large in volume, open, soft, firm, ductile, breathable and absorbent.
[0121] As used herein, point bonding is a method for thermally bonding nonwoven fabrics, webs or substrates. The method involves passing the web through the roll gap between two rollers, which are composed of a heated convex metal roll with a pattern or engraving and a smooth or patterned metal roll. The convex patterned roll may have a plurality of protrusions, generally cylindrical pins, which produce circular point bonding. The smooth roll may be heated or not heated according to the application. In a nonwoven production line, a nonwoven fabric that may be a non-bonded web is fed into the calendering roll gap, and the fiber temperature is raised to the point where the fiber is at the tip of the engraved point and against the point where the smooth roll is thermally fused to each other. The heating time is generally in the millisecond level. Fabric properties depend on process settings, such as roll temperature, web line speed and roll gap pressure, all of which can be determined by technicians according to the desired point bonding degree. Other types of point bonding commonly referred to as thermal calendering bonding can be composed of different geometric shapes (except circular shapes) for bonding, such as elliptical, linear, circular, etc. In the exemplary embodiments disclosed herein, point bonding produces a pattern of point bonds that are 0.5 mm diameter circles with a 10% total bond area. Other embodiments include bonding shapes where the raised pins have a longest dimension of about 0.1 mm to 2.0 mm over the entire bonding surface of the pins, and the total bond area is in the range of 5% to 30%.
[0122] like Fig.11 As shown, in one embodiment, the heated compaction roll 70 can form a bonding pattern that can be a substantially continuous network bonding pattern 80 (e.g., interconnected heart-shaped bonds) on the first surface 12 of the nonwoven fabric 10 (not shown in FIG. Fig.11In the embodiment of the present invention, the first surface 12 of the nonwoven fabric 10 is relatively flat (relative to the second surface 14), and has a relatively large amount of bonding due to the heated compacting roller, thereby forming a bonding portion 80 at the region of the fabric pressed by the raised element of the forming belt 60. This bonding gives the nonwoven fabric 10 structural integrity, but it may be relatively hard or rough for the user's skin. Therefore, the first surface 12 of the nonwoven fabric 10 can be oriented to face the inside of the product in a diaper or sanitary napkin, that is, away from the wearer's body. Similarly, the second surface 14 can face the body in use and contact the body. The relatively small point bonds 90 are less likely to be visually or tactilely perceived by the user, and the relatively soft three-dimensional features remain visually free of linting and pilling while feeling soft to the body during use. Further bonds may be used in lieu of or in addition to the above bonds.
[0123] The forming belt 60 may be prepared according to the methods and processes described in U.S. Pat. No. 6,610,173 issued to Lindsay et al. on August 26, 2003, or U.S. Pat. No. 5,514,523 issued to Trokhan et al. on May 7, 1996, or U.S. Pat. No. 6,398,910 issued to Burazin et al. on June 4, 2002, or U.S. Publication No. 2013 / 0199741 issued in the name of Stage et al. on August 8, 2013, each having the improved features and patterns disclosed herein for making spunbond nonwoven webs. The Lindsay, Trokhan, Burazin, and Stage disclosures describe the following belts, which represent papermaking belts made with a cured resin on a woven reinforcement member, which belts have improvements and can be used in the present disclosure as described herein.
[0124] An example of a forming belt 60 of the type that may be used in the present disclosure and that may be prepared in accordance with the disclosure of U.S. Patent No. 5,514,523 is shown at Fig.12 As taught herein, the reinforcing member 94 (such as a woven tape of filaments 96) is fully coated with a liquid photopolymer resin to a preselected thickness. Incorporating a desired raised element pattern repeating element (e.g., Fig.14) is juxtaposed over the liquid photosensitive resin. The resin is then exposed to light of an appropriate wavelength, such as UV light (for UV curable resins), passing through the film. This exposure to light results in curing of the resin in the exposed areas (i.e., the white or non-printed portions of the mask). The uncured resin (resin under the opaque portions of the mask) is removed from the system, leaving behind the cured resin that forms a pattern, such as that formed by the Fig.12 The cured resin element is shown as 92. Other patterns may also be formed, as described herein.
[0125] Fig.12 It is shown that it can be used to prepare Figure 1 A portion of a forming belt 60 of a nonwoven fabric 10 is shown. As shown, the forming belt 60 may include a cured resin element 92 on a woven reinforcing member 94. The reinforcing member 94 may be made of woven filaments 96, as is known in the papermaking belt art, including resin-coated papermaking belts. The cured resin element may have Fig.12 The general structure shown in FIG. 1 and by using Fig.14 The mask 97 of the size shown is prepared. Fig.13 As shown in the schematic cross-section in FIG, the cured resin element 92 flows around and is cured to "lock" to the reinforcing member 94, and may have a width DW at the distal end of about 0.020 inches to about 0.060 inches, or about 0.025 inches to about 0.030 inches, and may have an overall height above the reinforcing member 94 (referred to as overload OB) between about 0.015 inches and about 0.060 inches, or between about 0.020 inches and about 0.050 inches, or between about 0.025 inches and about 0.045 inches, or between about 0.030 inches and about 0.040 inches, or between about 0.030 inches and about 0.035 inches. Fig.14 A portion of mask 97 is shown, showing the Figure 1 The design and representative dimensions of one repeating unit of the repeating heart-shaped design in the nonwoven fabric 10 are shown. The white portion 98 is transparent to UV light and, in the process of making the tape, as described in U.S. Pat. No. 5,514,523, allows the UV light to cure the underlying resin layer, which is cured to form raised elements 92 on the reinforcing member 94. After the uncured resin is washed away, the ends of the tape length are seamed to produce a tape having a shape such as Fig.12 The curing resin is designed to form a belt 60, the length of which may depend on the design of the equipment, such as Figure 7 shown.
[0126] In a similar manner, Fig.15 A portion of mask 97 is shown, showing the Figure 2The white portion 98 is transparent to UV light and allows the UV light to cure the underlying resin layer, which is cured to the reinforcing member 94, during the process of making the tape. After the uncured resin is washed away, a tape having a shape such as a woven fabric 10 is produced by seaming the ends of the tape length. Fig.16 The curing resin is designed to form a belt 60, the length of which may depend on the design of the equipment, such as Figure 7 shown.
[0127] Additionally, in another non-limiting example, Fig.17 A portion of a mask is shown, showing the Fig.18 The white portion 98 is transparent to UV light and allows the UV light to cure the underlying resin layer, which is cured to the reinforcing member 94, during the process of making the tape. After the uncured resin is rinsed off, the ends of the length of fabric 10 are sewn together to create a tape having a shape similar to that of a repeating unit of the repeating design in the nonwoven fabric 10 shown. The white portion 98 is transparent to UV light and allows the UV light to cure the underlying resin layer, which is cured to the reinforcing member 94, during the process of making the tape. Fig.18 A forming belt 60 of a cured resin design is shown.
[0128] Another example of a portion of a forming belt 60 of the type that may be used in the present disclosure is shown in Fig.19 middle. Fig.19 The portion of the forming belt 60 shown is a discrete belt pattern 61, which can have a length L and a width W corresponding to the length L and the width W of the total area OA of the nonwoven fabric 10. That is, the forming belt 60 can have a discrete belt pattern 61 (as described below with reference to Fig. 22 ), each of which has a discrete patterned total area DPOA corresponding to the total area OA of the nonwoven fabric 10. Fig. 20 represents a portion of the mask, showing Fig.21 The white portion 98 is transparent to UV light and allows the UV light to cure the underlying resin layer, which is cured to the reinforcing member 94, during the process of making the tape. After the uncured resin is washed away, the tape is produced by seaming the ends of the length of tape. Fig.19 A forming belt 60 of a cured resin design is shown.
[0129] Fig.19 The portion of the forming belt shown illustrates another beneficial effect of the present disclosure. Fig.19 The portion of the forming belt 60 shown can be prepared Fig.21 The fabric 10 is shown. Fig.21 The nonwoven fabric 10 shown may have a width W dimension and a length L dimension and a total area OA, making it suitable for use as a top sheet in, for example, a disposable diaper. Fig.19The nonwoven fabric 10 formed on the illustrated forming belt 60 is different from Figures 1 to 3 The nonwoven fabric shown in the figure is not a regular repeating pattern over the entire total area because the pattern of the three-dimensional features formed by the discrete resin elements 92 on the forming belt 60. On the contrary, the pattern of the three-dimensional raised elements in the discrete band pattern total area DPOA can be described as an irregular pattern comprising different parts called zones. The difference between the zones can be visual, that is, visually discernible differences, or in the nonwoven fabric 10, the difference can produce average strength characteristics such as differences in basis weight or density or differences in the combination of visual characteristics and strength characteristics. If an observer can visually discern the pattern differences between a zone such as the first zone 112 and the second zone 122 under ordinary indoor lighting conditions (e.g., 20 / 20 vision, sufficient illumination for reading), there is a visually discernible difference.
[0130] The nonwoven fabric 10 may also have visually discernible areas corresponding to areas of the forming belt. Fig.21 As shown, for example, the fabric 10 may have at least two, three, or four visually discernible zones. A first zone 110 having a first pattern of three-dimensional features and a first average strength characteristic may have a first area that is approximately centrally located within the total area OA. A second zone 120 having a second pattern of three-dimensional features and a second average strength characteristic may have a second area that is approximately distributed around, and in one embodiment completely surrounds the first zone 110 within the total area OA. A third zone 130 having a third pattern of three-dimensional features and a third average strength characteristic may have a third area that is approximately distributed around, and in one embodiment completely surrounds the second zone 120 within the total area OA. A fourth zone 140 having a fourth three-dimensional feature and a fourth average strength characteristic may have a fourth area that is located in any position within the total area OA, such as at the front region of the top sheet, such as Fig.21 The heart-shaped design shown. Generally speaking, there can be n regions, where n is a positive integer. Each of the n regions can have an nth pattern of three-dimensional features and an nth area and an nth average intensity characteristic.
[0131] like Fig.21 As shown, the visually discernible area may include visually discernible three-dimensional features. These different three-dimensional features may be defined by a relatively high density (relative to the interior of the three-dimensional features) area, which may be in the form of a closed figure, such as Figure 1 and Figure 3 The heart shape in the Figure 2 and Figure 3In general, as discussed more fully below, including in the context of microregions, a three-dimensional feature structure may be defined by a first region and a second region, wherein the first region and the second region are visually distinct, and there is a common intensity characteristic associated with each of the first region and the second region, and there is a difference in the value of the common intensity characteristic of the first region and the second region. In one embodiment, a three-dimensional feature structure may be defined by a first region and a second region, wherein the first region is at a higher height (dimension measured in the Z direction) relative to the plane of the first surface than the second region. In another embodiment, a three-dimensional feature structure may be defined by a first region and a second region, wherein the first region is at a higher base than the second region.
[0132] As can be appreciated, instead of having a constant repeating pattern that is uniform across the entire forming belt, the forming belt 60 of the present disclosure allows for the creation of a nonwoven material that can have a repeating irregular discrete band pattern 61, each of which is similar to Fig.19 The discrete band patterns 61 are shown in the drawings. The discrete band patterns 61 can each be used to form a nonwoven fabric 10 having a total area OA suitable for, for example, disposable absorbent articles such as diapers or sanitary napkins. The nonwoven fabric 10 can be produced sequentially, that is, produced online, and optionally produced in parallel lanes in a sequential manner, each lane being a sequential line of the nonwoven fabric 10. The sequential lines of the nonwoven fabric 10 can be produced in the machine direction along an axis parallel to the machine direction. The nonwoven material can then be cut or otherwise cut to size to produce a nonwoven fabric 10 used as a top sheet in a disposable absorbent article such as a diaper or sanitary napkin.
[0133] In one embodiment, the patterns within each discrete patterned total area DPOA may be the same or different. That is, sequentially spaced discrete patterned strips may be substantially the same, or they may differ in visual appearance and / or in strength properties (resulting in the nonwoven substrate produced thereon). For example, Fig. 22As shown schematically, the pattern of the three-dimensional raised elements in the first forming area 112 of the discrete band pattern 61A may be different from the pattern of the three-dimensional raised elements in the first forming area 112 of the discrete band pattern 61B. The forming band 60 therefore provides flexibility in the process of producing the nonwoven web 10 suitable for consumer goods, and the consumer goods include disposable absorbent articles. For example, in a package of diapers, the top sheets of at least two diapers may be different because they are sequentially produced in the spunbond process as described herein, with sequential discrete band patterns with different patterns of zones. In one embodiment, the top sheet or back sheet nonwoven fabric pattern for a diaper of one size may be different from the top sheet or back sheet nonwoven fabric of a diaper of another size, thereby giving the caregiver visual cues about the diaper size. Similarly, fabric 10 can be used for top sheets in sanitary napkins, wherein the visual pattern of the three-dimensional feature structure represents the absorbency of the sanitary napkin. In any case, various patterns of fabric 10 can be produced on a single band by preparing different discrete band patterns as required.
[0134] refer to Fig. 22 , the forming belt has an axis A parallel to the longitudinal direction, which is the processing direction. The forming belt 60 may have a plurality of discrete belt patterns 61 that are arranged in at least one sequential relationship relative to the longitudinal direction. Each discrete belt pattern 61 may have a discrete belt pattern total area DPOA, which is defined in a rectangular pattern by the length L and width W as shown for the discrete belt pattern 61A. Each discrete belt pattern within its total area DPOA may have a first forming area 112 and a second forming area 122, the first forming area having a first pattern of three-dimensional protruding elements extending outward from the plane of the first surface, and the second forming area having a second three-dimensional protruding element extending outward from the plane of the first surface. The first forming area may have a first permeability value, and the second forming area may have a second permeability value, and the first permeability value may be different from the second permeability value. The patterns within each sequentially arranged discrete belt pattern total area DPOA may be the same or different.
[0135] By way of example, and with reference to Fig.19 The discrete belt pattern 61 and Fig.21 The nonwoven fabric 10 shown, the following properties are determined. The first region 110 of the nonwoven fabric 10 can have an average basis weight of about 5 gsm to about 30 gsm; the second region 120 can have an average basis weight of about 50 gsm to about 70 gsm; and the third region 130 can have an average basis weight of about 25 gsm to about 60 gsm. The difference in basis weight from one region to another can be attributed to the difference in air permeability of the forming belt 60. In the process used to prepare Fig. 20In the illustrated embodiment of the nonwoven fabric 10, where the basis weights of regions 110, 120, and 130 are 15 gsm, 53 gsm, and 25 gsm, respectively, the air permeabilities of corresponding regions 112, 122, and 132 of the forming belt 60 are 379 cfm, 805 cfm, and 625 cfm, respectively. Thus, by varying the air permeability of each region in the forming belt 10, the strength characteristics of the average basis weight and average density in each region can be facilitated over the total area of the fabric 10.
[0136] If you can Fig. 22 The description of the forming belt 60 is to be understood and referred to Fig.23 In one embodiment, the nonwoven substrate 11 prepared on the belt 60 can be described as a nonwoven substrate 11 having multiple parts, which are described herein as fabrics 10 that are arranged in at least one sequential relationship relative to the longitudinal direction, i.e., the processing direction, when prepared on the forming belt 60. Fig.23 is a schematic diagram of a spunbond nonwoven substrate 11, showing sequentially arranged fabrics 10, each fabric 10 having different patterns in various zones. Each fabric 10 may have a total area OA, which is defined by a length L and a width W in a rectangular-shaped pattern. Each sequentially arranged fabric 10 may have at least a first zone 110 within its total area OA, the first zone having a first pattern of three-dimensional features and a first average strength characteristic, and a first area within the total area OA; a second zone 120, the second zone having a second pattern of three-dimensional features and a second average strength characteristic, and having a second area within the total area OA. Optionally, there may be more zones, such as a third zone 130, the third zone having a third pattern of three-dimensional features and a third average strength characteristic, and having a third area within the total area OA. As Fig.23 As shown in the exemplary schematic diagram of , the first pattern 110A of fabric 10A may be different from the first pattern 110B of fabric 10B, and may be different from the first pattern 110C of fabric 10C. The same situation may also be established for the second areas 120A, 120B and 120C.
[0137] Generally speaking, the sequentially ordered nonwoven fabrics 10 of the nonwoven material 11 produced on the forming belt 60 may vary in their respective total area, strength characteristics, and visual appearance. A common strength characteristic is more than one zone (as opposed to a zoned pattern, such as Fig.21 The partition pattern shown) or area (for three-dimensional feature structures, such as regular repeating patterns, such as Figure 1The strength characteristics of the nonwoven fabric 10 may be average values and may include, but are not limited to, density, bulk density, basis weight, thickness, and opacity. For example, if density is a common strength characteristic of two different zones or regions, the density value in one zone or region may be different from the density value in another zone or region. Zones (such as, for example, a first zone and a second zone) may be identifiable areas that can be distinguished from each other visually and by different strength characteristics averaged within the zones.
[0138] Once produced, the individual nonwoven fabrics 10 can be cut to size and used for their intended use, such as for use as a top sheet in a disposable absorbent article. For example, a disposable diaper 1006 in a flat orientation is shown in FIG. Fig.24 A fabric 10 is cut to the appropriate total area and attached to the diaper 1006 by methods known in the art. The fabric 10 can be cut before being assembled into the diaper 1006, or during the diaper manufacturing process, the nonwoven substrate 11 can be placed together with other diaper components in the form of a fiber web and cut to size after assembly.
[0139] If you can refer to Fig.24 To understand, in one embodiment, the nonwoven substrate 11 made on the belt 60 can be described as a nonwoven fabric 11 having multiple parts, which are described herein as fabrics 10 that are arranged in at least one sequential relationship relative to the longitudinal direction, i.e., the processing direction, when prepared on the forming belt 60, and in at least one parallel relationship when prepared on the forming belt 60, i.e., in at least one parallel relationship in the transverse direction. Fig.24 is a schematic diagram of a spunbond nonwoven substrate 11 showing sequentially arranged fabrics 10 in adjacent machine direction lanes 13, with adjacent lanes having each fabric 10 next to them. Fig.24In the embodiment of the present invention, the fabric 10 is marked as 10D, 10E and 10F. Each fabric 10 may have a total area OA, which is limited in a rectangular pattern by a length L and a width W. Each fabric 10 arranged sequentially may have at least a first district 110 in its total area OA, the first district having a first pattern of a three-dimensional feature structure and a first average strength characteristic and a first area located in the total area OA; a second district 120, the second district having a second pattern of a three-dimensional feature structure and a second average strength characteristic, having a second area located in the total area OA. Optionally, more districts may be present, such as a third district 130, the third district having a third pattern of a three-dimensional feature structure and a third average strength characteristic, and having a third area in the total area OA. Each fabric 10 in the parallel lanes may be substantially the same, or they may be different in size, visual appearance, and / or strength characteristics. Once produced, the nonwoven substrate 11 may be wound onto a reel so as to be cut into the lanes to be processed into consumer products, or may be cut and subsequently wound onto a reel.
[0140] The nonwoven fabric 10 of Example 1 was compared to a fabric 10 having a similar pattern to that of Example 1 by comparing the basis weight difference between the fabric 10 made with a regularly repeating uniform pattern and the fabric 10 made with a non-uniform zoned pattern using representative samples. Fig.21 The fabrics having the pattern shown in FIG. 1 and FIG. 2 (and referred to as Example 3) were compared. Example 3 is a bicomponent spunbond nonwoven web produced on the apparatus disclosed herein by spinning a 50:50 ratio of polyethylene sheath (Aspun-6850-A from Dowchemical company) and polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration. The spunbond bicomponent trilobal fibers were laid down on a forming belt 60 which was moved at a line speed of about 25 m / min to a position on a belt having a pattern shown in FIG. Fig.19 The second substrate is formed under the same conditions, but has at least one cross-section that is formed in the following manner: Fig.16 The forming belt shown has a regularly repeating uniform pattern on it from which the basis weight was determined. The fiber spinning conditions, throughput, forming belt line speed, and compacting roll bonding temperature were identical for both substrates.
[0141] Example 3
[0142] A bicomponent spunbond nonwoven fabric produced by spinning a 50:50 ratio of polyethylene sheath (Aspun-6850-A from Dow chemical company) and polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration to an average basis weight of 30 g / m2. A nonwoven fabric is as described herein Figure 7 and Figure 8 The produced surface is moved at a forming belt line speed of about 25 m / min to form a Fig. 20 The fibers of the fabric are further bonded on the first surface 12 by heated compaction rollers 70 , 72 at 130° C. and the fabric is wound onto a reel at a winder 75 .
[0143] Example 4
[0144] A bicomponent spunbond nonwoven fabric produced by spinning a 50:50 ratio of polyethylene sheath (Aspun-6850-A from Dow chemical company) and polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration to an average basis weight of 30 g / m2. A nonwoven fabric is as described herein Figure 7 and Figure 8 The produced surface is moved at a forming belt line speed of about 25 m / min to form a Figure 2 The fabric is shown with a repeating (non-zonal) pattern. The fibers of the fabric are further bonded on the first surface 12 by heated compaction rollers 70 , 72 at 130° C. and wound onto a reel at winder 75 .
[0145] Table 2 below shows the average local basis weight measured according to the "Local Basis Weight" test method herein and averaged using 10 samples. The samples used for the measurements were taken from Fig.25A and Fig.25B The fabric shown, with the dark rectangle showing the 3cm 2 As can be seen, these fabrics are numbered A to E in the cross direction (CD). The measurements show not only the significant basis weight differences between the zones of the zoned fabrics, but also Fig.26 CD distribution shown.
[0146] Table 2: Average basis weight distribution in nonwoven fabric 10 measured in grams per square meter (gsm)
[0147]
[0148] As can be seen in Table 2, fabrics 10 made on a forming belt 60 having zones of varying air permeability exhibit substantial variation in fiber layup and, therefore, basis weight within the CD of the nonwoven fabric 10, suggesting the ability of the fibers to travel with the air into zones of high permeability. The non-zonal, regular repeating pattern fabric 10 exhibited approximately the same basis weight within the CD of the fabric.
[0149] In addition to the differences in air permeability of various zones of the forming belt 60, the structure of the forming belt 60 may also affect other strength characteristics of the zones in the fabric 10, such as average thickness, average softness, average resistance to compression, and fluid absorption characteristics.
[0150] Another aspect of the invention relates to a spunbond commercial line where multiple beams are used for improved laydown opacity and uniformity of the fabric. In some cases, the equipment may include a triple spunbond beam (referred to in the art as "SSS") and may be combined with meltblowing (M), for example, in equipment referred to as a "SSMMS" spunbond line.
[0151] By calendering nonwoven fabric 10 to have point bonding 90, this can reduce fuzzing. Fuzzing refers to the trend that fibers become loose and are removed from fabric 10. Looseness and removal can be attributed to the frictional engagement with manufacturing equipment during the production of disposable absorbent articles, or the interaction of another surface such as human skin and fabric 10. In some applications, such as the top sheet used in disposable absorbent articles, fuzzing is a negative consumer phenomenon. But fiber bonding in a fixed position can also be negative for consumption, because it can produce roughness on the surface of otherwise soft nonwoven substrate. As expected, we have found that nonwoven fabric substrate and nonwoven fabric of the present disclosure can ensure the increase of bonding (and the reduction of fuzzing thus occurring) with minimal softness loss. Bonding can be achieved by relatively closely spaced point bonding 90, wherein the spacing depends on the desired fuzzing reduction degree. Bonding can also be achieved by known methods for chemical bonding or thermal bonding nonwoven fibers, such as thermal bonding, ultrasonic bonding, pressure bonding, latex adhesive bonding and the combination of such methods. The fuzz reduction achieved by bonding is shown in relation to embodiments 5 and 6 below.
[0152] Example 5
[0153] A bicomponent spunbond nonwoven fabric is produced by: Figure 7 and Figure 8The forming belt is spun with a polyethylene sheath (Aspun-6850-A from Dow Chemical Company) and a polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration in a 50:50 ratio to an average basis weight of about 30 g / m2 and is moved at a line speed of about 25 m / min to form a forming belt having a fiber structure as shown in FIG. Fig.36 The fibers of the fabric are further bonded on the first surface 12 by compaction rollers 70 , 72 , wherein compaction roller 70 is heated to 130° C. to form substantially continuous bonds 80 .
[0154] Example 6
[0155] A bicomponent spunbond nonwoven fabric is produced by: Figure 7 and Figure 8 The forming belt is spun with a polyethylene sheath (Aspun-6850-A from Dow Chemical Company) and a polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration in a 50:50 ratio to an average basis weight of about 30 g / m2 and is moved at a line speed of about 25 m / min to form a forming belt having about Fig.37 The fibers of the fabric are further bonded on the first surface 12 by compacting rollers 70, 72, wherein compacting roller 70 is heated to 130°C to form substantially continuous bonds 80. The fibers of the fabric are further calendared and bonded at calendaring rollers 71, 73, wherein roller 73 is an engraved roller having raised portions 88 in the form of spikes with a spike height of 1.25 mm and an open gap of 0.62 mm in a 10% point bond pattern. Roller 73 is heated to 135°C to form point bonds 90 on the second side 14 of the fabric 10, as shown. Fig.11 shown.
[0156] The fabrics 10 of Examples 5 and 6 differ only in the absence or presence of point bonds 90. The second side 14 of the fabric 10 was subjected to a fuzz test according to the "Fuzz Content Test" to determine the effectiveness of the point bonds in securing the fibers to the fabric surface. The results of the fuzz test for Examples 5 and 6 are shown in Table 3.
[0157] Table 3: MD villus results
[0158]
[0159] As shown above, the point bonds 90 result in a significant reduction in the MD fuzz value. Despite the bonding process, it still maintains its softness, absorbency, and aesthetic benefits, and now also has the desired fuzz resistance when used by consumers.
[0160] Absorbent articles of the present disclosure are usually placed in packages for transportation, storage and sale. Packages may include polymer films and / or other materials. Graphics and / or markings relevant to the characteristics of the absorbent articles may be formed on, printed on, positioned on, and / or placed on the outer portion of the package. Each package may include a plurality of absorbent articles. The absorbent articles may be stacked under compression to reduce the size of the package while still providing a sufficient amount of absorbent articles for each package. By packaging the absorbent articles under compression, caregivers can easily handle and store the packages while also providing savings in distribution for the manufacturer due to the size of the packages. Fig. 27 An exemplary package 1000 is shown that includes a plurality of absorbent articles 1004. The package 1000 defines an interior space 1002 in which the plurality of absorbent articles 1004 are located. The plurality of absorbent articles 1004 are arranged in one or more stacks 1006.
[0161] According to the In-Bag Stack Height Test described herein, the absorbent article packages of the present disclosure may have an In-Bag Stack Height of less than about 100 mm, less than about 95 mm, less than about 90 mm, less than about 85 mm, less than about 85 mm, but greater than about 75 mm, less than about 80 mm, less than about 78 mm, less than about 76 mm, or less than about 74 mm, specifically reciting all 0.1 mm increments within the specified ranges and all ranges formed therein or thereby. Alternatively, according to the In-Bag Stack Height Test described herein, the absorbent article packages of the present disclosure may have an In-Bag Stack Height of about 70 mm to about 100 mm, about 70 mm to about 95 mm, about 72 mm to about 85 mm, about 72 mm to about 80 mm, or about 74 mm to about 78 mm, specifically reciting all 0.1 mm increments within the specified ranges and all ranges formed therein or thereby.
[0162] General description of absorbent articles
[0163] The three-dimensional nonwoven fabric 10 of the present disclosure can be used as a component of absorbent articles such as diapers, child care articles such as training pants, feminine care articles such as sanitary napkins, and adult care articles such as incontinence products, pads, and pants. An exemplary absorbent article in the form of a diaper 220 is shown in FIG. Figures 28 to 30 middle. Fig.28 2 is a plan view of an exemplary diaper 220 in a flattened state with portions of the structure cut away to more clearly illustrate the construction of the diaper 220. Fig.28The wearer-facing surface of the diaper 220 faces the viewer. The diaper 220 is shown for illustration purposes only, as the three-dimensional nonwoven material of the present disclosure may be used as one or more components of an absorbent article, such as a top sheet, an acquisition layer, a top sheet and an acquisition layer, or a top sheet and an acquisition and / or distribution system ("ADS"). In any case, the three-dimensional nonwoven material of the present disclosure may be liquid permeable.
[0164] The absorbent article 220 may include a liquid permeable material or topsheet 224, a liquid impermeable material or backsheet 225, and an absorbent core 228 positioned at least partially intermediate the topsheet 224 and the backsheet 225, and barrier leg cuffs 234. The absorbent article may also include an ADS 250, which in the example shown includes a distribution layer 254 and an acquisition layer 252, which will be discussed further below. The absorbent article 220 may also include an elasticized gasketing cuff 232, which includes an elastic component 233 that is typically joined to the chassis of the absorbent article via the topsheet and / or the backsheet and is substantially in-plane with the chassis of the diaper.
[0165] Fig.28 and Fig.31 Typical taped diaper components are also shown, such as a fastening system including a tab 242 attached toward the rear edge of the article and cooperating with a landing zone 244 on the front of the absorbent article. The absorbent article may also include other typical elements not shown, such as, for example, a rear elastic waist feature, a front elastic waist feature, one or more lateral barrier cuffs, and / or a lotion application.
[0166] The absorbent article 220 includes a front waist edge 210, a back waist edge 212 longitudinally opposite the front waist edge 210, a first side edge 203, and a second side edge 204 laterally opposite the first side edge 203. The front waist edge 210 is the edge of the article that is intended to be placed toward the front of the user when worn, and the back waist edge 212 is the opposite edge. The absorbent article 220 may have a longitudinal axis 280 that extends from the lateral midpoint of the front waist edge 210 of the article to the lateral midpoint of the back waist edge 212 and divides the article into two halves that are substantially symmetrical relative to the longitudinal axis 280, wherein the article is laid flat, unfolded, and viewed from above, as shown. Fig.28As shown. The absorbent article 220 may also have a lateral axis 290 extending from the longitudinal midpoint of the first side edge 203 to the longitudinal midpoint of the second side edge 204. The length L of the article may be measured along the longitudinal axis 280 from the front waist edge 210 to the back waist edge 212. The width W of the absorbent article may be measured along the lateral axis 290 from the first side edge 203 to the second side edge 204. The absorbent article may include a crotch point C, which is defined herein as a point disposed on the longitudinal axis at a distance of two-fifths (2 / 5) L from the front edge 210 of the article 220. The article may include a front waist region 205, a back waist region 206, and a crotch region 207. The front waist region 205, the back waist region 206, and the crotch region 207 may each define 1 / 3 of the longitudinal length L of the absorbent article.
[0167] The topsheet 224, backsheet 225, absorbent core 228 and other article components may be assembled in a variety of configurations, particularly by, for example, gluing or heat embossing.
[0168] The absorbent core 228 may include an absorbent material and a core wrap encapsulating a superabsorbent polymer, the absorbent material containing at least 80% by weight, at least 85% by weight, at least 90% by weight, at least 95% by weight, or at least 99% by weight of superabsorbent polymer. The core wrap may typically include two materials, substrates, or nonwoven materials 216 and 216' for the top and bottom sides of the core. These types of cores are referred to as cores that do not contain airfelt. The core may include one or more channels, Fig.28 Four channels 226, 226' and 227, 227' are shown in FIG. Channels 226, 226', 227 and 227' are optional features. Conversely, the core may not have any channels or may have any number of channels.
[0169] These and other components of exemplary absorbent articles will now be discussed in greater detail.
[0170] Top sheet
[0171] In the present disclosure, top sheet (the part that contacts the skin of the wearer and receives fluid of absorbent article) can be formed by a part of one or more in three-dimensional nonwoven material as herein described or all, and / or have one or more in the nonwoven material that is positioned thereon and / or is joined to it, so that one or more nonwoven materials contact the skin of the wearer.Other parts of top sheet (part except the three-dimensional nonwoven material) also can contact the skin of the wearer.Three-dimensional nonwoven material can be positioned on the top of typical top sheet 224 as strip or patch.Alternatively, three-dimensional nonwoven material can only form the center CD area of top sheet.The center CD area can extend the full MD length of top sheet or be less than the full MD length of top sheet.
[0172] As is well known to those skilled in the art, the top sheet 224 can be joined to the back sheet 225, the absorbent core 228, and / or any other layer. Typically, the top sheet 224 and the back sheet 225 are directly joined to each other at some locations (e.g., at or near the periphery of the absorbent article), and are indirectly joined together at other locations by making them directly joined to one or more other elements of the article 220.
[0173] The top sheet 224 can be compliant, feel soft, and non-irritating to the wearer's skin. In addition, a part or all of the top sheet 224 can be liquid permeable, allowing liquid to easily seep through its thickness. In addition, a part or all of the top sheet 224 can be processed with a surfactant or other reagent to hydrophilize the fiber web or make it hydrophobic. As generally disclosed in the art, any part of the top sheet 224 can be coated with lotion and / or skin care composition. The top sheet 224 also can include an antimicrobial agent or be processed with an antimicrobial agent.
[0174] Negatives
[0175] Backsheet 225 is normally that part of the surface positioning facing clothes of the adjacent absorbent core 228 of absorbent article 220 and it prevents or at least suppresses the fluid and body exudates absorbed and contained therein to soil articles such as sheets and underwear. Backsheet 225 is normally impermeable to fluid (for example, urine), or at least basically impermeable. Backsheet can be for example or include thin plastic film such as thermoplastic film, and it has the thickness of about 0.012mm to about 0.051mm. Other suitable backsheet materials can include breathable materials, which allow steam to escape from absorbent article 220, while still preventing or at least suppressing fluid from penetrating backsheet 225.
[0176] The backsheet 225 may be joined to the topsheet 224, the absorbent core 228, and / or any other element of the absorbent article 220 by any attachment method known to those skilled in the art.
[0177] The absorbent article may include a backsheet including an outer cover or an outer cover nonwoven. The outer cover or outer cover nonwoven of the absorbent article 220 may cover at least a portion or all of the backsheet 225 to form a soft, garment-facing surface of the absorbent article. The outer cover or outer cover nonwoven may be formed by a high-loft three-dimensional nonwoven material as described herein. Alternatively, the outer cover or outer cover nonwoven may include one or more known outer cover materials. If the outer cover includes one of the three-dimensional nonwoven materials disclosed herein, the three-dimensional nonwoven material of the outer cover may or may not match (e.g., the same material, the same pattern) the top sheet or the top sheet and the three-dimensional nonwoven material of the acquisition layer used as the absorbent article. In other examples, the outer cover may have a printed or otherwise applied pattern that matches or is visually similar to the pattern of the three-dimensional nonwoven material used as the top sheet or the top sheet and the acquisition layer laminate of the absorbent article. The outer cover may be joined to at least a portion of the backsheet 225 by mechanical bonding, ultrasonic bonding, thermal bonding, adhesive bonding, or other suitable attachment methods.
[0178] Absorbent core
[0179] The absorbent core is the following component of an absorbent article that has a maximum absorption capacity and includes an absorbent material and a core wrap or core bag that encapsulates the absorbent material. The absorbent core does not include any other component of the absorbent article that is not an integral part of the core wrap or core bag or is not placed in the core wrap or core bag of the acquisition and / or distribution system. The absorbent core may include, consist essentially of, or consist of a core wrap, the absorbent material in question (e.g., superabsorbent polymer and little or no cellulose fiber), and glue.
[0180] The absorbent core 228 may include an absorbent material having a high amount of superabsorbent polymer (abbreviated herein as "SAP") encapsulated in a core wrap. The SAP content may represent 70% to 100% or at least 70%, 75%, 80%, 85%, 90%, 95%, 99% or 100% by weight of the absorbent material contained in the core wrap. For the purpose of evaluating the percentage of SAP in the absorbent core, the core wrap is not considered to be an absorbent material. The absorbent core may include air felt with or without superabsorbent polymer.
[0181] So-called "absorbent material" refers to a material with some absorption properties or liquid retention properties, such as SAP, cellulose fiber and synthetic fiber. Typically, the glue used to prepare the absorbent core does not have or has very little absorption properties, and is not considered to be an absorbent material. SAP content can account for more than 80% of the weight of the absorbent material contained in the core wrap, for example at least 85%, at least 90%, at least 95%, at least 99%, and even up to and including 100%. Compared to the conventional core that usually comprises SAP between 40% and 60% by weight and high-content cellulose fiber, the core that does not contain air-permeable felt is relatively thin. Absorbent material can specifically comprise less than 15% weight percent or less than 10% weight percent of natural fiber, cellulose fiber or synthetic fiber, less than 5% weight percent, less than 3% weight percent, less than 2% weight percent, less than 1% weight percent, or even can be substantially free of natural fiber, cellulose fiber and / or synthetic fiber.
[0182] As described above, compared to conventional cores, cores without air felt with very little or no natural fibers, cellulose fibers and / or synthetic fibers are quite thin, making the overall absorbent article thinner than absorbent articles with cores containing mixed SAP and cellulose fibers (e.g., 40% to 60% cellulose fibers). The core thinness may cause consumers to perceive reduced absorbency and performance, but technically this is not the case. At present, these thin cores are usually used with substantially planar or perforated top sheets. In addition, absorbent articles with these thin cores without air felt also have reduced capillary void spaces because there are very few or no natural fibers, cellulose fibers, or synthetic fibers in the core. Therefore, sometimes there may not be enough capillary void spaces in absorbent articles to fully accept multiple insults or single large insults of body exudates.
[0183] To address such problems, the present disclosure provides absorbent articles with these thin, air-free cores, which are combined with one of the high-loft three-dimensional nonwoven materials described herein as a top sheet or a top sheet and a collection layer laminate. In this example, the consumer's perception of absorbency and performance is enhanced, although there is an increased thickness of the absorbent article due to the additional thickness provided by the high-loft three-dimensional nonwoven material. In addition, when used with these thin, air-free cores and used as a top sheet or a top sheet and a collection layer laminate, the three-dimensional nonwoven material adds capillary void space back into the absorbent article while still allowing a minimal stack height, thereby passing on cost savings to consumers and manufacturers. Therefore, due to the increased capillary void space, the absorbent article of the present disclosure can easily absorb multiple insults of body exudates or a single large insult. Additionally, absorbent articles comprising nonwoven materials as topsheets or topsheet and acquisition layer laminates also provide consumers with an aesthetically pleasing topsheet relative to flat topsheets or apertured topsheets with increased thickness and thus enhanced consumer perception of absorbency and performance.
[0184] exist Figure 33 to Figure 35 Shown in separate form Figure 31 to Figure 32 220 of an absorbent article 220. The absorbent core 228 may include a front side 480, a back side 282, and two longitudinal sides 284, 286 joining the front side 480 and the back side 282. The absorbent core 228 may also include a generally planar top side and a generally planar bottom side. The front side 480 of the core is the side of the core that is intended to be placed toward the front waist edge 210 of the absorbent article. As shown in Fig.28 When viewed from the top in the plan view shown, the core 228 may have a longitudinal axis 280' that substantially corresponds to the longitudinal axis 280 of the absorbent article 220. The absorbent material may be distributed in a higher amount toward the front side 480 than toward the back side 282, because greater absorbency may be required at the front of the absorbent article in particular. The front and back sides 480 and 282 of the core may be shorter than the longitudinal sides 284 and 286 of the core. The core wrap may be formed of two nonwoven materials, substrates, laminates, or other materials 216, 216', which may be at least partially sealed along the sides 284, 286 of the absorbent core 228. The core wrap may be at least partially sealed along its front side 480, back side 282, and both longitudinal sides 284, 286 so that substantially no absorbent material leaks out of the absorbent core wrap. The first material, substrate, or nonwoven fabric 216 may at least partially surround the second material, substrate, or nonwoven fabric 216' to form a core wrap, such as Fig.34 The first material 216 may surround portions of the second material 216' adjacent to the first and second sides 284 and 286.
[0185] The absorbent core may contain, for example, an adhesive to help secure the SAP within the core wrap and / or to ensure the integrity of the core wrap, particularly when the core wrap is made of two or more substrates. The adhesive may be a hot melt adhesive supplied by, for example, HB Fuller. The core wrap may extend to an area larger than the area strictly required to contain the absorbent material therein.
[0186] The absorbent material may be a continuous layer present in the core wrap. Alternatively, the absorbent material may be composed of a bag or strip of a separate absorbent material encapsulated in the core wrap. In the first case, the absorbent material may be obtained, for example, by applying a single continuous layer of absorbent material. The continuous layer of absorbent material (particularly, SAP) may also be obtained by combining two absorbent layers with a discontinuous absorbent material application pattern, wherein the resulting layer is substantially continuously distributed in the absorbent particulate polymer material region, as disclosed in, for example, U.S. Patent Application Publication 2008 / 0312622A1 (Hundorf). The absorbent core 228 may include a first absorbent layer and a second absorbent layer. The first absorbent layer may include a first material 216 and a first layer 261 of an absorbent material, which may be 100% or less SAP. The second absorbent layer may include a second material 216' and a second layer 262 of an absorbent material, which may be 100% or less SAP. The absorbent core 228 may also include a fibrous thermoplastic adhesive material 251 that at least partially bonds each layer 261, 262 of absorbent material to its respective material 216 or 216'. Figure 34 to Figure 35 , for example, where the first and second SAP layers have been applied to their respective substrates in the form of transverse strips or "landing zones" having the same width as the desired absorbent material deposition area and then combined. The strips may contain different amounts of absorbent material (SAP) to provide a basis weight distributed along the longitudinal axis of the core 280. The first material 216 and the second material 216' may form a core wrap.
[0187] The fibrous thermoplastic adhesive material 251 may at least partially contact the absorbent material 261, 262 in the landing area and at least partially contact the material 216 and 216' in the joining area. This gives the fibrous layer of thermoplastic adhesive material 251 a substantially three-dimensional structure, which itself is a substantially two-dimensional structure with a relatively small thickness compared to the dimensions in the length and width directions. Thus, the fibrous thermoplastic adhesive material can provide a cavity to cover the absorbent material in the landing area, thereby fixing the absorbent material, which can be 100% or less SAP.
[0188] The thermoplastic binder used for the fiber layer may have elastomeric properties so that the fiber web formed by the fibers on the SAP layer can be stretched when the SAP swells.
[0189] Superabsorbent polymer (SAP)
[0190] SAPs useful in the present disclosure may include a variety of water-insoluble but water-swellable polymers capable of absorbing large amounts of fluid.
[0191] The superabsorbent polymer may be in particulate form so as to be flowable in a dry state. The particulate absorbent polymer material may be made of poly(meth)acrylic acid polymers. However, starch-based particulate absorbent polymer materials may also be used, as well as polyacrylamide copolymers, ethylene maleic anhydride copolymers, cross-linked carboxymethyl cellulose, polyvinyl alcohol copolymers, cross-linked polyethylene oxide, and starch-grafted copolymers of polyacrylonitrile.
[0192] SAP can have various shapes. The term "particle" refers to granules, fibers, flakes, spheres, powders, thin plates, and other shapes and forms known to those skilled in the art in the field of superabsorbent polymer particles. SAP particles can be in the shape of fibers, i.e., elongated needle-like superabsorbent polymer particles. Fibers can also be in the form of woven filaments. SAP can be spherical particles. The absorbent core can contain one or more types of SAP.
[0193] For most absorbent articles, liquid discharge from the wearer occurs primarily in the front half of the absorbent article, particularly a diaper. Thus, the front half of the article (as defined by the area between the front edge and a transverse line disposed at a distance of half L from the front waist edge 210 or the back waist edge 212) may include most of the core's absorbent capacity. Thus, at least 60% of the SAP, or at least 65%, 70%, 75%, 80% or 85% of the SAP may be present in the front half of the absorbent article, while the remaining SAP may be disposed in the back half of the absorbent article. Alternatively, the SAP distribution throughout the core may be uniform or may have other suitable distributions.
[0194] The total amount of SAP present in the absorbent core may also vary depending on the desired user. Diapers for newborns may require less SAP than baby diapers, children's diapers or adult incontinence diapers. The amount of SAP in the core may be about 5g to 60g or 5g to 50g. The average SAP basis weight in the deposition area 8 of SAP (or if there are several, "at least one") may be at least 50g / m 2 , 100g / m 2 , 200g / m 2 , 300g / m 2 , 400g / m 2 , 500g / m 2 The areas of the channels (eg, 226, 226', 227, 227') present in the absorbent material deposition region 8 are derived from the absorbent material deposition area to calculate the average basis weight.
[0195] Core wrap
[0196] The core wrap may be made of a single substrate, material or nonwoven folded around the absorbent material, or may include two (or more) substrates, materials or nonwovens attached to each other. Typical attachments are so-called C-wraps and / or sandwich wraps. In a C-wrap, for example, as shown in the figure, Fig.29 and Fig.34 In the present invention, the longitudinal and / or transverse edges of one of the substrates are folded over another substrate to form a flap. Then, these flaps are usually bonded to the outer surface of the other substrate by gluing.
[0197] The core wrap may be formed of any material suitable for receiving and containing the absorbent material.Typical substrate materials for making conventional cores may be used, in particular paper, tissue, film, woven or nonwoven fabric, or a laminate or composite of any of these materials.
[0198] The substrate may also be breathable (in addition to being liquid or fluid permeable). Thus, films useful herein may include micropores.
[0199] The core wrap may be at least partially sealed along all sides of the absorbent core so that substantially no absorbent material leaks out of the core. By "substantially no absorbent material" is meant that less than 5%, less than 2%, less than 1% or about 0% by weight of the absorbent material escapes from the core wrap. The term "seal" should be understood in a broad sense. The seal need not be continuous along the entire periphery of the core wrap, but may be discontinuous along part or all of it, such as formed by a series of sealing points spaced apart in a line. The seal may be formed by gluing and / or thermal bonding.
[0200] If the core wrap is formed by two substrates 216, 216', four seals can be used to enclose the absorbent material 260 in the core wrap. For example, the first substrate 216 can be placed on one side of the core (e.g. Figure 33 to Figure 35The top side shown in the figure) and the longitudinal edge of the core extends to at least partially wrap the relative bottom side of the core. The second substrate 216' may be present between the wrapped fins of the first substrate 216 and the absorbent material 260. The fins of the first substrate 216 can be glued to the second substrate 216' to provide a strong seal. Compared with the sandwich seal, the so-called C-wrapper structure can provide a beneficial effect, such as improved crack resistance under a wet load state. Then, the front and back sides of the core wrapper can also be sealed by gluing the first substrate and the second substrate to each other to provide a complete encapsulation of the absorbent material across the entire periphery of the core. For the front and back sides of the core, the first substrate and the second substrate can extend in a substantially planar direction and can be joined together, forming a so-called sandwich structure for these edges. In the so-called sandwich structure, the first substrate and the second substrate can also extend outward on all sides of the core, and are usually sealed flatly or substantially flatly along all or part of the periphery of the core by gluing and / or heat / pressure bonding. In one example, neither the first substrate nor the second substrate need to be shaped so that they can be cut rectangularly for ease of manufacture, but other shapes are also within the scope of the present disclosure.
[0201] The core wrap may also be formed from a single substrate which encloses the absorbent material in a wrap and is sealed along the front and back sides of the core and a longitudinal seal.
[0202] SAP deposition area
[0203] As seen from the top side of the absorbent core, the absorbent material deposition area 208 can be defined by the perimeter of the layer defined by the absorbent material 260 within the core wrap. The absorbent material deposition area 208 can have a variety of shapes, specifically a so-called "dog bone" or "hourglass" shape showing a taper along its width toward the middle or "crotch" region of the core. In this way, the absorbent material deposition area 8 can have a relatively narrow width in a core region intended to be placed in the crotch region of an absorbent article, such as Fig.28 This can provide better wearing comfort. The absorbent material deposition area 8 can also be roughly rectangular, for example Figure 31 to Figure 33 As shown, however other deposition areas, such as rectangular, "T", "Y", "hourglass" or "dog bone" shapes are also within the scope of the present disclosure. The absorbent material may be deposited using any suitable technique that allows for relatively precise deposition of the SAP at relatively high speeds.
[0204] aisle
[0205] The absorbent material deposition area 208 may include at least one channel 226 that is at least partially oriented in the longitudinal direction of the article 280 (ie, has a longitudinal vector component), such as Fig.28 and Fig.29As shown. Other channels may be at least partially oriented in the lateral direction (i.e., having a lateral vector component) or oriented in any other direction. Hereinafter, the plural form "channels" will be used to refer to "at least one channel". The channel may have a length L' projected on the longitudinal axis 280 of the article, which is at least 10% of the length L of the article. The channel can be formed in various ways. For example, the channel may be formed by a zone in the absorbent material deposition area 208 that may be substantially free of or free of absorbent material, specifically SAP. In another example, the channel may be formed by a zone in the absorbent material deposition area 208, where the absorbent material of the core includes cellulose, air felt, SAP, or a combination thereof, and the channel may be substantially free of or free of absorbent material, specifically SAP, cellulose, or air felt. In addition or alternatively, one or more channels may also be formed by continuously or discontinuously bonding the top side of the core wrap to the bottom side of the core wrap via the absorbent material deposition area 208. The channel may be continuous, but it is also envisioned that the channel may be intermittent. The acquisition-distribution system or layer 250 or other layers of the article may also comprise channels, which may or may not correspond to channels of the absorbent core.
[0206] In some examples, the channel may exist at least at the same longitudinal position as the crotch point C or the lateral axis 260 in the absorbent article, such as Fig.28 The channels may also extend from the crotch region 207 or may be present in the front waist region 205 and / or the back waist region 206 of the article.
[0207] The absorbent core 228 may also include more than two channels, such as at least 3, at least 4, at least 5, or at least 6 or more channels. Shorter channels may also be present, for example, in the back waist region 206 or the front waist region 205 of the core, such as by Fig.28 The channels may include one or more pairs of channels arranged symmetrically with respect to the longitudinal axis 280, or arranged in other ways.
[0208] Channels are particularly useful in absorbent cores when the absorbent material deposition area is rectangular, since the channels can improve the flexibility of the core to a lesser extent than would be advantageous with a non-rectangular (shaped) core. Of course, channels can also be present in SAP layers having shaped deposition areas.
[0209] The channels may be completely longitudinally oriented and parallel to the longitudinal axis or completely transversely oriented and parallel to the lateral axis, but may also have at least some portions that are curved.
[0210] To reduce the risk of fluid leakage, the longitudinal main channels may not extend to either edge of the absorbent material deposition area 208 and may therefore be completely contained within the core absorbent material deposition area 208. The minimum distance between the channel and the nearest edge of the absorbent material deposition area 208 may be at least 5 mm.
[0211] The channel may have a width Wc along at least a portion of its length, such as at least 2 mm, at least 3 mm, at least 4 mm, such as 20 mm, 16 mm, or 12 mm at most. The width of one or more channels may be constant over substantially the entire length of the channel, or may vary along its length. When the channel is formed by a non-absorbent material zone in the absorbent material deposition area 208, it is considered that the width of the channel is the width of the zone without material, without considering the possibility of a core wrap in the channel. If the channel is not formed by a non-absorbent material zone, such as primarily formed by bonding of the core wrap in the entire absorbent material zone, the width of the channel is the width of the bonding.
[0212] At least some or all of the channels may be permanent channels, meaning that their integrity is maintained at least partially in a dry state and in a wet state. Permanent channels may be obtained by providing one or more adhesive materials, such as an adhesive material fiber layer or a structural adhesive that helps to adhere substrates and absorbent materials in the channel wall. Permanent channels may also be formed by bonding the upper and lower sides (such as the first substrate 216 and the second substrate 216') of the core wrapping material via the channel and / or bonding the top sheet 224 and the back sheet 225 together. Typically, adhesives may be used to bond the two sides or the top sheet and the back sheet of the core wrapping material through the channel, but it may be bonded via other known methods, such as pressure bonding, ultrasonic bonding, thermal bonding, or a combination thereof. The core wrapping material or the top sheet 224 and the back sheet 225 may be bonded continuously or intermittently along the channel. When the absorbent article is fully loaded with fluid, the channel may advantageously be maintained or become visible through at least the top sheet and / or the back sheet. This may be achieved by making the channel substantially free of SAP, so that it will not swell, and being large enough to obtain it by not closing when wetted. Furthermore, it may be advantageous to bond the core wrap to itself or to bond the topsheet to the backsheet through channels.
[0213] Barrier leg cuffs
[0214] The absorbent article may include a pair of barrier leg cuffs 34. Each barrier leg cuff may be formed by a material piece that is bonded to the absorbent article so that it can extend upward from the wearer-facing surface of the absorbent article and provide improved containment of fluid and other body exudates near the junction of the wearer's torso and legs. The barrier leg cuff is defined by the proximal edge directly or indirectly bonded to the top sheet 224 and / or the back sheet 225 and the free end edge 266, which is intended to contact the wearer's skin and form a seal. The barrier leg cuff 234 extends between the front waist edge 210 and the back waist edge 212 of the absorbent article on the opposite side of the longitudinal axis 280 at least partially, and is present at least at the crotch point (C) or the position of the crotch area. The barrier leg cuff can be bonded to the base structure of the article at the proximal edge 264 by a bonding portion 265, which can be made by a combination of gluing, melt bonding or other suitable bonding methods. The bonding portion 265 at the proximal edge 264 can be continuous or intermittent. The bond 265 closest to the raised section of the leg cuff defines the proximal edge 264 of the upstanding section of the leg cuff.
[0215] The barrier leg cuffs may be integral with the topsheet 224 or the backsheet 225, or may be separate materials joined to the chassis of the article. Each barrier leg cuff 234 may include one, two or more elastic bands 235 near the free end edge 266 to provide a better seal.
[0216] In addition to the barrier leg cuffs 234, the article may also include a gasketing cuff 232 that is joined to the chassis of the absorbent article (specifically the topsheet 224 and / or the backsheet 225) and may be positioned externally relative to the barrier leg cuffs. The gasketing cuffs 232 may provide a better seal around the wearer's thighs. Each gasketing leg cuff may include one or more elastic bands or elastic elements 233 in the chassis of the absorbent article between the topsheet 224 and the backsheet 225 in the leg opening area. All or a portion of the barrier leg cuffs and / or the gasketing cuffs may be treated with a lotion or another skin care composition.
[0217] Collection-distribution system
[0218] The absorbent articles of the present disclosure may include an acquisition-distribution layer or system 250 ("ADS"). One function of the ADS is to quickly acquire one or more of the fluids and distribute them to the absorbent core in an efficient manner. The ADS may include one, two or more layers, which may form an integral layer or may be maintained as discrete layers that may be attached to each other. In one example, the ADS may include two layers: a distribution layer 254 and an acquisition layer 252, which are disposed between the absorbent core and the top sheet, but the present disclosure is not limited thereto.
[0219] In one example, the high loft three-dimensional nonwoven material of the present disclosure may include a topsheet and an acquisition layer as a laminate. A distribution layer may also be disposed on the garment-facing side of the topsheet / acquisition layer laminate.
[0220] Carrier layer
[0221] In an example where the high loft three-dimensional nonwoven material of the present disclosure comprises a top sheet and an acquisition layer laminate, the distribution layer may need to be supported by a carrier layer (not shown), which may include one or more nonwoven materials or other materials. The distribution layer may be applied to or positioned on the carrier layer. Thus, the carrier layer may be positioned intermediate the acquisition layer and the distribution layer and in a facing relationship with the acquisition layer and the distribution layer.
[0222] Distribution Layer
[0223] The distribution layer of the ADS may contain at least 50% by weight of cross-linked cellulose fibers. The cross-linked cellulose fibers may be pleated, twisted, or curled, or a combination thereof (including pleated, twisted, and curled). This type of material is disclosed in U.S. Patent Publication 2008 / 0312622A1 (Hundorf). The cross-linked cellulose fibers provide higher elasticity and thus higher resistance to compression of the first absorbent layer in the product package or under use conditions (e.g., under the weight of the wearer). This can provide higher void volume, permeability, and liquid absorption to the core, thereby reducing leakage and improving dryness.
[0224] A distribution layer comprising crosslinked cellulosic fibers of the present disclosure may comprise other fibers, but the layer may advantageously comprise at least 50%, or 60%, or 70%, or 80%, or 90%, or even up to 100% crosslinked cellulosic fibers (including the crosslinking agent) by weight of the layer.
[0225] Collection Layer
[0226] If the three-dimensional nonwoven material of the present disclosure is provided only as the top sheet of the absorbent article, the ADS 250 may include an acquisition layer 252. The acquisition layer may be disposed between the distribution layer 254 and the top sheet 224. In such an example, the acquisition layer 252 may be or may include a nonwoven material, such as a hydrophilic SMS or SMMS material, including a spunbond layer, a meltblown layer and another spunbond layer or an alternatively carded staple fiber chemically bonded nonwoven fabric. The nonwoven material may be latex bonded.
[0227] Fastening system
[0228] The absorbent article may include a fastening system. The fastening system may be used to provide lateral tension around the circumference of the absorbent article to keep the absorbent article on the wearer, which is typical for adhesive diapers. The fastening system may not be necessary for training pants products because the waist area of these products has been bonded. The fastening system may include fasteners, such as belt tabs, hook and loop fastening components, interlocking fasteners such as tabs and slits, buckles, buttons, snaps and / or hermaphroditic fastening components, but any other suitable fastening mechanism is also within the scope of the present disclosure. The landing zone 244 is generally disposed on the garment-facing surface of the front waist region 205 for releasably attaching the fastener thereto.
[0229] Front and back ears
[0230] The absorbent article may include front ears 246 and back ears 240. The ears may be an integral part of the chassis, such as formed by the top sheet 224 and / or the back sheet 226 in the form of side panels. Alternatively, as Fig.28 As shown, the ears can be separate elements attached by gluing, heat embossing and / or pressure bonding. The back ears 240 can be stretchable to help the tabs 242 attach to the landing zone 244 and keep the taped diaper in place around the waist of the wearer. The back ears 240 can also be elastic or extensible to provide a more comfortable and conformable fit to the wearer by initially conforming to the absorbent article and maintaining the fit throughout the wear period when the absorbent article is loaded with fluids or other body exudates because the elasticized ears allow the sides of the absorbent article to expand and contract.
[0231] Elastic waist feature
[0232] The absorbent article 220 may also include at least one elastic waist feature (not shown) that helps provide improved fit and restraint. The elastic waist feature is generally intended to elastically expand and contract to dynamically fit the wearer's waist. The elastic waist feature may extend outwardly at least longitudinally from at least one waist edge of the absorbent core 228 and generally form at least a portion of the end edge of the absorbent article. A disposable diaper may be constructed so as to have two elastic waist features, one positioned in the front waist region and the other positioned in the back waist region.
[0233] Color signal
[0234] In one form, the absorbent articles of the present disclosure may have different colors in different layers or portions thereof (e.g., topsheet and acquisition layer, topsheet and nonwoven core cover, first and second portions of the topsheet, first and second portions of the acquisition layer). The different colors may be shades of the same color (e.g., dark blue and light blue), or may be actual different colors (e.g., purple and green). The different colors may have a ΔE, for example, in the range of about 1.5 to about 10, about 2 to about 8, or about 2 to about 6. Other ΔE ranges are also within the scope of the present disclosure.
[0235] In one example, a colored adhesive may be used to join the various layers of an absorbent article. The colored adhesive may be laid in a pattern on any suitable layer or layers. The adhesive pattern may or may not be complementary to the topsheet pattern. Such a pattern may enhance the appearance of depth in the absorbent article. In some examples, the colored adhesive may be blue.
[0236] In other examples, any of the layers may include indicia, such as printed ink, to contribute to the appearance, impression of depth, impression of absorbency, or impression of quality of the absorbent article.
[0237] In other examples, the color may be complementary or aligned with the pattern of the three-dimensional features of the nonwoven fabric 10 used as a component in an absorbent article. For example, the fabric of the first and second zones having visually distinct patterns of three-dimensional features may also have colors printed thereon to strengthen, highlight, contrast, or otherwise change the visual appearance of the fabric 10. Color enhancement may be useful in conveying certain functional features of the nonwoven fabric 10 when in use to the user of the absorbent article. Therefore, color may be used in combination with the structural three-dimensional features in a component or combination of components to deliver visually distinctive absorbent articles. For example, the second top sheet or acquisition layer may have a pattern of one or more colors printed thereon that is complementary to the pattern of the three-dimensional features of the fabric 10 used as a top sheet in an absorbent article. Another example is an absorbent article comprising: 1) an absorbent core comprising channels; 2) a top sheet having a registered three-dimensional pattern or a three-dimensional pattern that highlights one or more channels in the core; and 3) graphics, colored components, printed inks, or markings visible from the top sheet viewing surface (body contacting surface) or the back sheet viewing surface (garment facing surface) to further enhance the functional characteristics structure of the core channel or multiple core channels and the overall performance of the absorbent article.
[0238] Further characterization of the novel aspects of the present disclosure can be achieved by focusing on the three-dimensional features in the visually discernible zone. Each of the zones discussed above, such as zones 110, 120, and 130, can be further described with respect to micro-zones. A micro-zone is a portion of the nonwoven fabric 10 in a zone having at least two visually discernible regions, and a common strength property difference exists between the two zones. A micro-zone may include a portion of the nonwoven fabric 10 that passes through two or more zone boundaries having at least two visually discernible regions, and a common strength property difference exists between the two zones.
[0239] The benefits of micro-regions are considered in the present disclosure to illustrate that, in addition to the differences in average strength properties with zones such as zones 110, 120, and 130 (as described above), the present disclosure also provides fabrics having differences in actual and / or average strength properties between zones defined by three-dimensional features within the zones, wherein the three-dimensional features are precisely placed according to the design of the forming belt used to produce the fabric. The differences between the strength properties between the zones of the three-dimensional features provide additional visual benefits and functional benefits. The sharp visual contrast between the zones can provide extremely fine, visually distinctive designs within and between the zones. Similarly, the precise positioning of the zones provided by the precisely manufactured forming belt can provide excellent and customized softness, strength, and fluid handling properties of the zones. Therefore, in one embodiment, the present invention provides a combination of differences in average strength properties between the zones and differences in strength properties of the zones constituting the micro-regions.
[0240] refer to Fig.38 and Fig.39 It is understood that the area is defined by a three-dimensional feature structure. Fig.38 An optical microscope image of a portion of a fabric 10 according to the present disclosure is shown, and Fig.39 for Fig.38 A scanning electron micrograph (SEM) of a cross section of a portion of the fabric shown in FIG. Fig.38 and Fig.39 A portion of nonwoven fabric 10 is shown enlarged to more accurately depict otherwise visually discernible features of the fabric. Fig.38 The portion of nonwoven fabric 10 shown is approximately 36 mm in CD and exhibits portions of at least three visually distinct zones, as described below.
[0241] exist Fig.38 and Fig.39 , a portion of a pattern of a nonwoven fabric 10 is shown, with a first region 110 (in Fig.38The first region is also a three-dimensional feature structure 20 that defines the first region 300 and the second region 310. In one embodiment, the three-dimensional feature structure is a portion of the nonwoven fabric 10 formed between or around the raised elements of the forming belt, which portion is the first region 300 in this specification, so that the resulting structure has a relatively larger dimension in the Z direction. The adjacent second region 310 generally has strength characteristics in common with the first region 300, and in one embodiment has a relatively lower thickness value, i.e., has a smaller dimension in the Z direction. Fig.39 The relative sizes in the Z direction relative to the plane of the first surface 16 as described above can be seen in FIG. The absolute sizes are not critical; however, without magnification, the size differences can be visually discerned on the nonwoven fabric 10.
[0242] The invention disclosed herein allows for optimal expression of beneficial features relative to areas defined by three-dimensional features in micro-regions. Fig.38 As shown, in zone 110, for each three-dimensional feature structure 20, there is a visual distinction between the first region 300 and the second region 310. As described above, visual distinctions may exist in the nonwoven fabric 10 without magnification; the magnified views used herein are for the purpose of clear disclosure. Any region extending over the boundary between the first region 300 and the second region 310 sufficient to allow the difference in their respective intensity characteristics to be determined within the region may be a micro-region. In addition, optical microscopy or micro-CT images of the structure may also be used to establish the location of the region and the area of the micro-region.
[0243] Fig.38 The portion of the nonwoven fabric 10 shown further illustrates another beneficial feature of the fabric 10, which is that the difference in strength properties between adjacent regions can be a difference across the region. Thus, micro-regions can be identified that span the region including the second region 310 of region 120 and the first region 300 of region 130. In certain embodiments, the micro-regions included in Fig.38 and Fig.39 In the illustrated nonwoven fabric 10, the differences in strength properties exhibited by regions within a microdomain at the domain boundaries can differ significantly in magnitude from the differences between strength properties exhibited by regions within a domain.
[0244] No matter which area or which partition boundary a particular microregion includes, the three-dimensional characteristic structures can be characterized by the difference between the strength characteristics of the areas defined by them. Generally speaking, the nonwoven fabric of the present disclosure can be a spunbonded nonwoven fabric with a first surface of the plane defining the first surface. The fabric can have a plurality of three-dimensional characteristic structures, each of which defines a first region and a second region, and these regions have common strength characteristics with different values therebetween. In one embodiment, the first region can be distinguished as being at a higher height than the second region relative to the plane of the first surface, and therefore showing differences in the common strength characteristics of the thickness of each region. The two regions can also be distinguished as having different densities, basis weights, and bulk densities. That is, the two regions can be distinguished in the microregion of the spunbonded nonwoven fabric because they are different in common strength characteristics, including characteristics such as thickness, density, basis weight, and bulk density. In one embodiment, one or two regions of the microregion can be fluid permeable. In one embodiment, the higher density region of the microregion can be fluid permeable.
[0245] For example, in Fig.38 Within the region 110 of the portion of the fabric shown, there may be three-dimensional features 20 that define at least two regions, a first region 300 and a second region 310 . Fig.38 The differences in thickness, basis weight, and bulk density between the first and second regions of zone 110 as shown may be 274 microns, 1 gsm, and 0.437 g / cc, respectively.
[0246] Likewise, in Fig.38 Within the region 130 of the portion of the fabric shown, there may be three-dimensional features 20 that define at least two regions, a first region 300 and a second region 310 . Fig.38 The differences in thickness, basis weight, and bulk density between the first and second regions of zone 130 as shown may be 2083 microns, 116 gsm, and 0.462 g / cc, respectively.
[0247] In addition, Fig.38 Within the region 120 of the portion of the fabric shown, there may be three-dimensional features 20 that define at least two regions, a first region 300 and a second region 310 . Fig.38 The difference in thickness, basis weight, and bulk density between the first and second regions of the portion of the fabric shown may be 204 microns, 20 gsm, and 0.53 g / cc, respectively. In the illustrated embodiment, region 120 forms the region that appears in the unenlarged view of nonwoven fabric 10, which is the stitching boundary between region 110 and region 130.
[0248] in addition, Fig.38A zone including a boundary between zone 120 and zone 130 of a portion of the fabric is shown, for example, there are at least two regions, a first region 300 in zone 130 and a second region 310 in zone 120 . Fig.38 The difference in thickness, basis weight, and bulk density between the first and second regions of a portion of the fabric shown may be 2027 microns, 58 gsm, and 0.525 g / cc, respectively.
[0249] refer to Figure 40 to Figure 42 and Fig.44 The data depicted in are discussed in more detail for microdomains. Figure 40 to Figure 42 A micro-CT scan of a portion of nonwoven fabric 10, with a pattern similar to Fig.38 The pattern of the nonwoven fabric 10 shown. Micro-CT scanning allows the description of the nonwoven fabric 10 in a slightly different way and in a way that allows very accurate measurement of the strength properties. Fig.38 The same characteristic structure is shown.
[0250] like Fig.40 As shown, regions 110, 120 and 130 are clearly visible, with their corresponding three-dimensional features 20. Fig.40 and Fig.41 As shown, the three-dimensional feature structure is a dark portion, wherein the dark color also represents a first region 300 of the three-dimensional feature structure 20 , and the adjacent light-colored portion is a second region 310 of the three-dimensional feature structure 20 .
[0251] MicroCT scanning allows images to be "cut" and show cross-sections, such as Fig.41 The cutting plane 450 can be placed anywhere in the image; for the purposes of this disclosure, the cutting plane 450 cuts a cross section substantially parallel to the Z axis to produce Fig.42 Cross-sectional image of .
[0252] MicroCT technology allows precise and direct measurement of the intensity characteristics of the material. Thickness measurements can be made directly from the imaged cross-section based on the proportional magnification, such as Fig.42 Cross section shown. Additionally, the color difference between the first region and the second region is representative and proportional to the differences in basis weight, bulk density, and other strength properties which are also directly measurable. The micro-CT method is explained in the Test Methods section below.
[0253] Fig.43 for Fig.40 and Fig.41 A micro-CT scan image of a portion of the nonwoven fabric 10 is shown. For specific first and second regions shown as numbered portions of the nonwoven fabric 10, their utilization can be analyzed. Fig.43 , manually select and analyze specific areas to measure thickness, basis weight, and bulk density, and Fig.44 Generate data in .
[0254] Fig.44 Shown in Fig.43 Depicts data for grouping of first and second area measurements made within three zones. The x-axis is the zone, with the numbers corresponding to Fig.43 The first region measurements are labeled Fn (e.g., F1), and the second region measurements are labeled Sn (e.g., S1). Thus, regions 1 to 5 are first regions F1, each in zone 110. Regions 6 to 10 are second regions S1, also in zone 110. Likewise, first region F2 is regions 16 to 20 in zone 120, and regions 11 to 15 and 21 to 25 are second regions S2 in zone 120. Finally, regions 31 to 35 are first regions F3 in zone 130, and regions 26 to 30 are second regions S2 in zone 130. In Fig.44 The numbered regions are depicted consistently on all three graphs of FIG. 1 , but for simplicity, only regions 110 , 120 , and 130 are depicted on the thickness map.
[0255] Fig.44 The graph shown graphically represents the magnitude of the difference in intensive properties between a first region and a second region within any one of the zones, and can be used to graphically visualize the differences in intensive properties of pairs of regions that make up the micro-domains. For example, it can be seen that in zone 110, the basis weight between the two regions can be substantially the same, but the thickness (caliper) can vary from about 400 microns in the first region to about 40 microns in the second region, or a difference of about 10X. The bulk density in zone 110 can vary from about 0.1 g / cc to about 0.6 g / cc. Similar quantifiable differences can be understood for each of the zones shown.
[0256] Therefore, referring to Fig.43 and Fig.44 , further characterization of the beneficial structure of the fabric 10 of the present disclosure can be appreciated. The nonwoven fabric 10 can be described as having at least two visually distinct regions, such as regions 110 and 120, wherein each of the regions has a pattern of three-dimensional features, each of the three-dimensional features defining micro-regions including a first region and a second region, such as regions 300, 310, and wherein the difference in value of at least one of the micro-regions in the first region differs from the difference in value of at least one of the micro-regions in the second region in a quantifiable manner. For example, in Fig.43, two representative micro-regions 400 in region 130 are designated as region pairs labeled as regions 31 and 27 and regions 33 and 26. That is, the first region 31 and the second region 27 form a micro-region, and the first region 33 and the second region 26 form a micro-region. Similarly, two representative micro-regions 400 in region 120 are designated as region pairs labeled as regions 19 and 24 and regions 17 and 22. Fig.44 , Tables 4 to 7 can be filled in as follows:
[0257] Table 4: Illustrative examples of thickness differences in microdomains
[0258]
[0259]
[0260] Table 5: Illustrative Examples of Basis Weight Differences in Micro-Domains
[0261]
[0262] Table 6: Illustrative examples of volume density differences in microdomains
[0263]
[0264] Table 7: Illustrative examples of differences in intensity properties in different regions :
[0265]
[0266]
[0267] For illustrative purposes, Tables 4 to 6 show four representative micro-regions from two regions. However, as can be appreciated, Fig.43 Each pair of first and second regions in can also be quantified to further populate additional rows in Table 4, but for the sake of simplicity this is not done. In general, for any fabric having two or more regions, each region having a pattern of three-dimensional features defining micro-regions, as described herein with reference to Fig.43 and Fig.44 As shown, the intensity characteristic may be measured and tabulated to understand both the difference in the value of the intensity characteristic within a zone, and the difference in the value of the intensity characteristic between one area in a first zone and another area in a second zone.
[0268] Micro-regions spanning two zones, such as zone 110 and zone 130, may have even greater differences in strength properties relative to micro-regions within a single zone. For example, looking at the data for micro-regions spanning a first region of zone 130, such as at first region 32, and a second region of zone 110, such as at second region 8, the micro-regions exhibit significant differences in all thicknesses, basis weights, and bulk densities. The thickness of the first region 32 of zone 130 is about 2100 microns, while the thickness of the second region 8 of zone 110 is about 29 microns, or a difference of about 72X. Similarly, the basis weight of the first region 32 of zone 130 may be as high as 150 gsm, while the basis weight of the second region 8 of zone 110 may be about 14 gsm, or a difference of about 10X. In addition, the bulk density of the first region 32 of zone 130 may be about 0.069 g / cc, while the bulk density of the second region 8 of zone 110 may be 0.492 g / cc, or a difference of about 7X.
[0269] For each of the measured intensity characteristic parameters of various regions of the micro-domain, such measurements are performed using the micro-CT method described herein. The method solution supports establishing the intensity characteristics of the micro-domain region, so that the difference and ratio comparison of the regions sized as described herein can be performed.
[0270] Further characterization of fabric 10 can be found in Figures 45 to 49 conduct, Figures 45 to 49 is a SEM showing certain aspects of nonwoven fabric 10 and regions therein in greater detail. Figures 45 to 49 for Fig.38 A photograph of an enlarged portion of area 110 of the fabric is shown. Fig.38 The nonwoven fabric 10 shown is based on the above reference Figure 7 The method described is one in which the fabric is processed through a nip formed by compacting rolls 70 and 72, roll 72 contacting first side 12 being heated to cause localized bonding of the fibers in second region 301. Fig.45 (Facing belt) and Fig.46 (facing the heated compaction roll) SEM of a portion of the second surface 14 and the first surface 12, respectively, magnified 20X. Fig.47 (Facing belt) and Fig.48 (facing the heated compaction rolls) is a photograph of a portion of the second surface 14 and the first surface 12, respectively, magnified to 90X and showing in detail the beneficial structural feature of the partial bonding of the fibers formed by the compaction rolls 70 and 72.
[0271] from Fig.47 and Fig.48 as well as Fig.49As can be best seen in the cross-sectional view of FIG, the heated compaction rollers can cause the fibers to be thermally bonded to varying degrees, thereby producing a beneficial effect on the overall fabric 10. As shown, the fibers in contact with the heated rollers (e.g., roller 70 in contact with the first surface 12 of the fabric 10) can be melt-bonded, so that the first surface 12 is subjected to relatively greater fiber-fiber bonding than the second surface 14. In one embodiment, the bonded fibers 80 of the first surface can actually be substantially completely melt-bonded to form a film skin of bonded fibers, while the fibers in the second region 310 on the second side 14 can be subjected to little or no bonding. This characteristic structure allows the nonwoven fabric 10 used in disposable absorbent articles, such as as a top sheet, to maintain physical integrity during manufacture and use, as well as relative softness on one side, which can be the skin-contacting side facing the user.
[0272] This "skin bonding" effect serves to maintain web integrity even in micro-regions with the greatest thickness differences, without significantly affecting softness or other beneficial properties such as fluid handling properties. Figure 50 to Figure 53 As will be appreciated, the difference in the degree of thermal bonding of the fibers may be such that the fibers on the first surface 12 at the second region 310 may be intact or substantially intact, while the degree of thermal bonding of the fibers on the second surface 14 at the first region 300 may be minimal to non-existent.
[0273] Fig.50 It also shows Fig.38 A portion of a nonwoven fabric 10 is shown. Figure 51 to Figure 53 Shows Fig.50 3 shows an enlarged image of a micro region of the first region 300 and the second region 310 , which visually appears as a cavity or hole. Fig.51 and Fig.52 The micro-domains appearing on the second surface 14 are shown magnified to 40X and 200X respectively. Fig.53 A second region 310 is shown, visualized at 200X magnification, on the first side 12. The fibers in the second region 310 are completely or substantially completely bonded, while the fibers in the first region 300 are not completely or substantially completely bonded. A benefit of the illustrated structure is that the microdomains can function as fluid permeable pores while the bonded areas of the second region 310 simultaneously function to maintain the physical integrity of the fabric 10.
[0274] Thus, micro-domains play an important role in the overall physical structure and function of the fabric 10 of the present invention. By achieving the creation of relatively closely spaced, precisely designed three-dimensional features through the forming belt of the present disclosure, the fabric 10 can exhibit visually distinct zones, micro-domains, and three-dimensional features that provide functional advantages in at least the areas of softness and fluid handling, and provide a visually attractive aesthetic design. The potential differences in the physical properties of the first and second surfaces allow the nonwoven fabric 10 to be designed with respect to both strength and softness, both forming and function.
[0275] Fig.54 For similar Fig.40 and Fig.41 A micro-CT scan image of a portion of the nonwoven fabric 10 shown, but having undergone an additional processing step of forming point bonds 90 in the nip of calender rolls 71 and 73. Fig.43 and Fig.44 For a particular point bonded micro-region 400, the first and second regions shown as numbered portions of the nonwoven fabric 10 can be analyzed, and include point bonded regions (particularly in numbered regions 31 to 35). For example, adjacent regions 32 and 26 form a micro-region 400 in the third zone 130. Fig.54 In the process, specific areas are visually distinguished to identify the area including the added point bonding area and analyzed to measure thickness, basis weight and bulk density, and generate Fig.55 , where the thickness, basis weight and bulk density of all regions 1 to 45 (including the point bond areas) are quantified and compared.
[0276] Fig.55 Shown in Fig.54 The data of the grouping of the first and second area measurements performed within three zones are depicted. The x-axis is the area, where the numbers correspond to Fig.43 The first region measurements are labeled Fn (e.g., F1), and the second region measurements are labeled Sn (e.g., S1). Thus, regions 1 to 5 are first regions F1, each in zone 110. Regions 6 to 10 are second regions S1, also in zone 110. Likewise, first region F2 is regions 16 to 20 in zone 120, and regions 11 to 15 and 21 to 25 are second regions S2 in zone 120. Finally, regions 31 to 35 are second regions, but since they have been formed by a point bonding process, they are not in the Fig.55 The point bonding portions 90 are denoted as B1 above to distinguish them in the present disclosure. The first region F3 in the region 130 is the regions 26 to 30 and 36 to 40, and the regions 41 to 44 are the second region S2 in the region 130. Fig.55The numbered regions are depicted consistently on all three graphs of FIG. 1 , but for simplicity, only regions 110 , 120 , and 130 are depicted on the thickness map.
[0277] Fig.54 The diagram shown graphically represents the magnitude of the difference in strength properties between the first and second regions in any one of the regions of the fabric subjected to the calendering point bonding step, and can be used to graphically observe the difference in strength properties of the region pairs constituting the microregions. For example, it can be seen that in region 110, the basis weight between the two regions can vary within a narrower range than the thickness or bulk density. For example, the thickness (caliper) can vary from about 325 microns in the first region to about 29 microns in the second region of region 110, or a difference of about 10X. The bulk density in region 110 can vary from about 0.08 g / cc to about 0.39 g / cc. For each of the regions shown, similar quantifiable differences can be understood.
[0278] Generally speaking, the regions of the domains can have widely varying values of basis weight, thickness, and bulk density.
[0279] Therefore, referring to Fig.54 and Fig.55 , further characterization of the beneficial structure of the fabric 10 of the present disclosure with respect to the heat-calendered point bonded portion 90 can be specifically understood. For the purpose of describing the region 130, a three-dimensional feature structure defining a micro-region including a first region and a second region as a point bonded area can be identified, and the value of the strength property can be quantified. For example, in Fig.54 , representative point-bonded micro-regions 400 in region 130 may be pairs of regions labeled regions 26 and 32 or regions 30 and 35. That is, first region 26 and second region 32 form point-bonded micro-regions 400, and first region 30 and second region 35 form point-bonded micro-regions 400.
[0280] Differences in some strength properties of point-bonded microregions can be found in Fig.55 For example, using the above two point bonded micro-regions 400, such as two point bonded micro-regions 400 of regions 26 and 32 and regions 30 and 35, it can be seen that there is a slight difference in basis weight between the first region and the second region, which basis weight is in the range of about 55 gsm to about 60 gsm, but the thickness of the same region shows a significant difference from about 430 microns to about 460 microns to about 125 microns, and the bulk density shows a significant difference from about 0.13 g / cc-0.14 g / cc to about 0.41 g / cc-0.48 g / cc. By reference Fig.55 Other differences in strength properties can be observed.
[0281] The bonding points 90 can play an important role in the overall physical structure and function of the fabric 10 of the present invention. By adding bonding points 90 to the fabric 10 (including relatively closely spaced, precisely designed three-dimensional features achieved by the forming belt of the present disclosure), the fabric 10 can be further improved to exhibit a combination of visually distinct regions, micro-regions and three-dimensional features that provide functional advantages in terms of a high performance combination of softness, strength, low fuzz and fluid handling, and provide a visually attractive aesthetic design. The bonding point features provide the highest combined performance with respect to strength, softness, fluid handling and visual aesthetics, particularly for nonwoven fabrics 10 designed with both forming and function in mind.
[0282] One benefit of the formed nonwoven webs of the present disclosure is improved softness. Softness can be measured using an Emtec Tissue Softness Analyzer provided by Emtec Paper Testing Technology, Emtec Electronic, GmbH. Table 5 below shows the softness values as TS7 measurements from the Emtec Tissue Softness Analyzer according to the Emtec test method below. For all of Examples 7 to 9 below, Fig.16 The nonwoven fabric is prepared on a belt, wherein the nonwoven web has a similar Figure 2 The appearance shown.
[0283] Table 5: TS7 Values of Formed Nonwoven Fabrics of the Present Disclosure
[0284]
[0285]
[0286] Example 7 :
[0287] A bicomponent spunbond nonwoven web was produced by spinning a 50:50 ratio of polyethylene sheath (Aspun-6850-A from Dow chemical company) and polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration as discussed above with reference to Example 2. The nonwoven fabric was spun on a forming belt having a Fig.16 The repeating pattern, which moves at a line speed of about 25 meters per minute to form a fabric 10 having an average basis weight of 25 grams per square meter, has a repeating pattern of diamond shapes, such as Figure 2 The fibers of the fabric are compacted by compacting rollers 70, 72, but not calendered, by the following Fig.56 The through-air bonding unit achieves further bonding at a temperature of 145°C.
[0288] Example 8 :
[0289] A bicomponent spunbond nonwoven fabric produced by spinning a polyethylene sheath (Aspun-6850-A from Dow chemical company) and a polypropylene core (HG475 FP from Borealis) in a 30:70 ratio in a circular fiber configuration using a twin beam spunbond process, such as Fig.56 The nonwoven fabric is spun on a forming belt having a Fig.16 The repeating pattern, as described above with respect to Figure 7 As described, it moves at a line speed of about 152 meters per minute to an average basis weight of 35 grams per square meter to form a Figure 2 The repeating pattern of the diamond shape shown. Figure 7 The difference between the formed nonwoven web prepared by the method of Example 8 and Example 8 is that Example 8 is Figure 7 The method described below Fig.56 The method is prepared by a mixing method of the method described. Specifically, the method involves Fig.56 Two spinning beams are shown, however, the final heating step is by calendaring rolls 71, 73, rather than through-air bonding. The fibers of the fabric are bonded on the first surface 12 by heated compacting rolls 70A and 72A at 110°C after the first beam 48A and heated compacting rolls 70B and 72B at 110°C after the second beam 48B, and calendared at calendaring rolls 71 and 73 at about 140°C before being wound onto a reel at winder 75.
[0290] Example 9 :
[0291] A bicomponent spunbond nonwoven fabric produced by spinning a polyethylene sheath (Aspun-6850-A from Dow chemical company) and a polypropylene core (HG475 FP from Borealis) in a 30:70 ratio in a circular fiber configuration using a twin beam spunbond process, such as Fig.56 The nonwoven fabric is spun on a forming belt having a Fig.16 The repeating pattern is moved at a line speed of about 228 meters per minute to an average basis weight of 25 grams per square meter to form a Figure 2 The fibers of the fabric are further bonded on the first surface 12 by heated compaction rollers 70A and 72A at 110°C after the first box 48A and heated compaction rollers 70B and 72B at 110°C after the second box 48B, and by air-through bonding members 76 (such as 100C, 135C and 135C) before being wound onto a reel at a winder 75. Fig.56 Heat ventilation bonding is performed at three heating zones (as shown).
[0292] Examples 7 to 9 represent formed nonwoven fabrics of the present disclosure that exhibit improved softness as indicated by the Emtec measurements. The Emtec measurements can be from about 1 dB V 2 rms to about 15dB V 2 rms, or from about 3dBV 2 rms to about 10dB V 2 rms, or about 5dB from V 2 rms to about 8dB V 2 Generally, the Emtec measurement value of the first surface or the second surface can be at most about 15dB V 2 Any integer value of rms, and any integer range between 1 and 15. In addition, generally speaking, the ratio of the measured Emtec values of the first side to the second side can be between 1 and 3, and can be any real number between 1 and 3.
[0293] Without being bound by theory, it is believed that the improvement of the softness shown by the shaped nonwoven fabric of the present invention is achieved by the method and apparatus of the present invention, which allows different strength characteristics in relatively small areas (including disclosed areas and micro-areas). For example, the ability of designing and preparing a shaped nonwoven fabric with disclosed basis weight, density or thickness difference to simultaneously deliver the combined fabric for the top sheet in the absorbent article breaks the technical contradiction previously existing between surface texture and softness. That is, the shaped nonwoven fabric of the present invention can deliver a clearly visible surface texture including an irregular pattern, and excellent softness, as indicated by the Emtec value measured. In addition, the shaped nonwoven fabric of the present invention can deliver a clearly visible surface texture with a combined physical integrity and a reduced fluffing characteristic, and excellent softness, as indicated by the Emtec value measured.
[0294] As described above, in one example, the method of preparing a formed nonwoven fabric may be about Figure 7 An improved form of the method described. Fig.56 An improvement is described. Fig.56 As shown, the method may include a belt 60 as described above, which employs more than one spinning beam in a melt spinning process. As shown, only the spinning packs 48A and 48B are schematically shown, and two beams may be used to melt the spun fibers onto the belt 60, wherein compaction operations 70A, 72A and 70B, 72B occur after each beam, respectively. Vacuum boxes 64A and 64B may also be operably associated with each spinning beam 48A and 48B, respectively.
[0295] After the fibers are spun onto belt 60, and after compaction, which includes optional thermal bonding during compaction as described above, the formed nonwoven web may be subjected to additional heating by passage through a through-air heater 76, which may have multiple chambers, such as three chambers 76A, 76B, and 76C, each with its own independently controlled temperature.
[0296] The above-mentioned embodiments 7 and 9 are manufactured on a double-box production line and Fig.56 Through-air bonding is performed in the process schematically shown. Without being bound by theory, it is shown that through-air bonding retains most of the three-dimensionality of the three-dimensional features of the formed nonwoven fabric, as indicated by the difference in TS7 values in Table 5. Alternatively, if a nonwoven fabric with less side shape is desired, it is shown that calendering bonding tends to make the TS7 value uniform, as shown by Example 8 in Table 5. Therefore, as described herein, the process parameters can be controlled to obtain a predetermined softness on each side (i.e., surface) of the formed nonwoven fabric.
[0297] In addition to the beneficial effects described in detail above, another beneficial effect of the shaped nonwoven web of the present disclosure is the ability to provide a nonwoven web with microregions, which has a hydrophobic region and an independent hydrophilic region. The hydrophilicity and / or hydrophobicity in the specific region of the microregion can be determined by using the wicking time measurement value of the wicking time test method as described herein and / or using the contact angle measurement value of the contact angle test method as described herein. As used herein, the term "hydrophilic" for the specific region of the microregion refers to that when the wicking time test method is used to test, the wicking time of the specific region is less than 10 seconds. As used herein, the term "hydrophobic" for the specific region of the microregion refers to that when the contact angle test method is used to test, the contact angle of the specific region is 90 ° or greater.
[0298] Table 6 below details the contact angle and wicking time measurements of the formed nonwovens as detailed herein. For both Examples 10 and 11 below, Fig.16 The nonwoven fabric is prepared on a belt, wherein the nonwoven web has a similar Figure 2 The appearance shown.
[0299] Table 6: Contact Angles and Wicking Times of Formed Nonwovens of the Present Disclosure
[0300]
[0301]
[0302] Example 10 :
[0303] A bicomponent spunbond nonwoven web was produced by spinning a 50:50 ratio of polyethylene sheath (Aspun-6850-A from Dow chemical company) and polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration as discussed above with reference to Example 2. The nonwoven fabric was spun on a forming belt having a Fig.16 The repeating pattern, which moves at a line speed of about 25 meters per minute to form a fabric 10 having an average basis weight of 25 grams per square meter, has a repeating pattern of diamond shapes, such as Figure 2 The fibers of the fabric are compacted by compacting rollers 70, 72, but not calendered, by the following Fig.56 The through-air bonding unit achieves further bonding at a temperature of 145°C.
[0304] The surfactant Stantex S6327 (a combination of castor oil ethoxylate and PEG diester) supplied by Pulcra Chemicals was then disposed on the back surface (i.e., the flat side surface opposite the side on which the relatively pillow-like three-dimensional features are disposed) of the nonwoven fabric by a touch coating process. The coating process was performed using a Reicofil touch roller and an Omega drying process, both of which are well known in the art. The surfactant used in the touch roller process had a surfactant concentration of 6% in water at a temperature of 40°C. The touch roller contact angle was set to 250° and the drying temperature was 80°C. The nonwoven fabric was then contacted with a touch roller operated at a speed of 13 rpm, thereby delivering 0.45% by weight of the surfactant to the nonwoven fabric (surfactant % was 10% per 1 m 2 The weight of the added surfactant is divided by 1m 2 weight of nonwoven fabric).
[0305] Embodiment 11 :
[0306] A bicomponent spunbond nonwoven web was produced by spinning a 50:50 ratio of polyethylene sheath (Aspun-6850-A from Dow chemical company) and polypropylene core (PH-835 from LyondellBasell) in a trilobal fiber configuration as discussed above with reference to Example 2. The nonwoven fabric was spun on a forming belt having a Fig.16 The repeating pattern, which moves at a line speed of about 25 meters per minute to form a fabric 10 having an average basis weight of 25 grams per square meter, has a repeating pattern of diamond shapes, such as Figure 2 The fibers of the fabric are compacted by compacting rollers 70, 72, but not calendered, by the following Fig.56 The through-air bonding unit achieves further bonding at a temperature of 145°C.
[0307] The surfactant Stantex S6327 (a combination of castor oil ethoxylate and PEG diester) supplied by Pulcra Chemicals was then placed on the front side surface of the nonwoven fabric (i.e., the side on which the three-dimensional features of the pillow-like structure are placed). The inkjet printing process was performed using a Dimatix DMP 2831 inkjet printer equipped with an ink cartridge, model DMC-11610 / PM 700-10702-01 (10 pL). The print head temperature was 40°C. The surfactant used in the inkjet printing process consisted of 75% weight / weight Stantex S 6327 and 25% weight / weight ethanol. The surfactant was printed in the second area of the microregion of the nonwoven fabric by orienting the nonwoven fabric sample so that the second area of the first row of microregions was aligned with the print head direction and printing a first series of straight lines (where the drop spacing was adjusted to 170 um). The nonwoven fabric sample was then rotated at an angle so that the second area of the second row of microregions was aligned with the print head, and the second series of straight lines were printed at 170 um. The basis weight of the fiber in the second zone is about 16.0gsm. The basis weight of the surfactant that inkjet prints to the second zone is about 0.25gsm. Therefore, the amount of the surfactant that is locally printed on the second zone is determined to be about 1.6 % by weight surfactant (0.25gsm / 16.0gsm). In general, the amount of the surfactant that is printed on the nonwoven fabric sample is determined to be about 0.2 % by weight surfactant by the ratio between the line width and the line spacing of printing.
[0308] In addition to Stantex S 6327, the use of other surfactants to make the first and / or second regions of a particular microdomain hydrophilic and / or hydrophobic (by any application method) is considered within the scope of the present disclosure. Other potential surfactants for use in the process and nonwoven fabrics detailed herein include nonionic surfactants, including esters, amides, carboxylic acids, alcohols, ethers-polyoxyethylenes, polyoxypropylenes, sorbitans, ethoxylated fatty alcohols, allylphenol polyethoxylates, lecithins, glycerides and their ethoxylates, and sugar-based surfactants (polysorbates, polysaccharides), and anionic surfactants, including sulfonates, sulfates, phosphates, alkali metal salts of fatty acids, fatty alcohol monoesters of sulfate, linear alkylbenzene sulfonates, alkyl diphenyl oxide sulfonates, lignin sulfonates, olefin sulfonates, sulfosuccinates and Sulfated ethoxylates of fatty alcohols, and cationic surfactants including amines (primary, secondary, tertiary), quaternary ammonium, pyridine, quaternary ammonium salts-QUATS, alkylated pyridinium salts, alkyl primary, secondary, tertiary amines and alkanolamides, and zwitterionic surfactants including amino acids and derivatives, amine oxides, betaines and alkyl amine oxides, and polymeric surfactants including polyamines, carboxylic acid polymers and copolymers, EO / PO block copolymers, ethylene oxide polymers and copolymers and polyvinylpyrrolidone, and silicone surfactants including dimethylsiloxane polymers with hydrophiles, as well as perfluorocarboxylates and fluorinated surfactants.
[0309] The shaped nonwoven fabrics described in detail above have microregions, and the microregions have regions with differences in strength properties (such as, for example, basis weight, density or thickness). Those identical shaped nonwoven fabrics can also have such regions of microregions simultaneously, and the regions are especially and individually hydrophobic and / or hydrophilic. Any of the shaped nonwoven fabric examples described in detail herein (for example, including regions and / or microregions with regions with differences in thickness, basis weight and / or bulk density and / or samples on the surface with various TS7 values disclosed herein) can also have regions with hydrophilic differences in microregions, as described in detail herein. Hydrophilicity can be provided by targeting one or more surfactants to the specific regions of the microregions of the shaped nonwoven fabrics. For example, the second region of the microregion can have a surfactant disposed thereon, and the first region of the same microregion can not have a surfactant disposed thereon. In addition, the first region of the microregion can have a surfactant disposed thereon, and the second region of the same microregion can not have a surfactant disposed thereon. For example, in one microregion, the first region or the second region may have a surfactant of about 0.01% to about 5.0%, about .05% to about 4.0%, about 1.0% to about 3.0%, and any concentric range within the range of about 0.01% to about 5.0%, and the other region does not have a surfactant (i.e., does not contain a surfactant). For example, in one microregion, the second region may have a surfactant of about 0.01% to about 5.0%, about .05% to about 4.0%, about 1.0% to about 3.0%, and any concentric range within the range of about 0.01% to about 5.0%, and the first region does not have a surfactant (i.e., does not contain a surfactant). Therefore, some of the formed nonwoven fabrics disclosed herein have microregions, wherein at least one of the first and second regions has a surfactant, and the ratio of the surfactant % in the first region to the surfactant % in the second region is less than 1. In addition, some of the formed nonwoven fabrics disclosed herein have microregions, wherein at least the second region of the microregion has a surfactant, and the ratio of the surfactant % in the first region to the surfactant % in the second region is less than 1.
[0310] For example, the second area of the microregion may have a specific amount of surfactant or surfactant% disposed thereon, while the first area of the same microregion may have a different amount of surfactant or surfactant% disposed thereon. For example, in one microregion, the first area may have about 0.01% to about 2.0%, about .05% to about 1.5%, about 0.1% to about 1.0%, and any concentric range of surfactants in the range of about 0.01% to about 2.0%, and the second area may have different amounts. In addition, in one microregion, the second area may have about 0.01% to about 5.0%, about .05% to about 4.0%, about 1.0% to about 3.0%, and any concentric range of surfactants in the range of about 0.01% to about 5.0%, and the first area may have different amounts. The surfactant% for a specific area of a microregion can be determined by taking the grams of surfactant per square meter disposed in the specific area and dividing it by the basis weight of the fibers of the formed nonwoven fabric included in the same area. The grams of surfactant per square meter disposed in a particular region can be determined using any method currently known in the art (e.g., gravimetric analysis, etc.). The basis weight of the fibers of the formed nonwoven fabric included in a particular region of the micro-region can also be determined using any method currently known in the art (e.g., gravimetric analysis, micro-CT, etc.). For specific micro-region examples, basis weight ranges / examples of fibers included in the first region and the second region are detailed above.
[0311] Surfactant can be arranged on the shaped nonwoven fabric by any method known in the art.Specific examples include touch coating, inkjet printing, gravure printing, offset gravure printing, flexible graphic printing of surfactant and registration printing of surfactant.Any such method can arrange surfactant on the first surface and / or second surface of the shaped nonwoven fabric.For the overall shaped nonwoven fabric (considering all the individual zones and micro-regions on the fabric), surfactant can be added to the shaped nonwoven fabric in the amount of about 0.01% to about 2.0%, about .05% to about 1.5%, about 0.1% to about 1.0%, and any concentric range in the range of about 0.01% to about 2.0%.In order to calculate the surfactant % added to the overall shaped nonwoven fabric, the grams of surfactant per square meter in the overall shaped nonwoven fabric is divided by the basis weight of the overall shaped nonwoven fabric.The grams of surfactant per square meter arranged in the overall shaped nonwoven fabric can be determined using any currently known method (e.g., gravimetric analysis, etc.) in the art. The basis weight of the overall formed nonwoven fabric may also be determined using any method currently known in the art (eg, gravimetric analysis, micro-CT, etc.).
[0312] Reference again Fig.38 and Fig.39 , which shows a portion of a pattern of a nonwoven fabric 10, a first area 110 (in Fig.38 The first region 300 of the variable width row of the MD orientation is characterized by being separated from the second region 310 of the variable width row of the MD orientation (the first region and the second region are in the micro region). The first region is also a three-dimensional feature structure 20 that defines the first region 300 and the second region 310. In one embodiment, the three-dimensional feature structure is a part of the nonwoven fabric 10 formed between or around the raised elements of the forming belt, which is the first region 300 in this specification, so that when compared with the second region 310, the resulting structure has a relatively large size, a relatively high basis weight and a low bulk density in the Z direction. In addition, the first region 300 can be hydrophobic, and the second region 310 can be hydrophilic. Targeted addition of a surfactant to the second region 310 of the micro region can cause the second region to be hydrophilic. Thus, when tested by the contact angle test method detailed herein, the first region 300 of the microdomain may have a contact angle greater than about 90°, or between about 90° and about 140°, or between about 110° and about 135°, or between about 125° and about 135°, or any concentric range contained between about 90° and about 140°. When tested by the contact angle test method detailed herein, the second region 310 of the microdomain may have a contact angle less than 90°. The first region 300 of the microdomain may have a wicking time value greater than about 10 seconds, or between about 10 seconds and 60 seconds, as measured by the wicking time test method detailed herein. The second region 310 of the microdomain may have a wicking time value less than about 10 seconds, less than about 5 seconds, or less than about 2.5 seconds, or less than about 1 second, or less than about 0.5 seconds, as measured by the wicking time test method detailed herein. The formed nonwoven fabrics contemplated herein include any of the above-detailed parameter ranges for contact angle and / or wicking time measurements for the first region and / or second region, combined with any other strength properties / property differences disclosed herein for the same or different regions in the same or different microregions on the formed nonwoven fabric.
[0313] Formed nonwoven fabrics having microregions as detailed above with regions having differences in basis weight, density or thickness, for example, while also having specific microregions that are individually hydrophobic and / or hydrophilic can provide many useful applications, such as topsheet materials, for baby care, feminine care and adult incontinence products, and for medical pads, wipes and cleaning pads, etc.
[0314] Texture is a key component of human visual perception. If the textured pattern exhibits visual clarity and uniformity, the textured patterned nonwoven can be aesthetically more pleasing to consumers. Such uniform visually clear textured patterns can be viewed as indicating the quality of the nonwoven. The uniform visually clear textured pattern on the nonwoven imparts clean, well-defined texture contrast lines or boundaries to the visual perception of the nonwoven. In general, the uniform, visually clear textured pattern on the nonwoven can be described as exhibiting high visual resolution.
[0315] Therefore, in addition to the benefits detailed above, another benefit of the shaped nonwoven web of the present disclosure is the ability to provide a textured nonwoven web with at least a first discernible area that exhibits visual clarity and uniformity. As used herein, the term "visual clarity" is defined as the property of being able to visually separate something into its component parts. In other words, visual clarity is the ability to visually distinguish two objects as separate structures rather than a single fuzzy object. In another embodiment, visual clarity requires clean, well-defined texture contrast lines or boundaries between viewing areas or regions, rather than faded, blurred or difficult to visually discern texture contrast lines.
[0316] The visually clear pattern of the textured nonwoven fabric described in detail herein can be quantified in various ways.A mode of measuring the visual clarity of the textured nonwoven pattern described in detail herein is by Haralick feature extraction and analysis (" Haralick texture analysis "). Haralick texture analysis is a general process of analyzing images to obtain higher level information (e.g., color, shape, texture). The specific Haralick texture analysis adopted herein utilizes one or more images to measure the spatial distribution of grayscale values. Then use those distributions to calculate the contrast values in the textured nonwoven fabric. Such contrast values indicate the visual clarity of the patterned nonwoven fabric.
[0317] As further described in the test method section below, the first step in the Haralick texture analysis is to calculate the gray level co-occurrence matrix (GLCM). The GLCM is a list of the frequencies at which different combinations of pixel gray levels can occur in an image. In other words, the GLCM shows the frequency of each gray level occurring at a pixel at a fixed geometric position relative to each other pixel as a function of the gray level. In the second step, the texture feature structure is calculated from the GLCM. The texture feature structure can be a scalar number, a discrete histogram, or an empirical distribution, and reflects the regular changes in the gray values in the image. The goal is to assign an unknown sample image to one of a set of known texture categories. Specific parameters obtained by the Haralick texture analysis of the formed nonwoven fiber web disclosed in the present invention include the Haralick maximum average contrast value, the Haralick maximum 90° contrast value, the Haralick maximum 0° contrast value, and the presence or absence of a periodic Haralick wave response. An additional measure of visual clarity is the grayscale contrast slope. Additional details of such parameters and their measurement methods will be further described in this article.
[0318] In addition to being visually clear, the pattern of the textured nonwoven fabric detailed herein can also be uniform in appearance. One way to measure the uniformity of the textured nonwoven pattern detailed herein is through grayscale changes. Grayscale changes can be calculated within a single article, or calculated in multiple articles, as further described herein.
[0319] Tables 7A-7D below detail Haralick analysis data for formed nonwovens as detailed herein, as well as comparative data for flat, standard, non-patterned nonwoven fabrics.
[0320] Example 12 :
[0321] A side-by-side bicomponent spunbond nonwoven web was produced by spinning a 75 / 25 blend of polypropylene (PP3155 from ExxonMobil) and polypropylene (PP3854 and PP3155 from ExxonMobil) in a 30:70 ratio in a round fiber configuration. The nonwoven was spun on a forming belt having a repeating pattern (with Fig.12 , Fig.16 , Fig.18 and Fig.19 A cured resin forming belt of the same type as shown and described herein, but having different visually discernible areas having a pattern of three-dimensional features), moving at a line speed of about 20 meters per minute to form a fabric having an average basis weight of 35 grams per square meter. Figure 7As depicted, the fibers of the fabric are compacted by compaction rolls 70, 72 heated to 140°C. The fibers of the fabric are further calendar bonded at calendar rolls 71, 73, where roll 73 is an engraved roll having raised portions 88 in the form of spikes. Roll 73 is heated to 140°C to form point bonds 90 on the second side of the fabric (similar to the description of Example 6 detailed herein). An image of the nonwoven fabric of Example 12 is shown in Fig.57 middle.
[0322] Example 13 :
[0323] A side-by-side bicomponent spunbond nonwoven web was produced by spinning a 75 / 25 mixture of polypropylene (PP3155 from ExxonMobil) and polypropylene (PP3854 and PP3155 from ExxonMobil) in a 30:70 ratio in a round fiber configuration. The nonwoven fabric was spun on a flat standard permeable laydown belt (i.e., the belt did not contain a cured resin to give the belt structure), moving at a line speed of about 20 meters / minute to form a fabric having an average basis weight of 34 grams / square meter. Figure 7 As depicted, the fibers of the fabric are compacted by compaction rollers 70, 72 heated to 90°C. The fibers of the fabric are further calendar bonded at calendar rollers 71, 73, where roller 73 is an engraved roller having raised portions 88 in the form of spikes. Roller 73 is heated to 140°C to form point bonds 90 on the second side of the fabric (similar to the description of Example 6 detailed herein). The nonwoven fabric of Example 13 is flat, without visually discernible areas having a pattern of three-dimensional features.
[0324] Embodiment 12 is the representative of the shaped nonwoven fabric of the present disclosure that shows improved visual clarity.For this embodiment and any other shaped nonwoven fabric described herein, the shaped nonwoven fabric does not contain holes.In other words, nonwoven fabric described herein does not include any part with zero basis weight.In addition, in shaped nonwoven fabric described herein, when region is limited to have intensity characteristic, for this characteristic (basis weight, thickness, volume etc.), it must have a value higher than zero.Embodiment 13 is the flat nonwoven fabric of standard, and it does not have any visually discernible area, and this visually discernible area has the pattern of three-dimensional characteristic structure.Embodiment 13 does not show the pattern with high visual clarity, and is used for comparing with the visually clear pattern shown by the new shaped nonwoven fabric described in detail herein-confirmed by embodiment 12 described in detail herein.
[0325] Table 7A-Table 7D: Formed nonwoven fabrics of the present disclosure exhibiting improved visual clarity and / or uniformity and Comparative data
[0326] Using the In-Article Gray Scale Variation Test Method detailed below, the gray scale variation values for Example 12 were measured in three different 4 inch by 4 inch scans of a visually discernible area on the formed nonwoven fabric. The three scans were located at Fig.58 1 and identified as positions 1, 2, and 3. The grayscale variation values for Example 13 were also measured using the In-Article Grayscale Variation Test Method in a single 4 inch x 4 inch scan. These measurements for Example 13 were performed twice at different locations on a flat, non-patterned nonwoven.
[0327] Table 7A: Grayscale variation measured by the in-article grayscale variation test method
[0328]
[0329]
[0330] The Haralick Maximum Contrast Test Method described in detail below was used to measure the Haralick Maximum 90° Contrast value, the Haralick Maximum 0° Contrast value, the Haralick Maximum 45° Contrast value, the Haralick Maximum 135° Contrast value, and the Haralick Maximum Average Contrast value for Example 12 in three different 4 inch by 4 inch scans of a visually discernible area on the formed nonwoven fabric. The three scans were located at Fig.58 1, 2 and 3. The Haralick Maximum Contrast Test Method was also used to measure the Haralick Maximum 90° Contrast Value, Haralick Maximum 90° Contrast Value, Haralick Maximum 45° Contrast Value, Haralick Maximum 135° Contrast Value and Haralick Maximum Average Contrast Value of Example 13 in two 4 inch x 4 inch scans. These measurements for Example 13 were performed twice at different locations on a flat non-patterned nonwoven.
[0331] For clarity, Fig.59 The graph of provides a visual depiction of 150 individual data points of Haralick 0° contrast values, 150 individual data points of Haralick 45° contrast values, 150 individual data points of Haralick 90° contrast values, 150 individual data points of Haralick 135° contrast values for Example 12 taken at Position 1, and the Haralick average contrast value generated from those 600 data points ( Fig.58 ). These same graphs were generated for Example 12, Positions 2 and 3, and Example 13, First Position and Second Position, but are not reproduced herein for the sake of brevity.
[0332] Table 7B: Haralick maximum 90° contrast, maximum 0° contrast, and maximum average contrast
[0333]
[0334] The grayscale contrast slope of Example 12 was measured at ten random locations on the nonwoven fabric using the Grayscale Contrast Slope test method detailed below. The grayscale contrast slope measured for Example 12 had a high value of 23.9 and a low value of 11.0. The average grayscale contrast slope measured for Example 12 was 16.7.
[0335] Table 7C: Grayscale Contrast Slope
[0336] Location High GL Low GL Distance(mm) Slope 1 193.7 142.4 3.0 17.1 2 181.4 150.6 2.8 11.0 3 186.2 156.3 1.6 18.7 4 195.4 146.4 3.0 16.3 5 179.0 144.5 2.0 17.3 6 174.6 141.2 1.4 23.9 7 196.1 155.5 3.2 12.7 8 184.9 155.1 2.6 11.5 9 184.6 161.1 1.4 16.8 10 184.4 145.9 1.8 21.4
[0337] Using the Grayscale Variation Test Method detailed below, the grayscale variation values of the six nonwovens as detailed in Example 12 were measured in the same visually discernible area on the formed nonwoven fabric. Images of the scanned areas of the six nonwovens are shown in Fig.60 and are identified as A, B, C, D, E, and F. The average grayscale values of the six nonwovens are identified below, and the standard deviation of those values is the grayscale variation value.
[0338] Table 7D: Grayscale variation measured by the grayscale variation test method between products
[0339] sample Average gray value A 136.7 B 137.6 C 133.3 D 134.5 E 134.7 F 133.4
[0340] The standard deviation or grayscale variation value among the six samples was 1.8.
[0341] In one way of demonstrating uniformity within a single article (i.e., defining the contrast of pixels separated by a distance X), the grayscale variation value of a visually discernible area (e.g., a first visually discernible area) can be between about 0.1 and about 10.0, or between about 0.1 and about 7.0, or between about 0.1 and about 5.0, or between about 0.1 and about 4.7, or between about 0.1 and about 4.2, or between about 0.1 and 4.1, or between about 0.1 and about 4.0, or between about 0.1 and about 3.8, or between about 1.2 and 3.8, or less than 4.5, or less than 4.2, or less than 4.0, or less than 3.8, or less than 3.0, or less than 2.0, or less than 1.0. In general, the grayscale variation measurement value of a visually discernible area (in a single article) can be any value up to about 10, and any range of values between 0.1 and 10. This grayscale variation within a single article is measured according to the grayscale variation within article test method detailed herein.
[0342] In a first way of demonstrating visual clarity within a single article, the Haralick maximum average contrast value of a visually discernible area (e.g., a first visually discernible area) may be between about 80 and about 750, or between about 90 and about 600, or between about 100 and about 500, or between about 200 and about 500, or between about 300 and about 450, or greater than about 80, or greater than about 90, or greater than about 100, or greater than about 150, or greater than about 200, or greater than about 250, or greater than 300. Generally speaking, the Haralick maximum average contrast value within a visually discernible area may be any integer range between 80 and 750.
[0343] In a second way of demonstrating this visual clarity within a single article, the Haralick maximum 90° contrast value of a visually discernible area (e.g., a first visually discernible area) may be between about 80 and about 750, or between about 90 and about 600, or between about 100 to about 500, or between about 200 and about 500, or between about 300 to about 450, or greater than about 80, or greater than about 90, or greater than about 100, or greater than about 150, or greater than about 200, or greater than about 250, or greater than about 300, or greater than 315. Generally speaking, the Haralick maximum 90° contrast value within a visually discernible area may be any integer range between 80 and 750.
[0344] In a third way of demonstrating this visual clarity within a single article, the Haralick Maximum 0° Contrast value of a visually discernible area (e.g., a first visually discernible area) can be between about 80 and about 750, or between about 90 and about 600, or between about 100 and about 500, or between about 200 and about 500, or between about 300 and about 450, or greater than about 80, or greater than about 90, or greater than about 100, or greater than about 150, or greater than about 200, or greater than about 250, or greater than about 300, or greater than about 350, or greater than 381. Generally speaking, the Haralick Maximum 0° Contrast value within a visually discernible area can be any integer range between 80 and 750.
[0345] In a fourth way of demonstrating the visual clarity within a single article, the grayscale contrast slope of the first visually discernible area (e.g., the first visually discernible area) may be between about 5.0 and about 35.0, or between about 10.0 and about 30.0, or between about 11.0 and about 25.0, or between about 11.0 and about 23.9, or greater than about 11.0, or less than 23.9. In general, the grayscale contrast slope within a single article may be any range of values between 10.0 and 30.0.
[0346] In a fifth way of demonstrating such visual clarity within a single article, a visually discernible area (e.g., a first visually discernible area) may have a periodic Haralick wave response, as determined according to the Haralick maximum contrast method defined herein. For clarity, a wave response may be defined as periodic if at least one peak and at least one trough are observed in the Haralick response. As further defined in this method, a periodic response applies only to Haralick maximum 90° or 0° contrast values.
[0347] In one way of demonstrating high uniformity of consistency across multiple articles, such uniformity can be demonstrated by a grayscale variation value between about 0.1 to about 10.0, or between about 0.1 to about 7.0, or between about 0.1 to about 5.0, or between about 0.1 to about 4.7, or between about 0.1 to about 4.2, or between about 0.1 and 4.1, or between about 0.1 and about 4.0, or between about 0.1 and about 3.8, or between about 0.1 and about 1.2, or less than 4.5, or less than 4.2, or less than 4.0, or less than 3.8, or less than 3.0, or less than 2.0, or less than 1.2, or less than 1.0. In general, the grayscale variation measurement value of a visually discernible area (e.g., a first visually discernible area in a plurality of articles) can be any value up to about 10, and any range of values between 0.1 and 10. The grayscale variation between multiple products is measured according to the grayscale variation test method between products detailed in this article.
[0348] Any of the individual Haralick parameters for confirming visual clarity in the formed nonwoven fabrics described in detail above can be combined with one or more additional modes (additional Haralick parameters or other parameters) for confirming visual clarity in the formed nonwoven fabrics. In addition, the formed nonwoven fabrics described in detail above have microregions with regions where strength properties (such as, for example, basis weight, density, or thickness) differ. Nonwoven fabrics of the same shape can also have visually clear patterns simultaneously, with any and / or all of the Haralick analysis values described in detail herein. Any of the examples of formed nonwoven fabrics detailed herein (e.g., samples including regions and / or microregions with areas having different thickness, basis weight and / or bulk density, hydrophilic area and / or hydrophobic area, and / or surfaces with various TS7 values disclosed herein) may also have a visually distinct pattern that can be quantified by grayscale changes, Haralick maximum average contrast value, Haralick maximum 90° contrast value, Haralick maximum 0° contrast value, grayscale contrast slope, and the presence or absence of a periodic Haralick wave response. In addition, a package of any of the examples of formed nonwoven fabrics detailed herein (e.g., samples including regions and / or microregions with areas having different thickness, basis weight and / or bulk density, and / or surfaces with various TS7 values disclosed herein) may include a nonwoven fabric that also has a visually distinct pattern that can be quantified by grayscale changes.
[0349] Formed nonwoven fabrics having microregions as detailed above with areas of difference, for example, in basis weight, density or thickness, while also having visually distinct patterns with any and / or all of the Haralick analysis values detailed herein can provide many useful applications, such as topsheet materials, for baby care, feminine care and adult incontinence products, and for medical pads, wipes and cleaning pads, etc.
[0350] In addition, in order to utilize the methods as detailed herein to produce such formed nonwoven fabrics having high visual resolution patterns, the inventors have unexpectedly discovered that the forming belt must have a selected combination of knuckle area percentage (hereinafter referred to as "%KA") and / or air permeability and / or overload. Without wishing to be bound by theory, the inventors have discovered that formed nonwoven fabrics of the present invention having high visual resolution patterns can be achieved using only forming belts having selected %KA and / or air permeability and / or overload because these belt designs can facilitate deeper fiber migration into the open areas of the forming belt, greater filament count in the open areas relative to the knuckle or resin areas of the belt, more cooling-induced fiber setting during deposition in the open areas of the belt, less fiber consolidation losses at the resin wall areas of the belt, maintenance of fiber wall steepness and structure during post-production consolidation / bonding, maintenance of fiber wall steepness and structure in intermediate rolls for feeding to the production line, and fiber wall steepness and structure in the article all individually or simultaneously contribute to establishing steep transition slopes of filaments at zone boundaries of the nonwoven and unexpectedly achieving high visual resolution textures even under compression packaging and / or other factors.
[0351] In the context of the entire forming belt, %KA can be calculated by dividing the area of the forming belt containing the knuckle (i.e., the sum of the areas of the resin forming the raised portion) by the total area of the entire forming belt. In a defined segment on the forming belt, %KA can be calculated by dividing the area of the defined segment containing the knuckle (i.e., the sum of the areas of the resin forming the raised portion) by the total area of the defined segment. The method of measuring the air permeability of the forming belt defined herein is detailed in the Methods section below.
[0352] %KA, air permeability and overload may be measured in any defined segment on a forming belt as defined herein, including: 1) a defined segment comprising a portion or the entire repeating pattern of a forming belt (e.g., Fig.12 , Fig.16 or Fig.18 The entire segment of the forming belt shown, or Fig.12 , Fig.16 or Fig.18 any portion of the forming belt shown); 2) including a defined segment of a discrete belt pattern on the forming belt (e.g., Fig.19 3) including any discernible area defined segment on the forming belt (e.g., Fig.19 any defined segment of the discrete band pattern 61 comprising visually discernible areas in the forming band); and 4) a defined segment comprising any combination of discernible areas on the forming band (e.g., Fig.19 any defined segment of a discrete band pattern 61 comprising a combination of one or more visually discernible areas).
[0353] For the forming belt defined herein that delivers high visual resolution patterned nonwoven fabric, %KA can be between about 2% and about 35%, or between about 5% and about 30%, or between about 8% and about 25%, or between about 10% and about 25%. Air permeability can be between about 400cfm and about 1000cfm, or between about 400cfm and about 800cfm, or between about 500cfm and about 750cfm, or between about 650cfm and about 700cfm. As defined herein, overload OB can be between about 0.015 inch and about 0.060 inch, or between about 0.020 inch and about 0.050 inch, or between about 0.025 inch and about 0.045 inch, or between about 0.030 inch and about 0.040 inch, or between about 0.030 inch and about 0.035 inch.
[0354] Table 8A and plots the data from Table 8A. Fig.61 , shows the desired combined range of %KA and air permeability for a forming belt for making a formed nonwoven fabric having a high visual resolution pattern. When the forming belt has a %KA between about 2% and about 35% and an air permeability between about 400 cfm and about 1000 cfm, the belt can produce a formed nonwoven fabric having a high visual resolution pattern as described herein (i.e., a nonwoven fabric exhibiting high visual clarity as quantified by grayscale variation, Haralick maximum average contrast value, Haralick maximum 90° contrast value, Haralick maximum 0° contrast value, grayscale contrast slope, and the presence or absence of a periodic Haralick wave response). Such forming belts are identified as having high visual resolution. In Fig.61 In the , boxes are drawn around the high visual resolution forming belt data points to indicate the range of %KA and air permeability parameters displayed by such belts. When the forming belt has a %KA above 35%, or an air permeability below about 350 cfm, or a combination of a %KA above 35% and an air permeability below 400 cfm, the belt does not produce a formed nonwoven fabric having a high visual resolution pattern as described herein. Such forming belts are identified as low visual resolution. Data for some low visual resolution belt examples are detailed in Table 8B below, and are also described in Table 8B. Fig.61 Draw on.
[0355] Table 8A: %KA and Air Permeability of High Visual Resolution Formed Belts
[0356]
[0357]
[0358] Table 8B: %KA and Air Permeability of Low Visual Resolution Formed Belts
[0359] %KA Air permeability 36.0 336 41.0 305 60.0 117
[0360] In some high visual resolution forming belts of interest, the belt may have a %KA between about 8% to about 25% and an air permeability between about 500cfm to about 850cfm. In other high visual resolution forming belts of interest, the belt may have a %KA between about 10% to about 25% and an air permeability between about 650cfm to about 700cfm. In other high visual resolution forming belts of interest, the belt may have a %KA between about 8% to about 25% and an air permeability between about 500cfm to about 850cfm, and an overload between about 0.015 inches and about 0.060 inches. In other high visual resolution forming belts of interest, the belt may have a %KA between about 10% to about 25% and an air permeability between about 650cfm to about 700cfm, and an overload between about 0.025 inches and about 0.045 inches.
[0361] Any of the individual Haralick parameters detailed above to demonstrate visual clarity of the formed nonwoven fabric can be combined with one or more parameters associated with the forming belt used to make the formed nonwoven fabric (% KA and / or air permeability and / or overload). In addition, the formed nonwoven fabric produced on the forming belt detailed above has micro-regions having areas with differences in strength properties such as basis weight, density or thickness; and can also simultaneously have a visually clear pattern having any and / or all of the Haralick analysis values detailed herein. Any of the examples of formed nonwoven fabrics detailed herein (e.g., samples including regions and / or micro-regions with different thickness, basis weight and / or bulk density, hydrophilic area and / or hydrophobic area, and / or surfaces with various TS7 values disclosed herein) may also simultaneously have a visually distinct pattern that can be quantified by grayscale changes, Haralick maximum average contrast value, Haralick maximum 90° contrast value, Haralick maximum 0° contrast value, grayscale contrast slope, and the presence or absence of a periodic Haralick wave response, and / or be manufactured on a forming belt as described herein (% KA and / or air permeability and / or overload). In addition, a package of any of the examples of formed nonwoven fabrics detailed herein (e.g., samples including regions and / or micro-regions with different thickness, basis weight and / or bulk density, and / or surfaces with various TS7 values disclosed herein) may include a nonwoven fabric that also simultaneously has a visually distinct pattern that can be quantified by grayscale changes.
[0362] Test Method :
[0363] Compression aging test method
[0364] Initial thickness measurement:
[0365] • Cut five 3 inch by 3 inch samples from each nonwoven fabric to be measured.
[0366] • Number each sample from 1 to 5.
[0367] • Measure thickness according to standard procedure using a Thwing-Albert thickness gauge at 0.5 kPa with a "standard" 65 mm foot.
[0368] • Report the initial thickness of each of the five samples.
[0369] Report the average thickness of the five samples.
[0370] Aged Compression Method and Aged Thickness Measurement
[0371] • Stack five samples in an alternating pattern with each sample separated by a paper towel, the stack starting and ending with "Sample Number" 1 and 5 respectively.
[0372] • Place the alternating stack of samples in an aluminum sample holder and place an appropriate weight on top of the samples (4 KPa, 14 KPa or 35 KPa).
[0373] • Place the stacked sample with weights in an oven at 40°C for 15 hours.
[0374] • After 15 hours the weight was removed, the samples separated and the thickness of each sample measured at 0.5 kPa with a "standard" 65 mm foot Thwing-Albert thickness gauge according to standard procedures.
[0375] • Report the aged thickness value for each of the five samples.
[0376] Report the average aged thickness of the five samples.
[0377] Analytical Report:
[0378] Reports average initial thickness and aged thickness by location number
[0379] Report thickness recovery index:
[0380] (Average aging thickness / average initial thickness)*100
[0381] Local Basis Weight Test Method
[0382] The "local basis weight" of a nonwoven fabric can be determined by several available techniques, but one simple representative technique involves a 3.0 cm 2 A die of 100% area is used to cut a web sample piece from the selected area (out of the total area of the nonwoven fabric). The sample piece is then weighed and divided by its area to obtain the local basis weight of the nonwoven fabric in grams per square meter. For each selected area, the results are reported as the average of 2 samples.
[0383] Villus content test method
[0384] The fuzz content test is used to determine the amount of fibers removed from a nonwoven material under abrasive forces (ie, the fuzz content).
[0385] The fuzz content test utilizes the following materials:
[0386] • Sutherland Ink Rub Tester with 2 lb weight, purchased from Danilee Co, San Antonio, TX.
[0387] Aluminum Oxide Abrasive Cloth 320 Grit Abrasive Cloth Roll, by Plymouth Coatings, (617)
[0388] This material can also be ordered through McMaster Carr, Part No. 468.7A51, (330) 995-5500.
[0389] Double-sided tape, 3M #409, purchased from Netherland Rubber Company, (513)
[0390] 733-1085.
[0391] Fiber removal tape, 3M #3187, available from Netherland Rubber Company, (513)
[0392] 733-1085.
[0393] Analytical balance (+ / -0.0001g)
[0394] Paper cutter
[0395] 2200g weight (metal) 170mm×63mm.
[0396] • Thick Release Liner Paperboard—0.0445 inches (1.13 mm) thickness.
[0397] Material preparation
[0398] Measure and cut the aluminum oxide emery cloth into 7.5 inches (19.0mm) lengths. Measure and cut the 3M#3187 tape piece into 6.5 inches (16.5cm) lengths, two strips per sample. Fold less than about 0.25 inches (0.6cm) at each end of the 3M#3187 tape to facilitate handling. Place the 3M#3187 tape on thick release paper for subsequent use.
[0399] Sample preparation
[0400] Before any one of the processing or test materials, wash hands with soap and water to remove excess oil from hands. Optionally, latex gloves can be worn. The sample of the nonwoven fabric to be tested is cut to at least 11cm MD and 4cm CD size. Lay the sample of the nonwoven fabric to be tested flat, and make the side to be tested face down. Cut a piece of 3M#409 double-sided tape from the roll, the length is at least 11cm. Remove the backing, and apply the double-sided tape facing the backing to the longitudinal sample nonwoven fabric along the longitudinal direction (MD). Replace the backing on the exposed strip. Use a paper cutter to cut the test sample in the tape bonding area 11cm MD and 4cm CD.
[0401] Test procedures
[0402] 1. Install the aluminum oxide emery cloth section on the Sutherland Ink Rub Tester using a 2 lb weight. Place a second aluminum oxide emery cloth section on top of the thick release liner cardboard (use a new piece for each test). Place both on top of the 2 lb weight. The sides will fold down into the clamps - make sure the aluminum oxide emery cloth and thick release liner cardboard are flat.
[0403] 2. Mount the sample onto the Sutherland Ink Rub Tester platform, centered on the metal plate. Place a 2200 g weight on top of the sample for 20 seconds.
[0404] 3. Attach the metal plate and 2 lb weight to the Sutherland Ink Rub Tester.
[0405] 4. Turn on the Friction Tester. If the table light is not on, press the Reset button. Press the table button to set the Friction Cycle to 20 cycles. Use the Speed button to select Speed 1, Slow (light not on). Press Start.
[0406] 5. When the friction tester is turned off, carefully remove the aluminum oxide cloth / weight, making sure not to lose any loose microfibers (fuzz). In some cases, the microfibers will adhere to both the aluminum oxide cloth and the surface of the sample nonwoven. Place the weight upside down on the bench.
[0407] 6. Weigh the fiber removal tape with the release paper attached. Secure the fiber removal tape by its folded ends, remove the release paper and set aside. Gently place the strip onto an aluminum oxide emery cloth to remove any lint. Remove the fiber removal tape and place it back onto the release paper. Weigh the fiber removal tape and record.
[0408] 7. Another piece of pre-weighed fiber removal tape is secured by its folded end. The fiber removal tape is gently placed onto the surface of the rubbed nonwoven sample. A flat metal plate is placed on top of the fiber removal tape.
[0409] 8. Place a 2200 g weight on top of the metal plate for 20 seconds. Remove the fiber removal tape. The pre-weighed fiber removal tape is secured by its folded ends to avoid fingerprints. Place the pre-weighed fiber removal tape back onto the release paper. Weigh the fiber removal tape and record.
[0410] 9. The fuzz weight is the sum of the weight gains of the two fiber removal belts.
[0411] 10. Fluff weight is reported as the average of 10 measurements.
[0412] calculate
[0413] For a given sample, add the weight of fuzz in grams collected from the aluminum oxide cloth to the weight of fuzz in grams collected from the abraded sample nonwoven. Multiply the combined weight in grams by 1000 to convert to milligrams (mg). To convert this measurement from absolute weight loss to weight loss per unit area, divide the total weight of fuzz by the area of the abraded area.
[0414] Air permeability test method
[0415] The "Air Permeability Test" is used to determine the level of air flow through the forming belt in cubic feet per minute (cfm). The "Air Permeability Test" is performed on a Textest Instruments, model FX3360 Portair Air Permeability Tester, available from Textest AG, Sonnenbergstrasse 72, CH 8603 Schwerzenbach, Switzerland. The unit utilizes a 20.7 mm orifice plate for a permeability range between 300 cfm and 1000 cfm. If the permeability is below 300 cfm, the orifice plate needs to be reduced; if above 1000 cfm, the orifice plate needs to be increased. The air permeability can be measured in a localized area of the forming belt to determine the difference in air permeability across the forming belt.
[0416] Test procedures
[0417] 1. Turn on the power of the FX3360 instrument.
[0418] 2. Select a scheduled mode with the following settings:
[0419] a.Material: “Standard”
[0420] b. Measurement properties: air permeability (AP)
[0421] c. Test pressure: 125Pa (Pascal)
[0422] dT factor: 1.00
[0423] e. Test point pitch: 0.8 inches.
[0424] 3. Position a 20.7 mm orifice plate on the top side of the forming belt (the side with the 3D protrusions) at the location of interest.
[0425] 4. Select "Single Point Measurement" on the test unit's touch screen.
[0426] 5. If necessary, reset the sensor before measuring.
[0427] 6. Once reset, select the "Start" button to begin measuring.
[0428] 7. Wait until the measurement stabilizes and record the cfm reading on the screen.
[0429] 8. Select the Start button again to stop measuring.
[0430] Test method for stacking height in bags
[0431] The in-bag stack height of the absorbent article package is determined as follows:
[0432] equipment
[0433] A thickness tester with a flat rigid horizontal slide is used. The thickness tester is configured so that the horizontal slide is free to move in the vertical direction, wherein the horizontal slide is always maintained in a horizontal orientation directly above a flat rigid horizontal substrate. The thickness tester includes a device suitable for measuring the gap between the horizontal slide and the horizontal substrate, accurate to within ±0.5 mm. The horizontal slide and the horizontal substrate are larger than the surface of the absorbent article package that contacts each plate, i.e., each plate extends beyond the contact surface of the absorbent article package in all directions. The horizontal slide applies a downward force of 850 g ± 1 gram-force (8.34 N) to the absorbent article package, which can be achieved by placing a suitable weight on the center of the top surface of the horizontal slide that does not contact the package, so that the total mass of the slide plus the added weight is 850 g ± 1 gram.
[0434] Test procedures
[0435] Prior to measurement, the absorbent article packages were equilibrated at 23°C ± 2°C and 50% ± 5% relative humidity.
[0436] The horizontal slide is raised and the absorbent article package is placed centrally underneath the horizontal slide in such a manner that the absorbent articles in the package are in a horizontal orientation (see Fig. 27 ). Any handles or other packaging features on the surface of the package that touches either of the plates are folded flat against the surface of the package to minimize their effect on the measurement. Slowly lower the horizontal slide until it contacts the top surface of the package, and then release. Ten seconds after releasing the horizontal slide, measure the gap between the horizontal plates to within ±0.5 mm. Measure five identical packages (packages of the same size and the same number of absorbent articles) and report the arithmetic mean as the package width. Calculate and report "stack height in bag" = (package width / number of absorbent articles per stack) × 10, accurate to within ±0.5 mm.
[0437] Micro-CT intensity characteristics measurement test method
[0438] The micro-CT intensity characterization method measures the basis weight, thickness and volume density values within a visually discernible area of a substrate sample. It is based on the analysis of a 3D x-ray sample image obtained on a micro-CT instrument (a suitable instrument is a Scanco μCT 50 purchased from Scanco Medical AG, Switzerland, or an equivalent). The micro-CT instrument is a cone beam microphotograph with a shielded cabinet. A maintenance-free x-ray tube is used as a light source with an adjustable diameter focus. The x-ray beam passes through the sample, where some of the x-rays are attenuated by the sample. The degree of attenuation is related to the mass of the material through which the x-rays must pass. The transmitted x-rays continue to strike a digital detector array and produce a 2D projection image of the sample. A 3D image of the sample is generated by collecting several individual projection images of the sample as the sample rotates, and then reconstructing them into a single 3D image. The instrument is connected to a computer running software to control image acquisition and save raw data. The 3D image is then analyzed using image analysis software (a suitable image analysis software is MATLAB available from The Mathworks, Inc., Natick, MA, or equivalent) to measure basis weight, thickness, and bulk density strength properties of areas within the sample.
[0439] Sample preparation :
[0440] To obtain samples for measurement, a single layer of dry substrate material was laid flat and a circular piece having a diameter of 30 mm was punched out.
[0441] If the substrate material is a layer of an absorbent article, such as a topsheet, backsheet nonwoven, acquisition layer, distribution layer, or other component layer; the absorbent article is secured to a rigid flat surface with tape in a flat configuration. Carefully separate the separate substrate layer from the absorbent article. If necessary, the substrate layer may be removed from the additional underlying layers using a surgical scalpel and / or a cryogenic spray (such as Cyto-Freeze, Control Company, Houston TX) to avoid any longitudinal and lateral extension of the material. Once the substrate layer has been removed from the article, begin die cutting the sample as described above.
[0442] If the substrate material is in the form of wet wipes, open a new package of wet wipes and remove the entire stack from the package. Remove a wipe from the middle of the stack, lay it flat and allow it to dry completely before die cutting a sample for analysis.
[0443] The sample may be cut from any position that includes a visually distinguishable region to be analyzed. Within a region, the region to be analyzed is the region associated with the three-dimensional features that define the microregion. The microregion includes at least two visually distinguishable regions. Regions, three-dimensional features, or microregions may be visually distinguishable due to changes in texture, height, or thickness. Regions within different samples obtained from the same substrate material may be analyzed and compared to each other. When selecting the sampling location, care should be taken to avoid folds, wrinkles, or tears.
[0444] Image acquisition :
[0445] The micro-CT instrument was set and calibrated according to the manufacturer's instructions. The sample was placed in an appropriate holder between two low-density material rings with an inner diameter of 25 mm. This will allow the central portion of the sample to be placed horizontally and scanned without any other material directly adjacent to its upper and lower surfaces. Measurements should be made in this area. The 3D image field of view is about 35 mm on each side of the xy plane, with a resolution of about 5000 by 5000 pixels, and a sufficient number of 7-micron thick slices that completely include the z direction of the sample are collected. The reconstructed 3D image resolution contains 7 micron isotropic voxels. Images were collected with a light source of 45 kVp and 133 μA without an additional low-energy filter. These current and voltage settings can be optimized to produce the maximum contrast in the projection data, where enough x-rays penetrate the sample, but once optimized, all substantially similar samples remain constant. A total of 1500 projection images were obtained, with an integration time of 1000 ms and 3 averages. The projection images were reconstructed into 3D images and saved in 16-bit RAW format to retain the complete detector output signal for analysis.
[0446] Image Processing :
[0447] Load the 3D image into the image analysis software. Threshold the 3D image to a value that separates and removes background signals due to air, but maintains signals from sample fibers within the substrate.
[0448] Three 2D intensity characteristic images are generated from the thresholded 3D image. The first is the basis weight image. To generate this image, the value of each voxel in the xy plane slice is added to all its corresponding voxel values in the other z direction slices that include the signal from the sample. This creates a 2D image where each pixel now has a value equal to the cumulative signal of the entire sample.
[0449] In order to convert the raw data values in the basis weight image into real numbers, a basis weight calibration curve is generated. A substrate having a substantially similar composition to the sample being analyzed and having a uniform basis weight is obtained. At least ten replicates of the calibration curve substrate are obtained according to the above-mentioned procedure. The basis weight is accurately measured in the following manner: the mass of each of the single-layer calibration samples is taken to nearly 0.0001g and divided by the sample area and converted to grams per square meter (gsm), and the average value is calculated, accurate to 0.01gsm. According to the above-mentioned procedure, a micro-CT image of a single layer of the calibration sample substrate is collected. According to the above-mentioned procedure, the micro-CT image is processed, and a basis weight image including the raw data value is generated. The actual basis weight value of the sample is the average basis weight value measured on the calibration sample. Then, two layers of calibration substrate samples are stacked on top of each other, and micro-CT images of the two layers of calibration substrates are collected. The basis weight raw data images of the two layers are generated together, and their actual basis weight value is equal to twice the average basis weight value measured on the calibration sample. Repeat this step of stacking a single layer of calibration substrate, thereby acquiring microCT images of all layers, generating raw data basis weight images of all layers, whose actual basis weight values are equal to the number of layers multiplied by the average basis weight value measured on the calibration sample. Obtain a total of at least four different basis weight calibration images. The basis weight values of the calibration samples must include values above and below the basis weight values of the initial samples to be analyzed to ensure accurate calibration. Generate a calibration curve by performing a linear regression on the raw data with the actual basis weight values of the four calibration samples. If the entire calibration process is not repeated, this linear regression must have an R2 value of at least 0.95. This calibration curve is now used to convert the raw data values to actual basis weight.
[0450] The second intensity characteristic 2D image is the thickness image. To generate this image, the upper and lower surfaces of the sample are identified, and the distance between these surfaces is calculated to derive the sample thickness. The upper surface of the sample is identified by starting with the uppermost slice in the z direction and evaluating each slice through the sample to locate the z-direction voxels of all pixel positions in the xy plane where the sample signal is first detected. The lower surface of the sample is identified according to the same procedure, except that the z-direction voxels located are all positions in the xy plane where the sample signal is last detected. Once the upper and lower surfaces are identified, they are smoothed with a 15x15 median filter to remove signals from stray fibers. A 2D thickness image is then generated by counting the number of voxels that exist between the upper and lower surfaces for each of the pixel positions in the xy plane. This raw thickness value is then converted to an actual distance (in microns) by multiplying the voxel count by the 7μm slice thickness resolution.
[0451] The third intensity characteristic 2D image is the volume density image. To generate this image, each xy plane pixel value in the basis weight image (in gsm) is divided by the corresponding pixel in the thickness image, in microns. The units of the volume density image are grams per cubic centimeter (g / cc).
[0452] Micro-CT Basis Weight, Thickness and Volume Density Intensity Properties :
[0453] The analysis begins by identifying the region. The region to be analyzed is the region associated with the three-dimensional feature structure that defines the microregion. The microregion includes at least two visually distinguishable regions. The region, three-dimensional feature structure or microregion can be visually distinguishable due to changes in texture, height or thickness. Next, the boundaries of the region to be analyzed are identified. The boundaries of the region are identified by visually distinguishing the difference in intensity characteristics when compared to other regions within the sample. For example, the region boundaries can be identified based on visually distinguishing the thickness difference when compared to another region in the sample. Any of the intensity characteristics can be used to distinguish the region boundaries of the physical sample itself in any of the microCT intensity characteristic images. Once the boundaries of the region are identified, an elliptical or circular "region of interest" (ROI) is drawn inside the region. The ROI should have a size of at least 0.1mm 2 The area of the ROI is selected for measurement with an intensity characteristic value representative of the identified area. The average basis weight, thickness, and bulk density within the ROI are calculated from each of the three intensity characteristic images. These values are recorded as the basis weight of the area to the nearest 0.01 gsm, the thickness to the nearest 0.1 micron, and the bulk density to the nearest 0.0001 g / cc.
[0454] Emtec Test Methods
[0455] TS7 and TS750 values were measured using an EMTEC Tissue Softness Analyzer ("Emtec TSA") (Emtec Electronic GmbH, Leipzig, Germany) connected to a computer running Emtec TSA software (version 3.19 or equivalent). According to Emtec, the TS7 value is related to the actual material softness, while the TS750 value is related to the felt smoothness / roughness of the material. The Emtec TSA includes a rotor with a vertical blade that rotates on the test sample at a defined and calibrated rotational speed (set by the manufacturer) and a contact force of 100 mN. The contact between the vertical blade and the test piece produces vibrations that produce sounds that are recorded by a microphone within the instrument. The recorded sound files are then analyzed by the Emtec TSA software. Sample preparation, instrument operation, and test procedures are performed according to the instrument manufacturer's instructions.
[0456] Sample preparation
[0457] Test samples are prepared by cutting square or circular samples from finished products. In any of these sizes, the test samples are cut to a length and width (or diameter if circular) of not less than about 90 mm and not more than about 120 mm to ensure that the sample can be properly clamped into the TSA instrument. The test samples are selected to avoid perforations, creases or wrinkles in the test area. Eight substantially similar replicates are prepared for testing. All samples are balanced for at least 2 hours under TAPPI standard temperature and relative humidity conditions (23°C ± 2°C and 50% ± 2%) before performing the TSA test, which is also performed under TAPPI conditions.
[0458] Test procedures
[0459] The instrument was calibrated using a 1-point calibration method with Emtec reference standards ("ref. 2 sample") according to the manufacturer's instructions. If these reference samples were no longer available, appropriate reference samples provided by the manufacturer were used. The instrument was calibrated according to the manufacturer's recommendations and instructions so that the results were comparable to those obtained when using a 1-point calibration method with Emtec reference standards ("ref. 2 sample").
[0460] Provide eight replicate samples of the fabric for testing. Mount the test sample into the instrument with the surface facing up and perform the test according to the manufacturer's instructions. Upon completion, the software will display the values for TS7 and TS750. Record each of these values to the nearest 0.01 dB V 2 rms. The test sample is then removed from the instrument and discarded. The test is performed on the same surface of four replicates, and then on another surface of the other four replicates. The first test surface can be either the first surface 12 or the second surface 14 of the formed nonwoven fabric as disclosed herein.
[0461] Average the TS7 and TS750 values from the four test results for the first test surface (using a simple numerical average); also average the TS7 and TS750 values from the four test results for the second test surface. Report the average of the individual TS7 and TS750 values for the first and second test surfaces on a particular test sample to the nearest 0.01 dB V 2 Additionally, the TS7 ratio of the first test surface to the second test surface was calculated by dividing the average TS7 of the first test surface by the average TS7 of the second test surface.
[0462] Contact Angle and Wicking Time Test Methods
[0463] Contact angle and wicking time measurements are determined using a static drop experiment. A specified volume of type II reagent distilled water (as defined in ASTM D1193) is applied to the surface of the test sample using an automated liquid delivery system. A high-speed camera captures time-stamped images of the droplets within a 60-second time period at a rate of 900 frames per second. The contact angle between the droplet and the test sample surface of each captured image is determined by image analysis software. Wicking time is determined as the time required for the contact angle of the droplet absorbed into the test sample to decrease to a contact angle of <10 °. All measurements are performed at a constant temperature (23 ° C ± 2 ° C) and relative humidity (50% ± 2%).
[0464] An automatic contact angle tester is required to perform this test. The system consists of a light source, a video camera, a horizontal sample stage, a liquid delivery system with a pump and a micro-syringe, and a computer equipped with software suitable for video image capture, image analysis, and reporting of contact angle data. A suitable instrument is an optical contact angle measuring system (Optical Contact AngleMeasuring System) OCA 20 (DataPhysics Instruments, Filderstadt, Germany) or an equivalent system. The system must be able to deliver 8.2 microliter droplets and can capture images at a rate of 900 frames / second. Unless otherwise explicitly stated in this test procedure, the system is calibrated and operated according to the manufacturer's instructions.
[0465] To obtain the test sample for measurement, a single layer of dry substrate material is laid flat and rectangular test samples are cut, which are 15 mm in width and about 70 mm in length. The width of the sample can be reduced as needed to ensure that the test area of interest is not obscured by surrounding features during testing. For narrower sample strips, care must be taken that the droplets do not reach the edges of the test sample during testing, otherwise the test must be repeated. Prior to testing, the samples are pre-conditioned at about 23°C ± 2°C and 50% ± 2% relative humidity for 2 hours.
[0466] Sample preparation
[0467] The test sample may be cut from any position that includes a visually discernible region to be analyzed. Within a region, the region to be analyzed is the region associated with the three-dimensional features that define the microregion. The microregion includes at least two visually discernible regions. A region, three-dimensional feature, or microregion may be visually discernible due to a change in texture, height, or thickness. Regions within different test samples obtained from the same substrate material may be analyzed and compared to one another. When selecting the sampling location, care should be taken to avoid folds, wrinkles, or tears.
[0468] If the substrate material is a layer of an absorbent article, such as a topsheet or backsheet nonwoven material, a collection layer, a distribution layer, or other component layer; the absorbent article is secured to a rigid flat surface with tape in a flat configuration. Carefully separate the separate substrate layer from the absorbent article. If necessary, the substrate layer may be removed from the attached underlying layers using a surgical scalpel and / or a cryogenic spray (such as Cyto-Freeze, Control Company, Houston TX) to avoid any longitudinal and lateral extension of the material. Once the substrate layer has been removed from the article, begin cutting the test sample. If the substrate material is in the form of a wet wipe, open a new wet wipe package and remove the entire stack from the package. Remove a wipe from the middle of the stack, lay it flat and allow it to dry completely before cutting the sample for analysis.
[0469] Test procedures
[0470] The test sample is positioned on a horizontal sample stage, wherein the test area is in the camera field of view below the pin of the liquid delivery system, and the test side is facing up. The test sample is fixed in this way so that it is flat and strain-free, and any interaction between the droplet and the surface below is avoided to prevent excessive capillary forces. A 27-gauge blunt-end stainless steel needle (ID0.23mm, OD 0.41mm) is positioned above the test sample, wherein at least 2mm of the needle end is in the camera field of view. The sample stage is adjusted to achieve a distance of about 3mm between the needle end and the test sample surface. Droplets of 8.2 microliters of reagent distilled water are formed at a rate of 1 microliter / second, and are allowed to fall freely onto the surface of the test sample. Video image capture is started before the droplet contacts the surface of the test sample, and a series of continuous images are collected for 60 seconds after the droplet contacts the surface of the test sample. For a total of five (5) substantially similar repeated test areas, the process is repeated. Use fresh test samples or ensure that the area wetted by the previous droplet is avoided during subsequent measurements.
[0471] On each image captured by the camera, the test sample surface and profile of the droplet are identified and used by the image analysis software to calculate the contact angle for each droplet image and recorded to the nearest 0.1 degree. The contact angle is the angle formed by the surface of the test sample and the tangent line to the surface of the droplet contacting the test sample. For each series of images from the test, time zero is the time when the droplet begins to contact the surface of the test sample. Measure and record the contact angle on the droplet image corresponding to time zero plus five (5) seconds. If the droplet has been completely absorbed by the test sample within 5 seconds, the contact angle at 5 seconds is reported as 0°. Repeat this process for five replicate test areas. Calculate the arithmetic mean of the contact angles of the five replicate test areas at time zero plus five seconds and report that value as the contact angle to the nearest 0.1 degree.
[0472] The wicking time is defined as the time required for the contact angle of a droplet absorbed into the test sample to decrease to a contact angle of <10°. The wicking time is measured by identifying the first image of a given series in which the contact angle has decreased to a contact angle of <10°, and then, based on that image, calculating and reporting the length of time elapsed from time zero. If a contact angle of less than 10° is not reached within 60 seconds, the wicking time is reported as 60 seconds. This process is repeated for five replicate test areas. The arithmetic mean of the wicking times for the five replicate test areas is calculated and reported to the nearest 0.1 millisecond.
[0473] Grayscale change test method within the product
[0474] The grayscale variation test method in the product is used to determine the uniformity of the grayscale value in the visually discernible area of the nonwoven fabric image. Use a flat scanner (a suitable scanner is the Epson Perfection V750 Pro, or equivalent, derived from Epson America Inc. (Long Beach CA)) that can scan a minimum of 24 colors and manually control color management at 150dpi to collect images. The scanner is connected to the computer running the color calibration software through an interface, and the color calibration software can utilize the corresponding reference file that meets ANSI method IT8.7 / 2-1993 for color reflection IT8 target calibration scanner (a suitable color calibration software is Monaco EZColor or i1Studio purchased from X-Rite Grand Rapids (MI), or equivalent). The color calibration software constructs the International Color Association (ICC) color profile for the scanner, and the color profile is used to use the image analysis program of the application program that supports the ICC profile to carry out color correction to the output image (a suitable program is Photoshop CS4, or equivalent, purchased from Adobe Systems Inc. (San Jose, CA)). The color corrected image is then converted to grayscale for subsequent grayscale image analysis (a suitable image analysis software is MATLAB available from The Mathworks, Inc. (Natick, MA)).
[0475] To obtain the sample, the absorbent article is secured to a rigid flat surface with adhesive tape in a planar configuration. Any leg elastic components present may be cut to facilitate laying the article flat. The outer boundaries of the area above the absorbent core of the article are identified and marked on the outward surface of the layer. The sample is removed from the lower layer of the article by cutting around the outer periphery of the article with a razor blade. The layer sample is carefully removed so that its longitudinal extension and lateral extension are maintained to avoid distortion of the material. If necessary, a freezing spray (such as Cyto-Freeze, Control Company (Houston TX) or equivalent) may be used to remove the sample from the lower layer. Prior to testing, the sample is conditioned for 2 hours at a temperature of about 23°C ± 2°C and about 50% ± 2% relative humidity.
[0476] Turn on the scanner for 30 minutes prior to calibration and image acquisition. Deselect any automatic color correction or color management options that may be included in the scanner software. If automatic color management cannot be disabled, the scanner is not suitable for this application. Follow the color calibration software's recommended procedures to create and export an ICC color profile for the scanner. The color calibration software compares the acquired IT8 target images to the corresponding reference files to create and export an ICC color profile for the scanner, which will be applied within the image analysis program to correct the color of subsequent output images.
[0477] The scanner lid was opened and the sample was carefully placed flat on the center of the scanner glass with the outward-facing surface of the sample oriented toward the glass. Prior to acquiring the image, the sample was backed with a black glass tile (P / N 11-0050-30, purchased from HunterLab (Reston, VA), or equivalent). A 4-inch by 4-inch (101.6 mm by 101.6 mm) scan of the visually discernible area was acquired and imported into the image analysis software in reflective mode at a resolution of 150 dpi (approximately 5.9 pixels / mm) in 24-bit color. An ICC color profile was assigned to the image to produce a color-corrected RGB image. The RGB image was then converted to 8-bit grayscale based on the following weighted sum of the R, G, and B components.
[0478] Grayscale = 0.2989 × R + 0.5870 × G + 0.1140 × B
[0479] The image is smoothed and blurred by applying a 2D Gaussian filter, where the standard deviation of the Gaussian distribution (sigma) is equal to 4 and the borders are filled by repeating border elements. The calibrated and blurred grayscale image is saved in an uncompressed format (such as a TIFF file) before analysis.
[0480] Open the calibrated and blurred grayscale image in the image analysis software and divide it into a 4 × 4 grid. Measure and record the arithmetic mean grayscale value in each of the 16 regions. Calculate the standard deviation of the recorded means and report it as the grayscale change to the nearest 0.1.
[0481] Haralick Maximum Contrast Test Method
[0482] The Haralick maximum contrast value is based on the Haralick texture feature structure described in RM Haralick, K. Shanmugam and I. Dinstein, "Textural features for image classification", IEEE Transactions on Systems, Man and Cybernetics, Vol. 3, No. 6, pp. 610-621 (1973). The contrast texture feature structure is calculated by calculating the gray-level co-occurrence matrix (GLCM). The GLCM is a list of the frequencies of occurrence of different combinations of pixel brightness values (grayscale) in an image. The GLCM is normalized so that the sum of its elements is equal to 1. Each element (i, j) in the normalized GLCM is the joint probability occurrence of a pair of pixels with grayscale values i and j in the image with a defined spatial relationship, direction and distance. The contrast texture feature structure is calculated using the following formula:
[0483]
[0484] where i is the number of rows, j is the number of columns, and p(i,j) is the probability value recorded for element (i,j) in the GLCM.
[0485] The Haralick maximum contrast value is obtained by analyzing the calibrated and blurred grayscale images collected and saved in the in-product grayscale variation test method using image analysis software (a suitable image analysis software is MATLAB available from Mathworks, Inc., Natick, MA). Using a symmetric grayscale co-occurrence matrix with 256 grayscales, the Haralick contrast value is calculated in the 0° (horizontal), 45°, 90° (vertical), and 135° directions at each of the integer pixel distances between the pixel of interest and its neighboring pixels, ranging from 1 to 150. For the 150 Haralick contrast values obtained in the 0° direction, the maximum contrast value (rounded to the nearest integer) is identified and recorded as the Haralick maximum 0° contrast value. For the 150 Haralick contrast values obtained in the 90° direction, the maximum contrast value (rounded to the nearest integer) is identified and recorded as the Haralick maximum 90° contrast value. For each of the 150 integer pixel distances, calculate the arithmetic mean contrast value between all four directions (i.e., at each particular integer pixel distance, calculate the arithmetic mean, which is the average of: 1) the 0° Haralick contrast value at that integer pixel distance, 2) the 45° Haralick contrast value at that integer pixel distance, 3) the 90° Haralick contrast value at that integer pixel distance, and 4) the 135° Haralick contrast value at that integer pixel distance). And from those 150 calculated averages, identify the maximum of those averages and record it as the Haralick maximum average contrast value (rounded to the nearest integer).
[0486] Grayscale contrast slope test method
[0487] Grayscale contrast slope values are obtained by analyzing the calibrated and blurred grayscale images collected and saved in the In-Product Grayscale Variation Test Method using image analysis software (a suitable image analysis software is ImageJ v. 1.52 or equivalent, National Institute of Health, USA).
[0488] Open the image in the image analysis software, and identify the border between two adjacent regions. The border between the regions is identified by visual discrimination or difference of the intensity characteristics when compared with other regions in the sample. For example, the regional boundary can be identified based on visually distinguishing the difference when compared with another region in the sample. Or any one of the intensity characteristics described in detail herein can be used to distinguish the regional boundary on the physical sample itself or the grayscale image, such as the change of basis weight. Once the boundary between the two regions is identified, the maximum circular region of interest that can be inscribed in each region is drawn so that the inscribed circle is adjacent to each other at the boundary between the two regions. The smaller of the two inscribed circles is identified, and the larger circular region of interest is replaced with one of the same size as the smaller region so that the two regions of interest are still in contact at the adjoining point. The arithmetic mean gray value in the two circular regions of interest is calculated. The linear distance closest to 0.001mm is measured between the centers of the two circles. The grayscale contrast slope is calculated by dividing the absolute value difference of the average grayscale of the two regions by the distance between their centers. This value is recorded as the grayscale contrast slope closest to 0.01 gray / mm.
[0489] Grayscale variation test method between products
[0490] Use the grayscale variation test method between products to determine the uniformity of the grayscale value between six independent repetition nonwoven fabric images of the same visually discernible area pattern.Use the flat scanner (suitable scanner is the EpsonPerfection V750 Pro deriving from Epson America Inc. (Long Beach CA), or equivalent) that can scan minimum 24 colors and manually control color management with 150dpi to collect images.The scanner is connected with the computer running color calibration software by interface, and this color calibration software can utilize the corresponding reference file that meets ANSI method IT8.7 / 2-1993 for color reflection IT8 target calibration scanner (suitable color calibration software is Monaco EXColor or i1Studio purchased from X-Rite Grand Rapids (MI), or equivalent).The color calibration software has constructed the International Color Association (ICC) color profile for scanner, and this color profile is used for the image analysis program of the application program that supports ICC profile to carry out color correction to output image (suitable program is purchased from Adobe Systems Inc. (San Jose, CA) Photoshop CS4, or equivalent). The color corrected image is then converted to grayscale for subsequent grayscale image analysis (a suitable image analysis software is MATLAB available from The Mathworks, Inc. (Natick, MA)).
[0491] To obtain each sample in the sample, the absorbent article is fixed to a rigid flat surface with adhesive tape in a planar configuration. Any leg elastic components present can be cut to facilitate the article to lie flat. The outer boundaries of the area above the absorbent core of the article are identified and marked on the outward surface of the layer. The sample is removed from the lower layer of the article by cutting around the outer periphery of the article with a razor blade. Carefully remove the layer sample so that its longitudinal extension and lateral extension are maintained to avoid distortion of the material. If necessary, a freezing spray (such as Cyto-Freeze, Control Company (Houston TX) or equivalent) can be used to remove the sample from the lower layer. Six replicate samples obtained from six substantially similar absorbent articles of the same package are prepared for analysis. Before testing, the sample is conditioned for 2 hours at a temperature of about 23°C ± 2°C and about 50% ± 2% relative humidity.
[0492] Turn on the scanner for 30 minutes prior to calibration and image acquisition. Deselect any automatic color correction or color management options that may be included in the scanner software. If automatic color management cannot be disabled, the scanner is not suitable for this application. Follow the color calibration software's recommended procedures to create and export an ICC color profile for the scanner. The color calibration software compares the acquired IT8 target images to the corresponding reference files to create and export an ICC color profile for the scanner, which will be applied within the image analysis program to correct the color of subsequent output images.
[0493] The scanner lid was opened and the sample was carefully placed flat on the center of the scanner glass with the outward surface of the sample oriented toward the glass. Before collecting the image, the sample was backed with a black glass tile (P / N 11-0050-30, purchased from HunterLab (Reston, VA), or equivalent). Images of the visually discernible area were collected and imported into the image analysis software at a resolution of 150 dpi (about 5.9 pixels / mm) in 24-bit color in reflective mode. An ICC color profile was assigned to the image to produce a color-corrected RGB image. The RGB image was then converted to 8-bit grayscale according to the weighted sum of the following R, G, and B components.
[0494] Grayscale = 0.2989 × R + 0.5870 × G + 0.1140 × B
[0495] The image is smoothed and blurred by applying a 2D Gaussian filter with a standard deviation of the Gaussian distribution (sigma) equal to 4 and borders filled with repeating border elements. The calibrated and blurred grayscale image is saved in an uncompressed format (such as a TIFF file) prior to analysis. This procedure is repeated for each of the six samples to obtain six repeated images of the same visually discernible area.
[0496] Each of the six calibrated and blurred grayscale images was opened in the image analysis software. The arithmetic mean grayscale value of each of the six images was measured and recorded. The standard deviation of the recorded mean was calculated and reported as the grayscale change to the nearest 0.1.
[0497] Example / combination:
[0498] 1. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0499] wherein the first visually discernible area has a Gray Scale Variation of between about 0.1 and about 10.0 as measured according to the In-Article Gray Scale Variation Test Method defined herein, and wherein the forming belt has a %KA of between about 2% and about 35%.
[0500] 2. A forming belt according to paragraph 1, wherein the gray scale variation is between about 0.1 and about 7.0.
[0501] 3. A forming belt according to paragraph 1, wherein the gray scale variation is between about 0.1 and about 4.1.
[0502] 4. A forming belt according to paragraph 1, wherein the gray scale variation is less than 4.2.
[0503] 5. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0504] wherein the first visually discernible area has a Haralick Maximum Average Contrast value of between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0505] Wherein the forming belt has a %KA between about 2% and about 35%.
[0506] 6. The forming belt of paragraph 5 wherein the Haralick Maximum Average Contrast value is between about 100 and about 600.
[0507] 7. The forming belt of paragraph 5 wherein the Haralick Maximum Average Contrast Value is greater than 80.
[0508] 8. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0509] wherein the first visually discernible area has a Haralick Maximum 90° Contrast value of between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0510] Wherein the forming belt has a %KA between about 2% and about 35%.
[0511] 9. The forming belt of paragraph 8 wherein the Haralick Maximum 90° Contrast value is between about 100 and about 600.
[0512] 10. The forming belt of paragraph 8 wherein the Haralick Maximum 90° Contrast Value is greater than 80.
[0513] 11. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first region and a second region, the first region and the second region having a difference in value of an intensity property;
[0514] wherein the first visually discernible area has a Haralick Maximum 0° Contrast value of between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0515] Wherein the forming belt has a %KA between about 2% and about 35%.
[0516] 12. The forming belt of paragraph 11 wherein the Haralick Maximum 0° Contrast value is between about 100 and about 600.
[0517] 13. The forming belt of paragraph 11 wherein the Haralick Maximum 0° Contrast value is greater than 80.
[0518] 14. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0519] wherein the first visually discernible area has a grayscale variation between about 0.1 and about 10.0 as measured according to the In-Article Grayscale Variation Test Method defined herein; and
[0520] and
[0521] wherein the first visually discernible area has a Haralick Maximum Average Contrast value of between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0522] Wherein the forming belt has a %KA between about 2% and about 35%.
[0523] 15. The forming belt of paragraph 14, wherein the gray scale varies between about 0.1 and about 7.0
[0524] between.
[0525] 16. The forming belt of paragraph 14, wherein the gray scale varies between about 0.1 and about 4.1
[0526] between.
[0527] 17. A forming belt according to paragraph 14, wherein the gray scale variation is less than 4.2.
[0528] 18. The forming belt of paragraph 14 wherein the Haralick Maximum Average Contrast value is between about 100 and about 600.
[0529] 19. The forming belt of paragraph 14 wherein the Haralick Maximum Average Contrast Value is greater than 80.
[0530] 20. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity characteristic, wherein at least one of the micro-regions has a Grayscale Contrast Slope of between about 5.0 and about 35.0 as measured according to the Grayscale Contrast Slope Test Method defined herein,
[0531] Wherein the forming belt has a %KA between about 2% and about 35%.
[0532] 21. The forming belt of paragraph 20, wherein the grayscale contrast slope is between about 11.0 and about 25.0.
[0533] 22. A forming belt as described in paragraph 20 wherein the grayscale contrast slope is greater than 11.0.
[0534] 23. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a microregion comprising a first region and a second region, the first region and the second region having a difference in value of an intensity characteristic, wherein the first visually discernible area has a periodic Haralick wave response as determined according to the Haralick Maximum Contrast Test method defined herein, wherein
[0535] The formed belt has a %KA between about 2% and about 35%.
[0536] 24. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensive property, wherein the intensive property is one or more of the following:
[0537] a.Thickness,
[0538] b. Basis weight, and
[0539] c. Bulk density;
[0540] wherein the first visually discernible area has a Gray Scale Variation of between about 0.1 and about 10.0 as measured according to the In-Article Gray Scale Variation Test Method defined herein, and wherein the forming belt has a %KA of between about 2% and about 35%.
[0541] 25. The forming belt of paragraph 24, wherein the gray scale varies between about 0.1 and about 7.0
[0542] between.
[0543] 26. The forming belt of paragraph 24, wherein the gray scale varies between about 0.1 and about 4.1
[0544] between.
[0545] 27. A forming belt according to paragraph 24, wherein the gray scale variation is less than 4.2.
[0546] 28. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensive property, wherein the intensive property is one or more of the following:
[0547] a.Thickness,
[0548] b. Basis weight, and
[0549] c. Bulk density;
[0550] wherein the first visually discernible area has a Haralick Maximum Average Contrast value of between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0551] Wherein the forming belt has a %KA between about 2% and about 35%.
[0552] 29. The forming belt of paragraph 28 wherein the Haralick Maximum Average Contrast value is between about 100 and about 600.
[0553] 30. The forming belt of paragraph 28 wherein the Haralick Maximum Average Contrast Value is greater than 80.
[0554] 31. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensive property, wherein the intensive property is one or more of the following:
[0555] a.Thickness,
[0556] b. Basis weight, and
[0557] c. Bulk density;
[0558] wherein the first visually discernible area has a Haralick Maximum 90° Contrast value of between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0559] Wherein the forming belt has a %KA between about 2% and about 35%.
[0560] 32. The forming belt of paragraph 31 wherein the Haralick Maximum 90° Contrast value is between about 100 and about 600.
[0561] 33. The forming belt of paragraph 31 wherein the Haralick Maximum 90° Contrast Value is greater than 80.
[0562] 34. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensive property, wherein the intensive property is one or more of the following:
[0563] a.Thickness,
[0564] b. Basis weight, and
[0565] c. Bulk density;
[0566] wherein the first visually discernible area has a Haralick Maximum 0° Contrast value of between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0567] Wherein the forming belt has a %KA between about 2% and about 35%.
[0568] 35. The forming belt of paragraph 34 wherein the Haralick Maximum 0° Contrast value is between about 100 and about 600.
[0569] 36. A forming belt according to paragraph 34 wherein the Haralick Maximum 0° Contrast Value is greater than 80.
[0570] 37. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property, wherein the intensity property is one or more of the following:
[0571] a.Thickness,
[0572] b. Basis weight, and
[0573] c. Bulk density;
[0574] wherein the first visually discernible area has a grayscale variation between about 0.1 and about 10.0 as measured according to the In-Article Grayscale Variation Test Method defined herein;
[0575] wherein the first visually discernible area has a Haralick Maximum Average Contrast value between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein, and
[0576] Wherein the forming belt has a %KA between about 2% and about 35%.
[0577] 38. A forming belt according to paragraph 37, wherein the gray scale variation is between about 0.1 and 7.0.
[0578] 39. The forming belt of paragraph 37, wherein the gray scale varies between about 0.1 and about 4.1
[0579] between.
[0580] 40. A forming belt as described in paragraph 37 wherein the gray scale variation is less than 4.2.
[0581] 41. The forming belt of paragraph 37 wherein the Haralick Maximum Average Contrast value is between about 100 and about 600.
[0582] 42. The forming belt of paragraph 37 wherein the Haralick Maximum Average Contrast Value is greater than 80.
[0583] 43. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensive property, wherein the intensive property is one or more of the following:
[0584] a.Thickness,
[0585] b. Basis weight, and
[0586] c. Bulk density;
[0587] wherein at least one of the micro-regions has a grayscale contrast slope between about 10.0 and about 30.0 as measured according to the grayscale contrast slope test method defined herein,
[0588] Wherein the forming belt has a %KA between about 2% and about 35%.
[0589] 44. A forming belt as described in paragraph 43, wherein the grayscale contrast slope is between about 11.0 and about 25.0.
[0590] 45. A forming belt as described in paragraph 43 wherein the grayscale contrast slope is greater than 11.0.
[0591] 46. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensive property, wherein the intensive property is one or more of the following:
[0592] a.Thickness,
[0593] b. Basis weight, and
[0594] c. Bulk density;
[0595] Wherein the first visually discernible area has a periodic Haralick wave response as determined according to the Haralick Maximum Contrast Test Method defined herein, wherein the shaped band has a %KA between about 2% and about 35%.
[0596] 47. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area and a second visually discernible area on at least one of the first surface and the second surface, the first visually discernible area and the second visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0597] wherein at least one of the first visually discernible area and the second visually discernible area has a grayscale variation between about 0.1 and about 10.0 as measured according to the In-Article Grayscale Variation Test Method defined herein,
[0598] Wherein the forming belt has a %KA between about 2% and about 35%.
[0599] 48. A forming belt according to paragraph 47, wherein the gray scale variation is between about 0.1 and 7.0.
[0600] 49. The forming belt of paragraph 47, wherein the gray scale varies between about 0.1 and about 4.1
[0601] between.
[0602] 50. A forming belt according to paragraph 47, wherein the gray scale variation is less than 4.2.
[0603] 51. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area and a second visually discernible area on at least one of the first surface and the second surface, the first visually discernible area and the second visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0604] wherein the first visually discernible area and the second visually discernible area have a Haralick Maximum Average Contrast value between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0605] Wherein the forming belt has a %KA between about 2% and about 35%.
[0606] 52. The forming belt of paragraph 51 wherein the Haralick Maximum Average Contrast value is between about 100 and about 600.
[0607] 53. The forming belt of paragraph 51 wherein the Haralick Maximum Average Contrast Value is greater than 80.
[0608] 54. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area and a second visually discernible area on at least one of the first surface and the second surface, the first visually discernible area and the second visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0609] wherein the first visually discernible area and the second visually discernible area have a Haralick Maximum 90° Contrast value of between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0610] Wherein the forming belt has a %KA between about 2% and about 35%.
[0611] 55. The forming belt of paragraph 54 wherein the Haralick Maximum 90° Contrast value is between about 100 and about 600.
[0612] 56. The forming belt of paragraph 54 wherein the Haralick Maximum 90° Contrast Value is greater than 80.
[0613] 57. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area and a second visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0614] wherein the first visually discernible area and the second visually discernible area have a Haralick Maximum 0° Contrast value between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0615] Wherein the forming belt has a %KA between about 2% and about 35%.
[0616] 58. A forming belt according to paragraph 57 wherein the Haralick Maximum 0° Contrast value is between about 100 and about 600.
[0617] 59. A forming belt according to paragraph 57 wherein the Haralick Maximum 0° Contrast Value is greater than 80.
[0618] 60. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area and a second visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property;
[0619] wherein the first visually discernible area and the second visually discernible area have a grayscale variation between about 0.1 and about 10.0 as measured according to the In-Article Grayscale Variation Test Method defined herein; and
[0620] wherein the first visually discernible area and the second visually discernible area have a Haralick Maximum Average Contrast value between about 80 and about 750 as measured according to the Haralick Maximum Contrast Test Method defined herein,
[0621] Wherein the forming belt has a %KA between about 2% and about 35%.
[0622] 61. A forming belt according to paragraph 60, wherein the gray scale variation is between about 0.1 and 7.0.
[0623] 62. The forming belt of paragraph 60, wherein the gray scale varies between about 0.1 and about 4.1
[0624] between.
[0625] 63. A forming belt according to paragraph 60, wherein the gray scale variation is less than 4.2.
[0626] 64. The forming belt of paragraph 60 wherein the Haralick Maximum Average Contrast value is between about 100 and about 600.
[0627] 65. The forming belt of paragraph 60 wherein the Haralick Maximum Average Contrast Value is greater than 80.
[0628] 66. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area and a second visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first region and a second region, the first region and the second region having a difference in value of an intensity property, wherein the intensity property is one of:
[0629] or more:
[0630] d. thickness,
[0631] e. Basis weight, and
[0632] f. Bulk density;
[0633] The nonwoven fabric has one or more of the following:
[0634] 1. The first visually discernible area has a grayscale variation between about 0.1 and about 10.0 as measured by the In-Article Grayscale Variation Test Method defined herein;
[0635] 2. The first visually discernible area has a Haralick maximum contrast ratio between about 80 and about 750 as measured by the Haralick maximum contrast ratio test method defined herein.
[0636] Maximum average contrast value;
[0637] 3. The first visually discernible area has a Haralick maximum contrast ratio between about 80 and about 750 as measured by the Haralick maximum contrast ratio test method defined herein.
[0638] Maximum 90° contrast value;
[0639] 4. The first visually discernible area has a Haralick maximum contrast ratio between about 80 and about 750 as measured by the Haralick maximum contrast ratio test method defined herein.
[0640] Maximum 0° contrast value; and
[0641] 5. at least one of the micro-regions has a grayscale contrast slope between about 5.0 and about 35.0 as measured according to the Grayscale Contrast Slope Test Method defined herein,
[0642] Wherein the forming belt has a %KA between about 2% and about 35%.
[0643] The dimensions and values disclosed herein are not to be understood as being strictly limited to the exact numerical values cited. Instead, unless otherwise indicated, each such dimension is intended to represent the stated value and a functionally equivalent range around that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm".
[0644] Unless expressly excluded or otherwise limited, each document cited herein, including any cross-referenced or related patent or patent application and any patent application or patent to which this application claims priority or the benefit of, is hereby incorporated by reference in its entirety. The citation of any document is not an admission that it is prior art to any of the present invention disclosed or claimed herein, or an admission that it, by itself or in combination with any one or more of the references, proposes, suggests, or discloses any such invention. In addition, to the extent that any meaning or definition of a term in this invention conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this invention shall govern.
[0645] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.
Claims
1. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property; wherein the first visually discernible area has a Haralick maximum average contrast value between 80 and 750 as measured by the Haralick maximum contrast test method; wherein the forming belt has a %KA between 2% and 35%, and wherein the forming belt has an Air Permeability in the range of 400 cfm to 800 cfm according to the Air Permeability Test Method, A symmetric gray-level co-occurrence matrix with 256 gray levels is used. At each of the integer pixel distances between the pixel of interest and its neighboring pixels, Haralick contrast values ranging from 1 to 150 are calculated in the 0°, 45°, 90°, and 135° directions. For the 150 Haralick contrast values obtained in the 0° direction, the maximum contrast value is identified and rounded to the nearest integer and recorded as the Haralick maximum 0° contrast value. For the 150 Haralick contrast values obtained in the 90° direction, the maximum contrast value is identified and rounded to the nearest integer and recorded as For the Haralick maximum 90° contrast value, at each specific integer pixel distance, calculate the arithmetic mean, which is the average of: 1) 0° Haralick contrast values at integer pixel distances, 2) 45° Haralick contrast values at integer pixel distances, 3) 90° Haralick contrast values at integer pixel distances, and 4) 135° Haralick contrast values at integer pixel distances, and from those 150 calculated averages, identify the maximum of the averages, round it to the nearest integer, and record it as the Haralick maximum average contrast value, Wherein %KA is calculated by dividing the sum of the areas of the resin forming the raised portions by the total area of the forming belt, and The air permeability test method is carried out on the FX3360 Portair air permeability tester.
2. The forming belt of claim 1, wherein the Haralick Maximum Average Contrast value is between 100 and 600.
3. The forming belt of claim 1 wherein the Haralick Maximum Average Contrast value is greater than 80.
4. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property; wherein the first visually discernible area has a Haralick maximum 90 degree contrast value between 80 and 750 as measured by the Haralick maximum contrast test method; wherein the forming belt has a %KA between 2% and 35%, and wherein the forming belt has an Air Permeability in the range of 400 cfm to 800 cfm according to the Air Permeability Test Method, wherein a symmetric gray-level co-occurrence matrix with 256 gray levels is used, at each of the integer pixel distances between the pixel of interest and its neighboring pixels, a Haralick contrast value is calculated in the 90° direction, ranging from 1 to 150, for the 150 Haralick contrast values obtained in the 90° direction, the maximum contrast value is identified and rounded to the nearest integer, which is recorded as the Haralick maximum 90° contrast value, for each of the 150 integer pixel distances, at each specific integer pixel distance, an arithmetic mean is calculated, which is the 90° Haralick contrast value at the integer pixel distance, and from those 150 calculated mean values, the maximum of the mean values is identified, rounded to the nearest integer, and recorded as the Haralick maximum 90° contrast value, Wherein %KA is calculated by dividing the sum of the areas of the resin forming the raised portions by the total area of the forming belt, and The air permeability test method is carried out on the FX3360 Portair air permeability tester.
5. The forming belt of claim 4 wherein the Haralick Maximum 90 Degree Contrast value is between 100 and 600.
6. The forming belt of claim 4 wherein the Haralick maximum 90 degree contrast value is greater than 80.
7. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property; wherein the first visually discernible area has a Haralick maximum 0 degree contrast value between 80 and 750 as measured by the Haralick maximum contrast test method; and wherein the forming belt has a %KA between 2% and 35%, and wherein the forming belt has an Air Permeability in the range of 400 cfm to 800 cfm according to the Air Permeability Test Method, wherein a symmetric gray-level co-occurrence matrix with 256 gray levels is used, at each of the integer pixel distances between the pixel of interest and its neighboring pixels, a Haralick contrast value is calculated in the 0° direction, ranging from 1 to 150, for the 150 Haralick contrast values obtained in the 0° direction, the maximum contrast value is identified and rounded to the nearest integer, which is recorded as the Haralick maximum 0° contrast value, at each specific integer pixel distance, the arithmetic mean is calculated, which is the 0° Haralick contrast value at the integer pixel distance, and from those 150 calculated mean values, the maximum of the mean values is identified, rounded to the nearest integer, and recorded as the Haralick maximum 0° contrast value, Wherein %KA is calculated by dividing the sum of the areas of the resin forming the raised portions by the total area of the forming belt, and The air permeability test method is carried out on the FX3360 Portair air permeability tester.
8. The forming belt of claim 7, wherein the Haralick Maximum 0 Degree Contrast value is between 100 and 600.
9. The forming belt of claim 7 wherein the Haralick Maximum 0 Degree Contrast Value is greater than 80.
10. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property; wherein the first visually discernible area has a grayscale variation between 0.1 and 10.0 as measured by the grayscale variation test method within the product; and wherein the first visually discernible area has a Haralick Maximum Average Contrast value between 80 and 750 as measured according to the Haralick Maximum Contrast Test Method, wherein the forming belt has a %KA between 2% and 35%, and wherein the forming belt has an air permeability in the range of 400 cfm to 800 cfm according to the Air Permeability Test Method, wherein an image is captured using a flatbed scanner capable of scanning at least 24-bit color at 150 dpi and manually controlling color management, and the flatbed scanner is calibrated by color calibration software using a corresponding reference file that complies with ANSI method IT8.7 / 2-1993 for a color reflective IT8 target, the color calibration software constructs an International Color Association color profile for the flatbed scanner, the color profile is used to color correct the output image using an image analysis program using an application that supports the International Color Association profile, and then the color corrected image is converted to grayscale for grayscale image analysis, wherein the RGB image is converted to 8-bit grayscale according to the weighted sum of the R, G and B components as follows, Grayscale = 0.2989 × R + 0.5870 × G + 0.1140 × B The image was smoothed and blurred by applying a 2D Gaussian filter, where the standard deviation of the Gaussian distribution was equal to 4 and the borders were filled by repeating border elements. The calibrated and blurred grayscale image was saved in an uncompressed format before analysis. Open the calibrated and blurred grayscale image in an image analysis software and divide it into a 4 × 4 grid. Measure and record the arithmetic mean grayscale value in each of the 16 regions. Calculate the standard deviation of the recorded mean and report it as grayscale variation. A symmetric gray-level co-occurrence matrix with 256 gray levels is used. At each of the integer pixel distances between the pixel of interest and its neighboring pixels, Haralick contrast values ranging from 1 to 150 are calculated in the 0°, 45°, 90°, and 135° directions. For the 150 Haralick contrast values obtained in the 0° direction, the maximum contrast value is identified and rounded to the nearest integer and recorded as the Haralick maximum 0° contrast value. For the 150 Haralick contrast values obtained in the 90° direction, the maximum contrast value is identified and rounded to the nearest integer and recorded as For the Haralick maximum 90° contrast value, at each specific integer pixel distance, calculate the arithmetic mean, which is the average of: 1) 0° Haralick contrast values at integer pixel distances, 2) 45° Haralick contrast values at integer pixel distances, 3) 90° Haralick contrast values at integer pixel distances, and 4) 135° Haralick contrast values at integer pixel distances, and from those 150 calculated averages, identify the maximum of the averages, round it to the nearest integer, and record it as the Haralick maximum average contrast value, Wherein %KA is calculated by dividing the sum of the areas of the resin forming the raised portions by the total area of the forming belt, and The air permeability test method is carried out on the FX3360 Portair air permeability tester.
11. A forming belt according to claim 10, wherein the grey scale variation is between 0.1 and 7.
0.
12. A forming belt according to claim 10, wherein the grey scale variation is between 0.1 and 4.
1.
13. The forming belt of claim 10, wherein the gray scale variation is less than 4.
2.
14. The forming belt of claim 10, wherein the Haralick Maximum Average Contrast value is between 100 and 600.
15. The forming belt of claim 10 wherein said Haralick Maximum Average Contrast value is greater than 80.
16. A forming belt for producing a nonwoven fabric, the nonwoven fabric comprising a first surface and a second surface and at least a first visually discernible area on at least one of the first surface and the second surface, the first visually discernible area having a pattern of three-dimensional features, each of the three-dimensional features defining a micro-region comprising a first area and a second area, the first area and the second area having a difference in value of an intensity property; wherein at least one of the micro-regions has a grayscale contrast slope between 5.0 and 35.0 as measured by a grayscale contrast slope test method; wherein the forming belt has a %KA between 2% and 35%, and wherein the forming belt has an Air Permeability in the range of 400 cfm to 800 cfm according to the Air Permeability Test Method, wherein an image is captured using a flatbed scanner capable of scanning at least 24-bit color at 150 dpi and manually controlling color management, and the flatbed scanner is calibrated by color calibration software using a corresponding reference file that complies with ANSI method IT8.7 / 2-1993 for a color reflective IT8 target, the color calibration software constructs an International Color Association color profile for the flatbed scanner, the color profile is used to color correct the output image using an image analysis program using an application that supports the International Color Association profile, and then the color corrected image is converted to grayscale for grayscale image analysis, wherein the RGB image is converted to 8-bit grayscale according to the weighted sum of the R, G and B components as follows, Grayscale = 0.2989 × R + 0.5870 × G + 0.1140 × B The image was smoothed and blurred by applying a 2D Gaussian filter, where the standard deviation of the Gaussian distribution was equal to 4 and the borders were filled by repeating border elements. The calibrated and blurred grayscale image was saved in an uncompressed format before analysis. The image is opened in image analysis software and the boundary between two adjacent regions is identified, the boundary between the regions is identified by visual discrimination of intensity characteristics when compared to other regions within the sample, once the boundary between the two regions is identified, the largest circular region of interest that can be inscribed within each region is drawn so that the inscribed circles abut each other at the boundary between the two regions, the smaller of the two inscribed circles is identified and the larger circular region of interest is replaced with one of equal size to the smaller region so that the two regions of interest still touch at the abutment point, the arithmetic mean grayscale value within the two circular regions of interest is calculated, the linear distance is measured between the centers of the two circles, the grayscale contrast slope is calculated by dividing the absolute value difference in the mean grayscale of the two regions by the distance between their centers, Wherein %KA is calculated by dividing the sum of the areas of the resin forming the raised portions by the total area of the forming belt, and The air permeability test method is carried out on the FX3360 Portair air permeability tester.
17. A forming belt as claimed in claim 16 wherein the grey scale contrast slope is between 11.0 and 25.
0.
18. The forming belt of claim 16 wherein said grayscale contrast slope is greater than 11.0.
Citation Information
Patent Citations
Disposable Absorbent Article With Improved Acquisition System
US20080312622A1
High bulk tissue sheets and products
US20130199741A1
Process for the production of a nonwoven web of a continuous filament yarn
US3423266A
Continuous filament nonwoven web
US3692618A
Apparatus for producing non-woven fleeces
US3802817A